Precursor glasses and glass-ceramics comprising crystalline phase having Jeffbenite crystalline structure

By forming the glass-ceramic material of the jeffbenite crystal phase in the glass, the problem of insufficient mechanical properties of existing glass products is solved, and a glass-ceramic material with high hardness and stiffness is achieved, suitable for the shells and display surfaces of mobile electronic devices.

CN119461854APending Publication Date: 2025-02-18CORNING INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411086183.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-05
Filing Date
2024-08-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing glass products are prone to damage when accidentally dropped or conventional contact and lack sufficient mechanical properties to meet the needs of mobile electronic devices.

Method used

By forming a glass-ceramic material with a crystalline phase in the glass, the excellent hardness and stiffness characteristics are used to improve the mechanical properties of the material.

Benefits of technology

The high hardness and stiffness of glass-ceramic materials are achieved, suitable for thin and light display surfaces of mobile phones and tablets, while opaque or tinted glass-ceramics can be used in telephones and tablets housings, reducing dependence on lithium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461854A_ABST
    Figure CN119461854A_ABST
Patent Text Reader

Abstract

Disclosed herein are glass-ceramics and glass-ceramic articles comprising a crystalline phase comprising a jeffbenite crystalline structure, glasses that can become these by ceramization, and methods of making and using the same.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority to U.S. application serial number 63 / 532,167, filed on August 11, 2023, the contents of which are of primary importance herein and are incorporated herein by reference in their entirety. Technical Field

[0003] This specification relates to glasses and glass-ceramic articles made therefrom. Background Art

[0004] Glass articles, such as cover glasses, glass backs, housings, etc., are used in both consumer and commercial electronic devices, such as smartphones, tablet computers, portable media players, personal computers, and cameras. The mobile nature of these portable devices makes the devices and the glass articles contained therein particularly vulnerable to accidental drops onto hard surfaces, such as the ground. In addition, glass articles, such as cover glasses, may include "touch" functionality, which requires the glass article to be contacted by a variety of objects, including a user's finger and / or a stylus device. Therefore, the glass article must be strong enough to withstand accidental drops and routine contact without damage.

[0005] Therefore, there is a need for alternative materials having improved mechanical properties relative to glass. Summary of the invention

[0006] Features and advantages of the precursor glasses and glass-ceramics described herein will be set forth in the following detailed description, and in part will be apparent to those skilled in the art from that description or learned by practicing the embodiments described herein, including the following detailed description, claims, and accompanying drawings.

[0007] Applicants have discovered that the jeffbenite crystalline structure associated with inclusions in "ultra-deep" diamonds, as explained herein, can provide a number of useful advantages and properties if formed as a crystalline phase in a glass-ceramic in a glass. Applicants believe that a crystalline phase having the jeffbenite crystalline structure has never before been grown or otherwise formed in a glass-ceramic. Applicants also believe that a crystalline phase having the jeffbenite crystalline structure has never before been formed or otherwise incorporated into a glass-ceramic article such as a glass-ceramic sheet, glass-ceramic container, window, panel, housing, board, counter, cookware, rod, fiber or other such article. Furthermore, in contrast to jeffbenite in diamond or isolated jeffbenite, Applicants believe that a crystalline phase having the jeffbenite crystal structure has never been included in an article having isotropic material properties (e.g., properties such as tensile strength, elasticity, and fracture toughness that remain the same when tested in different directions), which can be effectively achieved by including relatively small grains, as disclosed herein, randomly oriented and uniformly distributed within a residual glass to form a glass-ceramic, or randomly oriented and uniformly distributed within another isotropic solid medium (e.g., a polymer). Applicants believe that a glass-ceramic having a crystalline phase having the jeffbenite crystal structure has never been made before, even in nature; has never been grown from a precursor glass; and has never been formed at temperatures (e.g., <1600K, <1400K) and pressures (e.g., <12GPa, such as <10GPa, <8GPa, <1GPa, such as even 1atm) as disclosed herein. Supported by the current findings, it is now possible to produce crystals with the jeffbenite crystalline structure in a single batch, in part by not requiring the extreme temperatures and pressures associated with ultra-deep formations within the Earth's mantle.

[0008] In addition, the glass-ceramics described herein can achieve excellent hardness and stiffness values ​​and thus enable thin and light mobile phone and tablet display surfaces. The same features allow opaque or colored glass-ceramics to be used in phone and tablet housings. Furthermore, these glass-ceramics may not contain lithium but can still be strengthened by ion exchange, thereby reducing the demand for this scarce resource.

[0009] Aspect 121 includes a glass-ceramic comprising a glass phase and one or more crystalline phases, wherein at least one of the one or more crystalline phases comprises jeffbenite.

[0010] Aspect 122 includes an article comprising: a surface; and a body within the surface, wherein the body comprises the glass-ceramic according to aspect 121.

[0011] Aspect 123 includes the article of aspect 122, wherein the surface is a first surface, the article further comprising a second surface opposite the first surface, wherein the body is located between the first and second surfaces such that the article is a sheet.

[0012] Aspect 124 includes a glass-ceramic article comprising a first surface; a second surface opposite the first surface; a perimeter defining a shape of the glass-ceramic article; and a phase combination comprising one or more crystalline phases and a glass phase, wherein the one or more crystalline phases include a crystalline phase comprising a jeffbenite crystal structure.

[0013] Aspect 125 includes the article of aspect 124, wherein the crystalline phase comprising the jeffbenite crystal structure is the predominant crystalline phase.

[0014] Aspect 126 includes the article of aspect 124 or 125, wherein the phase combination comprises greater than or equal to 10 wt. % and less than or equal to 85 wt. % of one or more crystalline phases and greater than or equal to 15 wt. % and less than or equal to 90 wt. % of a glass phase, based on the weight of the glass-ceramic article.

[0015] Aspect 127 includes the article of aspects 124-126, wherein the amount of jeffbenite crystalline structures in the one or more crystalline phases is greater than or equal to 90 weight percent to less than or equal to 100 weight percent, based on the total weight of the one or more crystalline phases.

[0016] Aspect 128 includes the article of aspects 124-127, wherein at least some of the grains of at least one crystalline phase comprising the jeffbenite crystalline structure have a maximum dimension of greater than or equal to 20 nm to less than or equal to 500 nm.

[0017] Aspect 129 includes the article of aspects 124-128, wherein the glass-ceramic article is substantially free of lithium.

[0018] Aspect 130 includes the article of aspects 124-129, wherein the crystalline phase comprising jeffbenite crystalline structures has a composition according to the formula:

[0019] (Mg,R 2+ ) 3+x (Zr,R 4+ ) x Al 2-2x SiO 12 ,

[0020] Where R 2+ represents one or more divalent metal cations, R 4+represents one or more tetravalent metal cations, and x is greater than or equal to 0 and less than or equal to 1.

[0021] Aspect 131 includes the article of manufacture of aspect 130, wherein R 2+ is selected from Ca 2+ , Mn 2+ , Fe 2+ 、Zn 2+ one or more divalent metal cations, and wherein R 4+ Selected from Ti 4+ Sn 4+ , Hf 4+ One or more tetravalent metal cations.

[0022] Aspect 132 includes the article of aspects 124-131, wherein the glass-ceramic article has an average transmittance of at least 75% for light in the wavelength range of 400 nm to 800 nm at an article thickness of 0.6 mm.

[0023] Aspect 133 includes the article of aspects 124-131, wherein the glass-ceramic article has an average transmittance in a range of 20% to less than 75% for light in a wavelength range of 400 nm to 800 nm at an article thickness of 0.6 mm.

[0024] Aspect 134 includes the article of aspects 124-131, wherein the glass-ceramic article has an average transmittance in the range of less than 20% for light in the wavelength range of 400 nm to 800 nm at an article thickness of 0.6 mm.

[0025] Aspect 135 includes a glass-ceramic article, comprising, in mole percent (mol%), based on oxides: 35 mol% or more and 65 mol% or less SiO2; 2.5 mol% or more and 20 mol% or less Al2O3; 7 mol% or more and 65 mol% or less MgO; 0 mol% or more and 10 mol% or less CaO; 0 mol% or more and 5 mol% or less B2O3; 0 mol% or more and 7 mol% or less ZrO; % to less than or equal to 15 mol % of ZnO; wherein the glass-ceramic comprises a phase combination comprising one or more crystalline phases and a glass phase, the one or more crystalline phases comprising a crystalline phase comprising a jeffbenite crystalline structure.

[0026] Aspect 136 includes the article of aspect 135, further comprising less than or equal to 3 mol % Li2O.

[0027] Aspect 137 includes the article of aspect 135, wherein the glass-ceramic article is substantially free of Li2O.

[0028] Aspect 138 includes the article of aspects 135-137, wherein the glass-ceramic article comprises greater than or equal to 1.5 mol % to less than or equal to 3 mol % ZrO 2 .

[0029] Aspect 139 includes the article of aspects 135-138, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 12 mol % HfO 2 , wherein the sum of ZrO 2 and HfO 2 is greater than 1 mol %.

[0030] Aspect 140 includes the article of aspects 135-139, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 4 mol % P2O5.

[0031] Aspect 141 includes the article of aspects 135-140, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 7 mol % La 2 O 3 .

[0032] Aspect 142 includes the article of aspects 135-141, wherein Na2O (mol %) + K2O (mol %) is greater than or equal to 2 mol % and less than or equal to 15 mol %.

[0033] Aspect 143 includes the article of aspects 135-142, wherein Na2O (mol%) / (Na2O (mol%)+K2O (mol%)) is greater than or equal to 0.2.

[0034] Aspect 144 includes the article of aspects 135-143, further comprising greater than or equal to 0.3 mol % and less than or equal to 7 mol % TiO 2 .

[0035] Aspect 145 includes the article of aspects 135-144, wherein ZrO2 (mol %) + TiO2 (mol %) is greater than or equal to 2 mol %.

[0036] Aspect 146 includes the article of aspects 135-145, wherein ZrO2 (mol%) / (ZrO2 (mol%)+TiO2 (mol%)) is greater than or equal to 0.3.

[0037] Aspect 147 includes the article of aspects 135-146, comprising greater than or equal to 1 mol % to less than or equal to 12 mol % ZnO.

[0038] Aspect 148 includes the article of aspects 135-147, further comprising greater than or equal to 1 mol % and less than or equal to 8 mol % BaO.

[0039] Aspect 149 includes the article of aspects 135-148, further comprising greater than or equal to 0.2 mol % to less than or equal to 1.7 mol % of at least one of CaO and SrO.

[0040] Aspect 150 includes the article of aspects 135-149, further comprising greater than or equal to 0 mol % and less than or equal to 0.2 mol % SnO 2 .

[0041] Aspect 151 includes the article of aspects 135-150, further comprising greater than or equal to 1x10 -6 mol % to less than or equal to 10 mol % of a colorant, the colorant comprising at least one of Au, Ag, Cr2O3, CuO, NiO, CoO, Co3O4, TiO2, Cr2O3, V2O5, MnO and CeO2.

[0042] Aspect 152 includes the article of aspect 151, wherein the glass-ceramic article comprises: an L* value greater than or equal to 0 and less than or equal to 100; an a* value greater than or equal to −128 and less than or equal to 127; and a b* value greater than or equal to −128 and less than or equal to 127.

[0043] Aspect 153 includes the article of aspects 135-152, wherein the glass-ceramic article has an elastic modulus greater than or equal to 50 GPa and less than or equal to 200 GPa.

[0044] Aspect 154 includes the article of aspects 135-153, wherein the glass-ceramic article has a strength of greater than or equal to 600 kgf / mm 2 To less than or equal to 1400kgf / mm 2 Vickers hardness.

[0045] Aspect 155 includes the article of aspects 135-154, wherein the glass-ceramic article is an ion exchange glass-ceramic article.

[0046] Aspect 156 includes the article of aspect 155, wherein the glass-ceramic article is heated to 450° C. in a salt bath containing Na + Ion pair K + Ion exchange process with a particle size greater than or equal to 200 μm 2 Diffusion rate / hour.

[0047] Aspect 157 includes the article of aspect 155 or aspect 156, wherein the glass-ceramic composition is heated to 500°C in a salt bath containing Na + Ion pair K+ The ion exchange process can have a particle size greater than or equal to 1500 μm 2 Diffusion rate / hour.

[0048] Aspect 158 ​​includes the article of aspects 155-157, wherein the ion exchange glass-ceramic article has a compression depth of about 30 μm or greater.

[0049] Aspect 159 includes the article of aspects 155-158, wherein the ion-exchanged glass-ceramic article has a compression depth greater than or equal to 3% of the thickness of the ion-exchanged glass-ceramic article.

[0050] Aspect 160 includes the article of aspects 155-159, wherein the ion exchange glass-ceramic article has a central tension greater than or equal to 10 MPa and less than or equal to 200 MPa.

[0051] Aspect 161 includes the article of aspects 155-160, wherein the ion-exchanged glass-ceramic article has a surface compressive stress greater than or equal to 100 MPa and less than or equal to 1 GPa.

[0052] Aspect 162 includes an article of manufacture of any of the preceding aspects, further comprising limitations, attributes, or features disclosed herein but not explicitly or inherently disclosed in International Application No. PCT / US2023 / 012905, filed on February 13, 2023, which is incorporated herein by reference in its entirety.

[0053] Aspect 163 includes the article of any preceding aspect, wherein the article is a sheet having a total thickness variation greater than 0.1 μm and less than 1 mm.

[0054] Aspect 164 includes the article of any preceding aspect, wherein the article has a blunted corner or edge.

[0055] Aspect 165 includes the article of any preceding aspect, wherein the article is coated with a coating other than conductive carbon.

[0056] Aspect 166 includes the article of any preceding aspect, wherein the article is coated and the coating has a thickness greater than 20 nm and less than 50 μm.

[0057] Aspect 167 includes a device comprising the article of any preceding aspect adhered thereto.

[0058] Aspect 168 includes a device comprising the article of any of the preceding aspects that is curved.

[0059] Aspect 169 includes a device comprising the article of any of the preceding aspects in a strain.

[0060] Aspect 170 includes a device comprising the article of any preceding aspect located within 10 cm of an electrical component of the device.

[0061] Aspect 171 includes an apparatus comprising the article of any preceding aspect and an antenna.

[0062] It should be understood that both the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overview or framework to understand the nature and characteristics of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate the various embodiments described herein and, together with the description, serve to explain the principles and operation of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 is a top view of an electronic device including a glass-ceramic article;

[0064] Figure 2 is a perspective view of an electronic device including a glass-ceramic article;

[0065] Figure 3 is a SEM micrograph of the crystalline structure of a glass-ceramic comprising a crystalline phase having a jeffbenite crystalline structure;

[0066] Figure 4 is a SEM micrograph of the crystalline structure of a glass-ceramic comprising a crystalline phase having a jeffbenite crystalline structure;

[0067] Figure 5 is a high temperature X-ray diffraction 2θ diagram, which shows the change of the stability range of various crystalline phases in the glass-ceramic containing a crystalline phase having a jeffbenite crystal structure and a tetragonal zirconia crystalline phase with temperature;

[0068] Fig. 6A is a SEM micrograph of the crystalline structure of a glass-ceramic comprising a crystalline phase having a jeffbenite crystalline structure;

[0069] Figure 6B is a SEM micrograph of the crystalline structure of a glass-ceramic comprising a crystalline phase having a jeffbenite crystalline structure;

[0070] Figure 6C is a SEM micrograph of the crystalline structure of a glass-ceramic comprising a crystalline phase having a jeffbenite crystalline structure;

[0071] Fig.6Dis a SEM micrograph of the crystalline structure of a glass-ceramic comprising a crystalline phase having a jeffbenite crystalline structure;

[0072] Fig. 6E is a SEM micrograph of the crystalline structure of a glass-ceramic comprising a crystalline phase having a jeffbenite crystalline structure;

[0073] Fig. 6F is a SEM micrograph of the crystalline structure of a glass-ceramic comprising a crystalline phase having a jeffbenite crystalline structure;

[0074] Figure 7 is an X-ray diffraction 2θ pattern showing a crystalline phase having a jeffbenite crystal structure in an exemplary glass-ceramic article;

[0075] Fig. 8A A glass-ceramic article is schematically depicted;

[0076] Figure 8B schematically depicts a cross section of the glass-ceramic article;

[0077] Fig. 9 A glass-ceramic article is schematically depicted;

[0078] Fig.10 Plotting the total transmittance of a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure as a function of wavelength;

[0079] Fig.11 The diffuse transmittance of a glass-ceramic article including a crystalline phase having a jeffbenite crystal structure varies with wavelength;

[0080] Fig.12 The axial transmittance of a glass-ceramic article including a crystalline phase having a jeffbenite crystal structure is plotted as a function of wavelength;

[0081] Fig.13 The variation of the scattering ratio of a glass-ceramic article including a crystalline phase having a jeffbenite crystal structure as a function of wavelength is plotted;

[0082] Fig.14 A window of the MDI Jade software used to characterize glass-ceramic products is depicted;

[0083] Fig.15 A window of the MDI Jade software used to characterize glass-ceramic products is depicted;

[0084] Fig.16A window of the MDI Jade software used to characterize glass-ceramic products is depicted;

[0085] Fig.17 A window of the Bruker Topas software used to characterize glass-ceramic products is depicted;

[0086] Fig.18 A window of the Bruker Topas software used to characterize glass-ceramic products is depicted;

[0087] Fig.19 A window of the Bruker Topas software used to characterize glass-ceramic products is depicted;

[0088] Fig. 20 A window of the Bruker Topas software used to characterize glass-ceramic products is depicted;

[0089] Fig.21 An XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure is depicted;

[0090] Fig. 22 An XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure is depicted;

[0091] Fig.23 An XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure is depicted;

[0092] Fig.24 An XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure is depicted;

[0093] Fig.25 An XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure is depicted;

[0094] Fig.26 An XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure is depicted;

[0095] Fig. 27 An XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure is depicted;

[0096] Fig.28 An XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure is depicted;

[0097] Fig.29An XRD spectrum of a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure is depicted;

[0098] Fig.30 is a photograph of a transparent glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure;

[0099] Fig.31 Plotting the total transmittance of a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure as a function of wavelength;

[0100] Fig.32 The diffuse transmittance of a glass-ceramic article including a crystalline phase having a jeffbenite crystal structure varies with wavelength;

[0101] Fig.33 The variation of the scattering ratio of a glass-ceramic article including a crystalline phase having a jeffbenite crystal structure as a function of wavelength is plotted;

[0102] Fig.34 plots the mole % of oxides as a function of depth for a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure; and

[0103] Fig.35 Plotted is the variation in mole % of oxides as a function of depth for a glass-ceramic article comprising a crystalline phase having a jeffbenite crystal structure. DETAILED DESCRIPTION

[0104] Various embodiments of the precursor glass and the glass-ceramic articles made therefrom will now be referred to in detail. According to an embodiment, the glass-ceramic article comprises a first surface, a second surface opposite to the first surface, and a periphery defining the shape of the glass-ceramic article. The glass-ceramic article may also include a phase combination comprising one or more crystalline phases and a glass phase, wherein the one or more crystalline phases comprise a crystalline phase comprising a jeffbenite crystalline structure. Various embodiments of the precursor glass, the glass-ceramic articles made therefrom, and the method for manufacturing the glass-ceramic article will be specifically described herein with reference to the accompanying drawings.

[0105] Ranges may be expressed herein as from "about" one particular value and / or to "about" another particular value. When such ranges are expressed, another embodiment includes from a particular value and / or to another particular value. Similarly, when a value is expressed as an approximation by using the antecedent "about," it is understood that the particular value forms another embodiment. It is also understood that the endpoints of each range are significant both relative to the other endpoint and independently of the other endpoint.

[0106] As used herein, directional terms—eg, up, down, right, left, front, back, top, bottom—are made with reference only to the drawings in which they are drawn and are not intended to imply an absolute orientation.

[0107] Unless otherwise expressly stated, any method described herein is in no way intended to be interpreted as requiring that its steps be performed in a particular order, nor is it intended to require a particular orientation for any apparatus. Thus, in the absence of a method claim actually reciting the order in which its steps are to be followed, or any apparatus claim actually reciting the order or orientation of the individual components, or in the absence of another express statement in the claim or specification that the steps are to be limited to a particular order, or in the absence of a particular order or orientation of the components of the apparatus, no order or orientation is intended to be inferred in any respect. This applies to any possible non-explicit basis for interpretation, including: logical issues regarding the arrangement of steps, operational flow, order of components, or orientation of components; obvious meaning derived from grammatical organization or punctuation; and the number or type of embodiments described in the specification.

[0108] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a" component includes aspects having two or more such components unless the context clearly dictates otherwise.

[0109] The term "substantially free", when used to describe the concentration and / or absence of a particular constituent component in a precursor glass or glass-ceramic composition, means that the constituent component is not intentionally added to the precursor glass or glass-ceramic composition. However, the precursor glass or glass-ceramic composition may contain trace amounts of constituent components that are contaminants or impurities in an amount of less than 0.05 mol%.

[0110] In the embodiments of the precursor glass or glass-ceramic compositions described herein, the concentrations of the constituent components (eg, SiO 2 , Al 2 O 3 , etc.) are specified in mole percent (mol %) on an oxide basis unless otherwise specified.

[0111] Transmittance data (total transmittance) were measured using a Lambda 950 UV / Vis spectrophotometer manufactured by PerkinElmer Inc. (Waltham, MA, USA). The Lambda 950 instrument was equipped with a 150 mm integrating sphere. An open beam baseline and Collect data with reference to the reflective disk. For total transmittance (Total Tx), mount the sample at the entrance point of the integrating sphere. For diffuse transmittance (Diffuse Tx), remove the A reference reflective disk is used to allow on-axis light to leave the sphere and enter the light trap. Zero-offset measurements of the diffuse portion are performed without a sample to determine the efficiency of the light trap. To correct the diffuse transmittance measurement, the zero-offset contribution is subtracted from the sample measurement using the following formula: Diffuse Tx = Diffuse Reflectance 测量值 - (Zero offset * (Total Tx / 100)). For all wavelengths, the scatter ratio is measured as follows: (% Diffuse Tx / % Total Tx).

[0112] The term "transparent," when used to describe the articles herein, refers to articles having an average transmittance of at least 75% for light in the wavelength range of 400 nm to 800 nm, inclusive, at an article thickness of 0.6 mm.

[0113] The term "translucent", unless otherwise specified in the claims, when used to describe the articles herein, refers to articles having an average transmittance in the range of 20% to less than 75% for light in the wavelength range of 400nm to 800nm ​​(inclusive) at an article thickness of 0.6mm.

[0114] The term "opaque", when used to describe a glass-ceramic article formed from the glass-ceramic composition herein, means that the glass-ceramic composition has an average transmittance of less than 20% for light in the wavelength range of 400 nm to 800 nm (inclusive) at an article thickness of 0.6 mm when measured at normal incidence.

[0115] As used herein, the term "CIELAB color space" refers to a color space defined by the International Commission on Illumination (CIE) in 1976. It represents color as three values: L* represents brightness from black (0) to white (100), a* represents from green (-) to red (+), and b* represents from blue (-) to yellow (+). Unless otherwise specified, L*, a*, and b* values ​​are indicated for a product thickness of 0.4 mm to 5 mm (including endpoints) in the thickness direction of the sample under F2 illumination and a 10° standard observer angle. Unless otherwise specified, this means that each thickness within this thickness range has L*, a*, and b* coordinates that fall within the specified range of L*, a*, and b* coordinates. For example, a colored glass product with an L* value in the range of 55 to 96.5 means that each thickness in the range of 0.4 mm to 5 mm (e.g., 0.6 mm, 0.9 mm, 2 mm, etc.) has an L* in the range of 55 to 96.5.

[0116] The size of the crystallites of one or more crystalline phases of the glass-ceramics described herein is measured using scanning electron microscopy.

[0117] As used herein, the term "melting point" refers to the temperature at which the viscosity of a precursor glass or glass-ceramic composition is 200 poise (20 Pa*s).

[0118] As used herein, the term "softening point" refers to the viscosity of a precursor glass or glass-ceramic composition at 1 x 10 7.6 moor(1x10 6.6 The softening point is measured by the parallel plate viscosity method, which measures the viscosity of inorganic glass from 10 7 Up to 10 9 moor(10 6 Up to 10 8 The variation of viscosity (Pa*s) with temperature is similar to ASTM C1351M.

[0119] As used herein, the term "liquidus viscosity" refers to the viscosity of a glass-ceramic at the onset of devitrification (ie, at the liquidus temperature, as measured by the gradient furnace method according to ASTM C829-81).

[0120] The elastic modulus (also known as Young's modulus) of the glass-based article is given in units of Gigapascals (GPa).The elastic modulus of glass is measured on a bulk sample of each glass-based article by resonant ultrasonic spectroscopy according to ASTM C623.

[0121] Vickers hardness can be measured using ASTM C1326 and C1327 (and progeny thereof, all of which are incorporated herein by reference) "Standard Test Methods for Vickers Indentation Hardness of Advanced Ceramics," ASTM International, Conshohocken, PA, U.S. In some embodiments, the glass-ceramic exhibits such Vickers indentation crack initiation load values ​​after chemical strengthening by ion exchange.

[0122] Fracture toughness can be measured prior to ion exchange strengthening of the glass-ceramic using a herringbone notched short beam in accordance with ASTM C1421-10 "Standard Test Methods for Determination of Fracture Toughness of Advanced Ceramics at Ambient Temperature".

[0123] Compressive stress (including surface compressive stress) is measured with a surface stress meter (FSM), such as a commercially available instrument such as the FSM-6000 manufactured by Orihara Industrial Co., Ltd. (Japan). Surface stress measurements rely on the measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass-ceramic. The SOC is then measured according to Procedure C (Glass Disk Method) described in ASTM Standard C770-16 entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient", the contents of which are incorporated herein by reference in their entirety. Depth of compression (DOC) is also measured using an FSM. Maximum central tension (CT) values ​​are measured using a scattered light polarizer (SCALP) technique known in the art.

[0124] The expressions "depth of compression" and "DOC" refer to the location in the glass-ceramic where compressive stress transforms into tensile stress.

[0125] As used herein, the expression "glass precursor" or "precursor glass" refers to a glass or glass article that contains one or more nucleating agents and / or nucleating sites (e.g., within the body of the material, which may be uniformly distributed therein and throughout the body), which, upon heat treatment, at least partially cause (e.g., promote) nucleation of at least one crystalline phase in the glass.

[0126] As used herein, the expression "glass-ceramic" refers to a material or article formed from a precursor glass material after nucleation of at least one crystalline phase in the precursor glass, wherein the nucleation causes the glass-ceramic to include a residual glass phase and at least one crystalline phase (see generally Fig. 9 and related public content).

[0127] As used herein, the expression "major crystalline phase" refers to a crystalline phase present in a glass-ceramic in an amount (as a % by weight of the glass-ceramic) greater than the amount (as a % by weight of any other individual crystalline phase present in the glass-ceramic. For example, if the glass-ceramic comprises crystalline phases A, B, and C and crystalline phase A is the major crystalline phase, then the amount of crystalline phase A in the glass-ceramic is greater than the amount of crystalline phase B in the glass-ceramic and greater than the amount of crystalline phase C in the glass-ceramic.

[0128] Articles formed from glass-ceramics generally have improved fracture toughness relative to articles formed from glass. This improvement may be attributed to the presence of crystalline grains in the glass-ceramics, which may hinder crack propagation. The fracture toughness of glass-ceramics can be improved by reducing the number of grains per unit volume of glass-ceramics, that is, by increasing the grain size of the glass-ceramics. However, the transparency or optical transmittance of glass-ceramics may decrease with the increase of grain size. In particular, when the grain size is greater than 300nm, the visible light transparency of glass-ceramics may be significantly reduced. Therefore, some glass-ceramics may have relatively good mechanical properties (such as fracture toughness) and relatively poor optical properties (such as optical transparency or optical transmittance), or have relatively poor mechanical properties and relatively good optical properties, but do not have relatively good mechanical properties and relatively good optical properties at the same time.

[0129] In addition, some glass-ceramics can be strengthened by ion exchange process, in which smaller alkali metal ions in glass-ceramics are exchanged for larger alkali metal ions from, for example, a molten alkali metal salt bath. As an example, lithium-containing glass-ceramics can be strengthened by ion exchange by placing glass-ceramics in a bath of molten alkali metal salts (such as sodium salts and / or potassium salts) to promote the exchange of lithium ions in glass-ceramics with sodium and / or potassium ions in the bath. However, the demand for using lithium in various applications recently has increased the cost of lithium raw materials and reduced availability, thereby increasing the total cost of lithium-containing glass-ceramics that can be strengthened by ion exchange. Glass-ceramics described herein do not need lithium to promote desired ion exchange properties.

[0130] Disclosed herein are precursor glasses and glass-ceramics formed therefrom that will alleviate the aforementioned problems.

[0131] For example, now refer to Fig. 9, which schematically depicts a glass-ceramic article 810 according to one or more embodiments shown and described herein. As described herein, the expression "glass-ceramic" refers to a material or article formed from a precursor glass material after nucleation of at least one crystalline phase in the precursor glass, such that the glass-ceramic includes a residual glass phase and at least one crystalline phase. Thus, the glass-ceramic article 810 includes both a glass phase 812 (e.g., an amorphous glass; a single-phase glass or a multi-phase glass) and a polycrystalline ceramic phase (e.g., grains of a primary crystalline phase 814, optionally with grains of a secondary crystalline phase 816). The glass phase 812 may be referred to as "residual glass" or "residual glass phase". It is contemplated that the grains of the crystalline phase 814, 816 may be unevenly distributed or directionally grown, such as by localizing heat with a laser, or by positioning and / or orienting nucleation sites to direct the growth of the grains of the crystalline phase 814, 816, and embodiments contemplated include such properties; however, generally in the glass-ceramics disclosed herein, the grains of the crystalline phase 814, 816 may be uniformly or uniformly distributed and randomly oriented within the glass phase 812, such as throughout some, most, or all of the glass phase of the glass-ceramic article 810. Furthermore, once nucleated from the precursor glass, the grains of the crystalline phase 814, 816 may be grown to contact each other, overlap each other, interlock with each other, and / or fill more volume of the glass-ceramic article 810. Growing the grains of the crystalline phases 814, 816 to different sizes can affect the properties of the glass-ceramic article 810, and when the grains of the crystalline phases 814, 816 have grain sizes as disclosed herein and the article has dimensions as disclosed herein, such properties can be isotropic, with the grains of the crystalline phases 814, 816 being consistently, uniformly positioned and randomly oriented. After the grains of the crystalline phases 814, 816 nucleate and grow, the glass phase 812 will surround (e.g., contact, encapsulate, encapsulate) individual or clusters of grains of the crystalline phases 814, 816. The glass-ceramic article 810 can have more than one glass phase 812 and / or more than one crystalline phase, as shown with the crystalline phases 814, 816.

[0132] Embodiments of the glass-ceramics described herein, such as Fig. 9In the embodiment illustrated in, there is a phase combination comprising one or more crystalline phases and a glass phase. At least one crystalline phase comprises a jeffbenite crystalline structure. A crystalline phase having a jeffbenite crystalline structure refers to a crystalline phase identified as jeffbenite by X-ray diffraction (XRD) analysis. For example, XRD data (such as an XRD spectrum) collected from a sample of a glass-ceramic material and general composition information about the sample composition (such as the batch composition of the sample) can be input into the MDI Jadepowder XRD analysis software from Materials Data Inc. The software utilizes the input information and the International Diffraction Data Center Powder Diffraction File Version 4 Database (ICDD PDF-4 Database) to identify the crystalline phase in the sample based on the composition information of the sample and the crystalline structure of the phase as determined from the XRD data. In an embodiment, the phase combination of glass-ceramic can have at least one crystalline phase comprising a jeffbenite crystalline structure, as determined by the method.

[0133] Based on the foregoing, unless otherwise specified or further clarified herein, as in the claims or elsewhere, the expression "jeffbenite crystalline structure" refers to a crystalline phase or crystalline phase grains identified by XRD analysis as jeffbenite as described herein, and the further characterization provided herein may help to clarify various embodiments and forms of crystalline phases having jeffbenite crystalline structures that may be included and claimed.

[0134] In embodiments, the crystalline phase having the jeffbenite crystal structure is the primary crystalline phase in the glass-ceramic.The crystalline phase having the jeffbenite crystal structure may have properties in common with jeffbenite (eg, compositional properties, molecular structure properties, microstructural properties).

[0135] Jeffbenite, named after Jeffrey Harris and Ben Harte, is a mineral recently observed as an inclusion in diamonds from "ultra-deep" (e.g., depths > 300 km) within the Earth's mantle. Prior to its naming, jeffbenite was called tetragonal-almandine-pyrope-phase ("TAPP"). Jeffbenite can contain tetragonal Mg3Al2Si3O 12The term "tetragonal" refers to an originally cubic lattice stretched along one of its lattice vectors into a rectangular prism having a square base ("axa") and height ("c", different from "a"), as in space group I42d. The tetragonal crystal structure of jeffbenite may include a unit cell edge parameter α of about 6.5, such as 6.5231(1), such as within plus or minus 0.1 thereof, and a parameter c of about 18.2, such as 18.1756(3) angstroms, such as within plus or minus 0.1 thereof. A crystalline phase having a jeffbenite crystal structure may have a tetragonal structure of jeffbenite as described herein.

[0136] The density of Jeffbenite (by itself) may be about 3.6 g / cm 3 , such as 3.576g / cm 3 , such as adding or subtracting 0.1g / cm 3 The microhardness of Jeffbenite (as such) may be about 7, such as within plus or minus 1 thereof. Jeffbenite (as such) may be uniaxial (-), with a refractive index ω of about 1.7, such as 1.733(5), such as within plus or minus 0.1 thereof, and ε of about 1.7, such as 1.721, such as within plus or minus 0.1 thereof.

[0137] Although Mg3Al2Si3O 12 is the ideal form of jeffbenite, but jeffbenite can generally be described as a stoichiometric garnet composition similar to pyrope (Mg3Al2(SiO4)3)–almandine (Fe3Al2(SiO4)3), but with a tetragonal crystal structure and may include other elements. In other words, structurally, jeffbenite and crystals with the jeffbenite crystal structure can be described as (M1)(M2)2(M3)2(T1)(T2)2O 12 , wherein M1 comprises magnesium (e.g., is primarily magnesium), M2 comprises aluminum (e.g., is primarily aluminum), M3 comprises magnesium (e.g., is primarily magnesium), and T1 and T2 comprise silicon (both are primarily silicon), and wherein the two tetrahedra of such a crystalline structure do not share any oxygen with each other. Jeffbenite can be classified as an orthosilicate, such as a silicate containing tetrahedral groups SiO4, wherein the ratio of silicon to oxygen is 1 to 4.

[0138] In the embodiments of the glass-ceramics described herein, the crystalline phase comprising the jeffbenite crystal structure may comprise at least tetragonal Mg3Al2Si3O 12 , mainly composed of tetragonal Mg3Al2Si3O 12 composition (>50 wt%), essentially tetragonal Mg3Al2Si3O 12Composition, or tetragonal Mg3Al2Si3O 12 .

[0139] In embodiments of the glass-ceramics described herein, a crystalline phase comprising a jeffbenite crystalline structure (or a portion thereof) can be modified by the addition of zirconium oxide (ZrO2). Without intending to be bound by any theory, in the jeffbenite crystalline structure, aluminum oxide (i.e., aluminum contributor) can be at least partially replaced with magnesium oxide (i.e., magnesium contributor) and zirconium oxide (i.e., zirconium contributor). In such embodiments, the crystalline phase comprising a jeffbenite crystalline structure (or a portion thereof) can have a composition according to the formula: Mg 3+x Zr x Al 2-2x SiO 12 , wherein x is greater than or equal to 0 to less than or equal to 1. In an embodiment, x may be greater than or equal to 0 to less than or equal to 0.6. For example, but not limited to, a crystalline phase having a jeffbenite crystalline structure (or a portion thereof) may have the following composition: Mg3Al2Si3O 12 Mg 3.1 Zr 0.1 Al 1.8 SiO 12 Mg 3.2 Zr 0.2 Al 1.6 SiO 12 Mg 3.3 Zr 0.3 Al 1.4 SiO 12 Mg 3.4 Zr 0.4 Al 1.2 SiO 12 Mg 3.5 Zr 0.5 AlSi3O 12 Mg 3.6 Zr 0.6 Al 0.8 SiO 12 Mg 3.7 Zr 0.7 Al 0.6 SiO 12 Mg 3.8 Zr 0.8 Al 0.4 SiO 12 or Mg 3.9 Zr 0.9 Al 0.2 SiO 12 .

[0140] In embodiments of the glass-ceramics described herein, the crystalline phase comprising the jeffbenite crystalline structure (or a portion thereof) can be further modified by the addition of titanium dioxide, tin oxide, iron oxide (FeO), manganese oxide, and / or zinc oxide. For example, titanium dioxide (i.e., titanium contributor) and / or tin oxide (i.e., tin contributor) can replace up to 50% of the zirconium in the jeffbenite crystalline structure. Similarly, iron oxide (i.e., iron contributor), manganese oxide (i.e., manganese contributor), and / or zinc oxide (i.e., zinc contributor) can replace a portion of the magnesium in the jeffbenite crystalline structure. In such embodiments, the crystalline phase comprising the jeffbenite crystalline structure (or a portion thereof) can have a composition according to the formula: (Mg, Fe, Mn, Zn) 3+x (Zr,Ti,Sn) x Al 2-2x SiO 12 , wherein x is greater than or equal to 0 to less than or equal to 1. In an embodiment, x may be greater than or equal to 0 to less than or equal to 0.6. For example, but not limited to, a crystalline phase having a jeffbenite crystalline structure (or a portion thereof) may have the following composition: (Mg, Fe, Mn, Zn)3Al2Si3O 12 、(Mg,Fe,Mn,Zn) 3.1 (Zr,Ti,Sn) 0.1 Al 1.8 SiO 12 、(Mg,Fe,Mn,Zn) 3.2 (Zr,Ti,Sn) 0.2 Al 1.6 SiO 12 、(Mg,Fe,Mn,Zn) 3.3 (Zr,Ti,Sn) 0.3 Al 1.4 SiO 12 、(Mg,Fe,Mn,Zn) 3.4 (Zr,Ti,Sn) 0.4 Al 1.2 SiO 12 、(Mg,Fe,Mn,Zn) 3.5 (Zr,Ti,Sn) 0.5 AlSi3O 12 、(Mg,Fe,Mn,Zn) 3.6 (Zr,Ti,Sn) 0.6 Al 0.8 SiO 12 、(Mg,Fe,Mn,Zn) 3.7 (Zr,Ti,Sn) 0.7 Al 0.6SiO 12 、(Mg,Fe,Mn,Zn) 3.8 (Zr,Ti,Sn) 0.8 Al 0.4 SiO 12 or (Mg,Fe,Mn,Zn) 3.9 (Zr,Ti,Sn) 0.9 Al 0.2 SiO 12 In these embodiments, it is understood that the Fe, Mn, Zn, Ti, and Sn components in the formula are each optional and can form a composition without one or more of these elements. For example, the composition can be free of Fe but can include Mn, Ti, and Sn, or free of Sn but can include Fe, Mn, Zn, and Ti. Therefore, it is understood that the above reference formula can be written without one or more of Fe, Mn, Zn, Ti, and Sn.

[0141] It should be understood that other substitutions and modifications to the crystalline phase comprising the jeffbenite structure are contemplated and possible. For example, in the embodiments of the glass-ceramics described herein, the crystalline phase comprising the jeffbenite crystalline structure (or a portion thereof) can be modified by adding a metal oxide as a divalent metal cation (denoted as "R 2+ ”) to replace part of the magnesium in the jeffbenite crystalline structure. Examples of divalent metal cations include, but are not limited to, Ca 2+ , Mn 2+ , Fe 2+ 、Zn 2+ In these embodiments, the divalent metal cation may have an ionic radius of less than 1 angstrom (0.1 nm). Similarly, a crystalline phase comprising a jeffbenite crystalline structure (or a portion thereof) may be prepared by adding a metal oxide as a tetravalent metal cation (denoted as "R 4+ ”) to replace part of the zirconium in the jeffbenite crystalline structure. Examples of tetravalent metal cations include Ti 4+ Sn 4+ , Hf 4+ In such an embodiment, the crystalline phase comprising the jeffbenite crystalline structure (or a portion thereof) may have a composition according to the following formula: (Mg, R 2+ ) 3+x (Zr,R 4+ ) x Al 2-2x SiO 12, wherein x is greater than or equal to 0 to less than or equal to 1. In an embodiment, x may be greater than or equal to 0 to less than or equal to 0.6. For example, but not limited to, a crystalline phase having a jeffbenite crystalline structure (or a portion thereof) may have the following composition: (Mg, R 2+ )3Al2Si3O 12 、(Mg,R 2+ ) 3.1 (Zr,R 4+ ) 0.1 Al 1.8 SiO 12 、(Mg,R 2+ ) 3.2 (Zr,R 4+ ) 0.2 Al 1.6 SiO 12 、(Mg,R 2+ ) 3.3 (Zr,R 4+ ) 0.3 Al 1.4 SiO 12 、(Mg,R 2+ ) 3.4 (Zr,R 4+ ) 0.4 Al 1.2 SiO 12 、(Mg,R 2+ ) 3.5 (Zr,R 4+ ) 0.5 AlSi3O 12 、(Mg,R 2+ ) 3.6 (Zr,R 4+ ) 0.6 Al 0.8 SiO 12 、(Mg,R 2+ ) 3.7 (Zr,R 4+ ) 0.7 Al 0.6 SiO 12 、(Mg,R 2+ ) 3.8 (Zr,R 4+ ) 0.8 Al 0.4 SiO 12 or (Mg,R 2+ ) 3.9 (Zr,R 4+ ) 0.9 Al 0.2 SiO 12In these embodiments, it is understood that R 2+ and R 4+ Each of the components is optional and the composition can be formed without one or another of these elements. Therefore, it should be understood that the above reference formula can be written without R 2+ and R 4+ One or the other.

[0142] In an embodiment, the one or more crystalline phases of the phase combination may include one or more secondary crystalline phases. The one or more secondary crystalline phases may be present in the glass-ceramic in an amount less than the main crystalline phase. In an embodiment, the one or more secondary crystalline phases may include tetragonal zirconium oxide (ZrO2), ZrTiO4 or a combination thereof. However, it should be understood that other secondary crystalline phases may also be present in the resulting glass-ceramic. In an embodiment, one or more of the secondary crystalline phases may enter the structure of a crystalline phase having a jeffbenite crystalline structure (e.g., a second phase may be present in the lattice of the jeffbenite crystalline phase.

[0143] In embodiments, the phase combination of the glass-ceramic described herein comprises greater than or equal to 25 wt % of the one or more crystalline phases and less than or equal to 75 wt % of the glass phase, greater than or equal to 30 wt % of the one or more crystalline phases and less than or equal to 70 wt % of the glass phase, greater than or equal to 40 wt % of the one or more crystalline phases and less than or equal to 60 wt % of the glass phase, greater than or equal to 50 wt % of the one or more crystalline phases and less than or equal to 50 wt % of the glass phase, greater than or equal to 60 wt % of the one or more crystalline phases and less than or equal to 40 wt % of the glass phase, greater than or equal to 70 wt % of the one or more crystalline phases and less than or equal to 30 wt % of the glass phase, greater than or equal to 80 wt % of the one or more crystalline phases and less than or equal to 20 wt % of the glass phase, as determined by Rietveld analysis of an XRD spectrum. It should be understood that the crystalline phase content or glass content can be within the subrange formed by any and all of the aforementioned endpoints. In embodiments, the one or more crystalline phases and the glass phase may be uniformly distributed throughout the glass-ceramic. It should also be noted that at least some, most (>50 wt%), or substantially all of such crystalline phases may have a jeffbenite crystalline structure (e.g., as identified by XRD; tetragonal, stoichiometric garnet, Mg3Al2Si3O 12 and its variations).

[0144] SiO can be the main glass former in the precursor glass and glass-ceramic composition described herein and can play the role of stabilizing the network structure of glass-ceramic. In the precursor glass and glass-ceramic composition, SiO concentration should be high enough (e.g., greater than or equal to 35 mol %) to form a crystalline phase when the precursor glass is heat treated and the precursor glass is converted into glass-ceramic. SiO can be limited in amount (e.g., to less than or equal to 65 mol %) to control the melting point of the precursor glass or glass-ceramic composition, because the melting temperature of pure SiO or high SiO glass is undesirably high. Therefore, limiting SiO concentration can contribute to improving the solubility and formability of the precursor glass or glass-ceramic composition.

[0145] In embodiments, the precursor glass or glass-ceramic composition may include a positive amount of silicon dioxide, such as greater than the amount of impurities (0.05 mol% or greater), such as greater than or equal to 35 mol% to less than or equal to 65 mol% SiO2. In embodiments, the precursor glass or glass-ceramic composition may include greater than or equal to 35 mol% to less than or equal to 62 mol%, greater than or equal to 35 mol% to less than or equal to 59 mol%, greater than or equal to 35 mol% to less than or equal to 56 mol%, greater than or equal to 35 mol% to less than or equal to 53 mol%, greater than or equal to 35 mol% to less than or equal to 50 mol%, greater than or equal to 35 mol% to less than or equal to 47 mol%, greater than or equal to 35 mol% to less than or equal to 4 ... % to less than or equal to 65 mol %, 35 mol % to less than or equal to 41 mol %, 35 mol % to less than or equal to 38 mol %, 38 mol % to less than or equal to 65 mol %, 41 mol % to less than or equal to 65 mol %, 42 mol % to less than or equal to 65 mol %, 43 mol % to less than or equal to 65 mol %, 44 mol % to less than or equal to 65 mol %, 45 mol % to less than or equal to 65 mol %, 46 mol % to less than or equal to 65 mol %, % to less than 65 mol %, 47 mol % to less than 65 mol %, 48 mol % to less than 65 mol %, 49 mol % to less than 65 mol %, 50 mol % to less than 65 mol %, 51 mol % to less than 65 mol %, 52 mol % to less than 65 mol %, 53 mol % to less than 65 mol %, 54 mol % to less than 65 mol % In some embodiments, the precursor glass or glass-ceramic composition may include SiO2 in an amount of greater than or equal to 48 mol% to less than or equal to 54 mol%. In embodiments, the concentration of SiO2 may be greater than or equal to 40 mol%, 45 mol%, or 50 mol%. In embodiments, the concentration of SiO2 may be less than or equal to 65 mol%, 60 mol%, or 55 mol%, or any and all subranges formed by any of these endpoints. In some embodiments, the precursor glass or glass-ceramic composition may include SiO2 in an amount of greater than or equal to 48 mol% to less than or equal to 54 mol%. In embodiments, the concentration of SiO2 may be greater than or equal to 40 mol%, 45 mol%, or 50 mol%. In embodiments, the concentration of SiO2 may be less than or equal to 65 mol%, 60 mol%, or 55 mol%.

[0146] Like SiO2, Al2O3 can also stabilize the glass network and additionally provide improved mechanical properties and chemical durability to the glass-ceramic. The amount of Al2O3 can also be adjusted to control the viscosity of the precursor glass or glass-ceramic composition. However, if the amount of Al2O3 is too high, the viscosity of the glass melt may increase. In an embodiment, the precursor glass or glass-ceramic composition may include greater than or equal to 5 mol% to less than or equal to 20 mol% Al2O3. In embodiments, the concentration of Al2O3 in the precursor glass or glass-ceramic composition can be a positive amount, such as greater than the amount of the impurity (0.05 mol% or greater), such as greater than or equal to 5 mol% to less than or equal to 20 mol%, greater than or equal to 5 mol% to less than or equal to 19 mol%, greater than or equal to 5 mol% to less than or equal to 18 mol%, greater than or equal to 5 mol% to less than or equal to 17 mol%, greater than or equal to 5 mol% to less than or equal to 16 mol%, greater than or equal to 5 mol% to less than or equal to 15 mol%, greater than or equal to 5 mol% to less than or equal to 14 mol%, greater than or equal to 5 mol% to less than or equal to 13 mol%, greater than or equal to 5 mol% to less than or equal to 12 mol%, greater than or equal to 5 mol% to less than or equal to 11 mol%, greater than or equal to 5 mol% to less than or equal to 10 mol%, greater than or equal to 5 mol% to less than or equal to 9 mol%, greater than or equal to 5 mol% to less than or equal to 8 mol%, greater than or equal to 5 mol% to less than or equal to 7 mol%. %, 5 mol% or more and 6 mol% or less, 6 mol% or more and 20 mol% or less, 7 mol% or more and 20 mol% or less, 8 mol% or more and 20 mol% or less, 9 mol% or more and 20 mol% or less, 10 mol% or more and 20 mol% or less, 11 mol% or more and 20 mol% or less, 12 mol% or more and 20 mol% or less, 14 mol% or more and 20 mol% or less, 16 mol% or more and 20 mol% or less, 17 mol% or more and 21 mol% or less, 18 mol% or more and 22 mol% or less, 19 mol% or more and 20 mol% or less, 20 mol% or more and 21 mol% or more and 22 mol% or less, 23 mol% or more and 24 mol% or less, 25 mol% or more and 26 mol% or less, 27 mol% or more and 28 mol% or more, 29 mol% or more and 30 mol% or more, 31 mol% or more and 32 mol% or more In some embodiments, the concentration of Al2O3 in the precursor glass or glass-ceramic composition may be greater than or equal to 9 mol% to less than or equal to 13 mol%. In some embodiments, the concentration of Al2O3 in the precursor glass or glass-ceramic composition may be greater than or equal to 5 mol%, 7 mol%, or 10 mol%. In some embodiments, the concentration of Al2O3 in the precursor glass or glass-ceramic composition may be less than or equal to 20 mol%, 15 mol%, 12 mol%, or 10 mol%. In some embodiments, the concentration of Al2O3 may be less than or equal to 20 mol%, 15 mol%, 12 mol%, or 10 mol%.

[0147] In an embodiment, the precursor glass or glass-ceramic composition may include a positive amount of MgO, such as greater than the amount of impurities (0.05 mol% or greater), such as greater than or equal to 10 mol% to less than or equal to 45 mol% of MgO. In an embodiment, the precursor glass or glass-ceramic composition may include greater than or equal to 7 mol% to less than or equal to 65 mol% of MgO. The addition of MgO can increase the elastic modulus of the precursor glass and the resulting glass-ceramic glass. MgO can also replace Al2O3 in the glass network and produce a more open network structure, thereby improving the ion mobility in the glass network. Without intending to be bound by theory, the addition of MgO can increase the crystallinity of the glass-ceramic composition. In embodiments, the concentration of MgO in the precursor glass or glass-ceramic composition may be greater than or equal to 7 mol% and less than or equal to 65 mol%, greater than or equal to 7 mol% and less than or equal to 60 mol%, greater than or equal to 7 mol% and less than or equal to 55 mol%, greater than or equal to 7 mol% and less than or equal to 50 mol%, greater than or equal to 7 mol% and less than or equal to 48 mol%, greater than or equal to 7 mol% and less than or equal to 46 mol%, greater than or equal to 7 mol% and less than or equal to 44 mol%, greater than or equal to 7 mol% and less than or equal to 46 mol%, greater than or equal to 7 mol% and less than or equal to 47 mol%, greater than or equal to 7 mol% and less than or equal to 48 ... % to less than or equal to 30 mol %, greater than or equal to 7 mol % to less than or equal to 28 mol %, greater than or equal to 7 mol % to less than or equal to 26 mol %, greater than or equal to 7 mol % to less than or equal to 36 mol %, greater than or equal to 7 mol % to less than or equal to 34 mol %, greater than or equal to 7 mol % to less than or equal to 32 mol %, greater than or equal to 7 mol ... % to less than or equal to 10 mol %, 9 mol % to less than or equal to 50 mol %, 10 mol % to less than or equal to 50 mol %, 10 mol % to less than or equal to 15 mol %, 10 mol % to less than or equal to 24 mol %, 7 mol % to less than or equal to 22 mol %, 7 mol % to less than or equal to 20 mol %, 7 mol % to less than or equal to 18 mol %, 7 mol % to less than or equal to 16 mol %, 7 mol % to less than or equal to 14 mol %, 7 mol % to less than or equal to 12 mol %, 7 mol % to less than or equal to 10 mol %, 9 mol % to less than or equal to 50 mol %, 10 mol % to less than or equal to 15 mol % to less than or equal to 65 mol %, to less than or equal to 60 mol %, to less than or equal to 55 mol %, to less than or equal to 45 mol %, to less than or equal to 42 mol %, to less than or equal to 40 mol %, to less than or equal to 38 mol %, to less than or equal to 36 mol %, to less than or equal to 34 mol %,% to less than or equal to 32 mol%, 10 mol% to less than or equal to 30 mol%, 10 mol% to less than or equal to 28 mol%, 10 mol% to less than or equal to 26 mol%, 10 mol% to less than or equal to 24 mol%, 10 mol% to less than or equal to 22 mol%, 10 mol% to less than or equal to 20 mol%, 10 mol% to less than or equal to 18 mol%, 10 mol% to less than or equal to 16 mol%, 10 mol% to less than or equal to 14 mol%, 10 mol% to less than or equal to 12 ...2 mol%, 10 mol% to less than or equal to 16 mol%, 10 mol% to less than or equal to 16 mol%, 10 mol% to less than or equal to 16 mol%, 10 mol% to less than or equal to 16 mol%, 10 mol% to less than or equal to 16 mol%, 10 mol% to less than or equal to 16 mol%, 10 mol% to less than or equal to 16 mol%, 10 mol% to less than or equal % to less than or equal to 50 mol%, 12 mol% to less than or equal to 60 mol%, 12 mol% to less than or equal to 45 mol%, 13 mol% to less than or equal to 65 mol%, 13 mol% to less than or equal to 50 mol%, 14 mol% to less than or equal to 60 mol%, 14 mol% to less than or equal to 45 mol%, 15 mol% to less than or equal to 65 mol%, 15 mol% to less than or equal to 50 mol%, 16 mol% to less than or equal to 65 mol%, 16 mol% to less than or equal to 45 mol%, 17 mol% to less than or equal to 18 mol% % to less than or equal to 65 mol%, 17 mol% to less than or equal to 50 mol%, 18 mol% to less than or equal to 60 mol%, 18 mol% to less than or equal to 45 mol%, 19 mol% to less than or equal to 65 mol%, 19 mol% to less than or equal to 50 mol%, 20 mol% to less than or equal to 65 mol%, 20 mol% to less than or equal to 45 mol%, 21 mol% to less than or equal to 65 mol%, 21 mol% to less than or equal to 50 mol%, 22 mol% to less than or equal to 65 mol%, 22 mol% to less than or equal to % to less than or equal to 50 mol %, greater than or equal to 24 mol % to less than or equal to 60 mol %, greater than or equal to 24 mol % to less than or equal to 45 mol %, greater than or equal to 25 mol % to less than or equal to 65 mol %, greater than or equal to 25 mol % to less than or equal to 50 mol %, greater than or equal to 26 mol % to less than or equal to 60 mol %, greater than or equal to 26 mol % to less than or equal to 45 mol %, greater than or equal to 27 mol % to less than or equal to 65 mol %, greater than or equal to 27 mol % to less than or equal to 50 mol %, greater than or equal to 28 mol % to less than or equal to 60 mol %,28 mol% or more and 45 mol% or less, 29 mol% or more and 65 mol% or less, 29 mol% or more and 50 mol% or less, 30 mol% or more and 60 mol% or less, 30 mol% or more and 45 mol% or more, 31 mol% or more and 65 mol% or less, 31 mol% or more and 50 mol% or less, 32 mol% or more and 60 mol% or less, 32 mol% or more and 50 mol% or less 45 mol%, greater than or equal to 33 mol% and less than or equal to 65 mol%, greater than or equal to 33 mol% and less than or equal to 50 mol%, greater than or equal to 34 mol% and less than or equal to 60 mol%, greater than or equal to 34 mol% and less than or equal to 45 mol%, greater than or equal to 35 mol% and less than or equal to 65 mol%, greater than or equal to 35 mol% and less than or equal to 65 mol%, greater than or equal to 35 mol% and less than or equal to 50 mol%, greater than or equal to 36 mol% and less than or equal to 60 mol%, greater than or equal to 36 mol% % to less than or equal to 45 mol%, 37 mol% to less than or equal to 65 mol%, 37 mol% to less than or equal to 50 mol%, 38 mol% to less than or equal to 60 mol%, 38 mol% to less than or equal to 45 mol%, 39 mol% to less than or equal to 65 mol%, 39 mol% to less than or equal to 50 mol%, 40 mol% to less than or equal to 60 mol%, 40 mol% to less than or equal to 45 mol%, % to less than or equal to 50 mol%, greater than or equal to 42 mol% to less than or equal to 60 mol%, greater than or equal to 42 mol% to less than or equal to 45 mol%, greater than or equal to 43 mol% to less than or equal to 65 mol%, greater than or equal to 43 mol% to less than or equal to 50 mol%, greater than or equal to 45 mol% to less than or equal to 50 mol%, greater than or equal to 47 mol% to less than or equal to 50 mol%, or any and all subranges formed by any of these endpoints. In embodiments, the concentration of MgO in the precursor glass or glass-ceramic composition may be greater than or equal to 7 mol%, 10 mol%, 20 mol%, 25 mol%, or 30 mol%. In embodiments, the concentration of MgO may be less than or equal to 65 mol%, 60 mol%, 55 mol%, 50 mol%, 45 mol%, 40 mol%,35 mol % or 30 mol %. Without intending to be bound by theory, as the concentration of MgO in the glass-ceramic composition increases, the opacity of the glass-ceramic may increase. Likewise, as the concentration of MgO in the glass-ceramic composition decreases, the transparency may improve. However, if the concentration of MgO in the glass-ceramic composition is too low, the glass-ceramic composition may become turbid.

[0148] In an embodiment, the precursor glass or glass-ceramic composition may include Na2O. The addition of Na2O can reduce the liquidus viscosity of the glass, which in turn can help to form or shape the precursor glass. Na2O can also promote the ion exchange strengthening of the resulting glass-ceramic, because most of the Na2O present in the precursor glass will be separated into the residual glass phase after heat treatment (e.g., ceramization). In an embodiment, the concentration of Na2O in the precursor glass or glass-ceramic composition can be greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of impurities (0.05 mol% or greater)) to less than or equal to 15 mol%, greater than or equal to 0 mol% to less than or equal to 13 mol%, greater than or equal to 0 mol% to less than or equal to 11 mol%, greater than or equal to 0 mol% to less than or equal to 9 mol%, greater than or equal to 0 mol% to less than or equal to 7 mol%, greater than or equal to 0 mol% to less than or equal to 5 mol%, greater than or equal to 0 mol% to less than or equal to 3 mol%. mol %, greater than or equal to 0 mol % to less than or equal to 1 mol %, greater than or equal to 1 mol % to less than or equal to 15 mol %, greater than or equal to 1 mol % to less than or equal to 13 mol %, greater than or equal to 1 mol % to less than or equal to 11 mol %, greater than or equal to 1 mol % to less than or equal to 9 mol %, greater than or equal to 1 mol % to less than or equal to 7 mol %, greater than or equal to 1 mol % to less than or equal to 5 mol %, greater than or equal to 1 mol % to less than or equal to 3 mol %, greater than or equal to 2 mol % to less than or equal to 15 mol %, greater than or equal to 2 mol % % to less than or equal to 13 mol %, greater than or equal to 2 mol % to less than or equal to 11 mol %, greater than or equal to 2 mol % to less than or equal to 9 mol %, greater than or equal to 2 mol % to less than or equal to 7 mol %, greater than or equal to 2 mol % to less than or equal to 5 mol %, greater than or equal to 2 mol % to less than or equal to 3 mol %, greater than or equal to 3 mol % to less than or equal to 15 mol %, greater than or equal to 4 mol % to less than or equal to 15 mol %, greater than or equal to 5 mol % to less than or equal to 15 mol %, greater than or equal to 6 mol % to less than or equal to 15 mol % %, 7 mol % to less than or equal to 15 mol %, 8 mol % to less than or equal to 15 mol %, 9 mol % to less than or equal to 15 mol %, 10 mol % to less than or equal to 15 mol %, 11 mol % to less than or equal to 15 mol %, 12 mol % to less than or equal to 15 mol %, 13 mol % to less than or equal to 15 mol %, 14 mol % to less than or equal to 15 mol %, or any and all subranges formed by any of these endpoints. In embodiments, the concentration of NaO in the precursor glass or glass-ceramic composition may be greater than or equal to 0 mol %, 5 mol %, or 10 mol %.In embodiments, the concentration of Na2O may be less than or equal to 15 mol%, 10 mol%, or 5 mol%. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of Na2O.

[0149] In an embodiment, the precursor glass or glass-ceramic composition may include K2O. The addition of K2O can reduce the liquidus viscosity of the glass, which in turn can help to form or shape the precursor glass. K2O can also promote the ion exchange strengthening of the resulting glass-ceramic because most of the K2O will be separated into the glass phase after ceramicization. In an embodiment, the concentration of K2O in the precursor glass or glass-ceramic composition can be greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of impurities (0.05 mol% or greater)) to less than or equal to 15 mol%, greater than or equal to 0 mol% to less than or equal to 13 mol%, greater than or equal to 0 mol% to less than or equal to 11 mol%, greater than or equal to 0 mol% to less than or equal to 9 mol%, greater than or equal to 0 mol% to less than or equal to 7 mol%, greater than or equal to 0 mol% to less than or equal to 5 mol%, greater than or equal to 0 mol% to less than or equal to 3 mol%. %, greater than or equal to 0 mol% to less than or equal to 1 mol%, greater than or equal to 1 mol% to less than or equal to 15 mol%, greater than or equal to 1 mol% to less than or equal to 13 mol%, greater than or equal to 1 mol% to less than or equal to 11 mol%, greater than or equal to 1 mol% to less than or equal to 9 mol%, greater than or equal to 1 mol% to less than or equal to 7 mol%, greater than or equal to 1 mol% to less than or equal to 5 mol%, greater than or equal to 1 mol% to less than or equal to 3 mol%, greater than or equal to 2 mol% to less than or equal to 15 mol%, greater than or equal to 2 mol% % to less than or equal to 13 mol %, greater than or equal to 2 mol % to less than or equal to 11 mol %, greater than or equal to 2 mol % to less than or equal to 9 mol %, greater than or equal to 2 mol % to less than or equal to 7 mol %, greater than or equal to 2 mol % to less than or equal to 5 mol %, greater than or equal to 2 mol % to less than or equal to 3 mol %, greater than or equal to 3 mol % to less than or equal to 15 mol %, greater than or equal to 4 mol % to less than or equal to 15 mol %, greater than or equal to 5 mol % to less than or equal to 15 mol %, greater than or equal to 5 mol % to less than or equal to 15 mol % %, 6 mol % to less than or equal to 15 mol %, 7 mol % to less than or equal to 15 mol %, 8 mol % to less than or equal to 15 mol %, 9 mol % to less than or equal to 15 mol %, 10 mol % to less than or equal to 15 mol %, 11 mol % to less than or equal to 15 mol %, 12 mol % to less than or equal to 15 mol %, 13 mol % to less than or equal to 15 mol %, or any and all subranges formed by any of these endpoints. In embodiments, the concentration of KO in the precursor glass or glass-ceramic composition may be greater than or equal to 0 mol %, 5 mol %, or 10 mol %. In embodiments, the concentration of KO may be less than or equal to 15 mol %, 10 mol %, or 5 mol %.In embodiments, the precursor glass or glass-ceramic composition may be substantially free of K2O.

[0150] In embodiments, the precursor glass or glass-ceramic composition described herein may have Na2O (mol%) + KO (mol%) greater than or equal to 0 mol% and less than or equal to 15 mol%. In embodiments, the precursor glass or glass-ceramic composition described herein may have Na2O (mol%) + KO (mol%) greater than or equal to 0 mol% to less than or equal to 15 mol%, greater than or equal to 0 mol% to less than or equal to 13 mol%, greater than or equal to 0 mol% to less than or equal to 11 mol%, greater than or equal to 0 mol% to less than or equal to 9 mol%, greater than or equal to 0 mol% to less than or equal to 7 mol%, greater than or equal to 0 mol% to less than or equal to 5 mol%, greater than or equal to 1 mol% to less than or equal to 15 mol%, greater than or equal to 1 mol% to less than or equal to 13 mol%, greater than or equal to 1 mol% to less than or equal to 13 mol%, greater than or equal to 1 mol% to less than or equal to 13 mol%. % to less than or equal to 11 mol%, 1 mol% to less than or equal to 9 mol%, 1 mol% to less than or equal to 17 mol%, 1 mol% to less than or equal to 5 mol%, 2 mol% to less than or equal to 15 mol%, 2 mol% to less than or equal to 13 mol%, 2 mol% to less than or equal to 11 mol%, 2 mol% to less than or equal to 9 mol%, 2 mol% to less than or equal to 7 mol%, 2 mol% to less than or equal to 5 mol%, 3 mol% to less than or equal to 15 mol%, 3 mol% to less than or equal to 13 mol%, 2 mol% to less than or equal to 11 mol%, 2 mol% to less than or equal to 9 mol%, 2 mol% to less than or equal to 7 mol%, 2 mol% to less than or equal to 5 mol%, 3 mol% to less than or equal to 15 mol%, 3 mol% to less than or equal to 13 mol% mol% to less than or equal to 13 mol%, 3 mol% to less than or equal to 11 mol%, 3 mol% to less than or equal to 9 mol%, 3 mol% to less than or equal to 7 mol%, 3 mol% to less than or equal to 5 mol%, 4 mol% to less than or equal to 15 mol%, 4 mol% to less than or equal to 13 mol%, 4 mol% to less than or equal to 11 mol%, 4 mol% to less than or equal to 9 mol%, 4 mol% to less than or equal to 7 mol%, 4 mol% to less than or equal to 5 mol%, % to less than or equal to 15 mol %, greater than or equal to 5 mol % to less than or equal to 13 mol %, greater than or equal to 5 mol % to less than or equal to 11 mol %, greater than or equal to 5 mol % to less than or equal to 9 mol %, greater than or equal to 5 mol % to less than or equal to 7 mol %, greater than or equal to 6 mol % to less than or equal to 15 mol %, greater than or equal to 6 mol % to less than or equal to 13 mol %, greater than or equal to 6 mol % to less than or equal to 11 mol %, greater than or equal to 6 mol % to less than or equal to 9 mol %, greater than or equal to 6 mol % to less than or equal to 7 mol %, greater than or equal to 7 mol % to less than or equal to 15,mol %, greater than or equal to 7 mol % and less than or equal to 13 mol %, greater than or equal to 7 mol % and less than or equal to 11 mol %, greater than or equal to 7 mol % and less than or equal to 9 mol %, greater than or equal to 8 mol % and less than or equal to 15 mol %, greater than or equal to 8 mol % and less than or equal to 13 mol %, greater than or equal to 8 mol % and less than or equal to 11 mol %, greater than or equal to 8 mol % and less than or equal to 9 mol %, greater than or equal to 9 mol % and less than or equal to 15 mol %, greater than or equal to 9 mol % and less than % to less than or equal to 13 mol %, 9 mol % to less than or equal to 11 mol %, 10 mol % to less than or equal to 15 mol %, 10 mol % to less than or equal to 13 mol %, 10 mol % to less than or equal to 11 mol %, 11 mol % to less than or equal to 15 mol %, 11 mol % to less than or equal to 13 mol %, 13 mol % to less than or equal to 15 mol %, or any and all subranges formed by any of these endpoints. In embodiments, the concentration of Na2O (mol %) + KO (mol %) in the precursor glass or glass-ceramic composition may be greater than or equal to 2 mol %, 3 mol %, 5 mol %, or 10 mol %. In embodiments, the concentration of Na2O (mol %) + KO (mol %) may be less than or equal to 15 mol %, 10 mol %, or 5 mol %. In embodiments, Na2O (mol%) / (Na2O (mol%)+K2O (mol%)) may be greater than or equal to 0.2 or even greater than or equal to 0.3 to improve the ion exchangeability of the resulting glass-ceramic.

[0151] In embodiments, the ratio of Na2O (mol %) to KO (mol %) may be about 1:3, about 2:5, or about 1:1, such as in a particular composition as disclosed herein, the amount of Na2O in mol % is at least 33% or more of the amount of KO or vice versa (i.e., the amount of KO in mol % is at least 33% or more of the amount of Na2O), as shown in the examples, such as in an amount of Na2O in mol % is at least 40% or more of the amount of KO or vice versa, such as in an amount of Na2O in mol % is at least 50% or more of the amount of KO or vice versa, such as in an amount of Na2O in mol % is at least 60% or more of the amount of KO or vice versa, such as in an amount of Na2O in mol % is at least 70% or more of the amount of KO or vice versa, such as in an amount of Na2O in mol % is at least 80% or more of the amount of KO or vice versa, such as in an amount of Na2O in mol % is at least 90% or more of the amount of KO or vice versa. Without wishing to be bound by theory, it is believed that the ratio of Na2O (mol %) to K2O (mol %) can be adjusted to improve the transparency of the glass-ceramic composition.

[0152] In an embodiment, the precursor glass or glass-ceramic composition may include ZrO2. Without wishing to be bound by theory, it is believed that ZrO2 acts as a nucleating agent that promotes the nucleation of a crystalline phase having a jeffbenite crystal structure during heat treatment at ambient atmospheric pressure (i.e., ~100 kPa). In an embodiment, ZrO2 may be tetragonal ZrO2. In an embodiment, the concentration of ZrO2 in the precursor glass or glass-ceramic composition may be greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of impurities (0.05 mol% or greater)) to less than or equal to 7 mol% ZrO2, greater than or equal to 0 mol% to less than or equal to 7 mol%, greater than or equal to 0 mol% to less than or equal to 6 mol%, greater than or equal to 0 mol% to less than or equal to 5 mol%, greater than or equal to 0 mol% to less than or equal to 4 mol%, greater than or equal to 0 mol% to less than or equal to 3 mol%, greater than or equal to 0 mol% to less than or equal to 0 mol% % to less than or equal to 2 mol%, greater than or equal to 0 mol% to less than or equal to 1 mol%, greater than or equal to 1 mol% to less than or equal to 7 mol%, greater than or equal to 1 mol% to less than or equal to 6 mol%, greater than or equal to 1 mol% to less than or equal to 5 mol%, greater than or equal to 1 mol% to less than or equal to 4 mol%, greater than or equal to 1 mol% to less than or equal to 3 mol%, greater than or equal to 1 mol% to less than or equal to 2 mol%, greater than 1.5 mol% to less than or equal to 7 mol%, greater than 1.5 mol% to less than or equal to 6 mol%, greater than 1.5 mol% to less than or equal to 6 mol%, greater than 1.5 mol% to less than or equal to 1 % to less than or equal to 5 mol%, greater than 1.5 mol% to less than or equal to 4 mol%, greater than 1.5 mol% to less than or equal to 3 mol%, greater than 1.5 mol% to less than or equal to 2 mol%, greater than or equal to 2 mol% to less than or equal to 7 mol%, greater than or equal to 2 mol% to less than or equal to 6 mol%, greater than or equal to 2 mol% to less than or equal to 5 mol%, greater than or equal to 2 mol% to less than or equal to 4 mol%, greater than or equal to 2 mol% to less than or equal to 3 mol%, greater than or equal to 3 mol% to less than or equal to 7 mol%, greater than or equal to 3 % to less than or equal to 6 mol%, greater than or equal to 3 mol% to less than or equal to 5 mol%, greater than or equal to 3 mol% to less than or equal to 4 mol%, greater than or equal to 4 mol% to less than or equal to 7 mol%, greater than or equal to 4 mol% to less than or equal to 6 mol%, greater than or equal to 4 mol% to less than or equal to 5 mol%, greater than or equal to 5 mol% to less than or equal to 7 mol%, greater than or equal to 5 mol% to less than or equal to 6 mol%, greater than or equal to 6 mol% to less than or equal to 7 mol%, or any and all subranges formed by any of these endpoints. In an embodiment, the concentration of ZrO2 in the precursor glass or glass-ceramic composition can be greater than 1.5 mol%, greater than or equal to 2 mol%, 3 mol% or 4 mol%. In an embodiment, the concentration of ZrO2 can be less than or equal to 7 mol%, 6 mol% or 5 mol%.In embodiments, the precursor glass or glass-ceramic composition may be substantially free of ZrO2.

[0153] In an embodiment, the precursor glass or glass-ceramic composition may include HfO2. Without wishing to be bound by theory, it is believed that HfO2 acts as a nucleating agent that promotes the formation of a crystalline phase during thermal treatment. In an embodiment, in addition to ZrO2, HfO2 may be used as a nucleating agent, or HfO2 may be used as a substitute for ZrO2. In addition, HfO2 may help lower the liquidus of the precursor glass. In an embodiment, the concentration of HfO2 in the precursor glass or glass-ceramic composition may be greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of impurities (0.05 mol% or greater)) to less than or equal to 12 mol%.In embodiments, the concentration of HfO2 in the precursor glass or glass-ceramic composition may be greater than or equal to 0 mol% to less than or equal to 12 mol%, greater than or equal to 0 mol% to less than or equal to 10 mol%, greater than or equal to 0 mol% to less than or equal to 7 mol%, greater than or equal to 0 mol% to less than or equal to 6 mol%, greater than or equal to 0 mol% to less than or equal to 5 mol%, greater than or equal to 0 mol% to less than or equal to 4 mol%, greater than or equal to 0 mol% to less than or equal to 3 mol%, greater than or equal to 0 mol% to less than or equal to 2 mol%, greater than or equal to 0 mol% to less than or equal to 1 mol%, greater than or equal to 1 mol% to less than or equal to, etc. % to 12 mol%, 1 mol% or more and 10 mol%, 1 mol% or more and 7 mol% or more, 1 mol% or more and 6 mol%, 1 mol% or more and 5 mol%, 1 mol% or more and 4 mol%, 1 mol% or more and 3 mol%, 1 mol% or more and 2 mol%, 2 mol% or more and 12 mol%, 2 mol% or more and 10 mol%, 2 mol% or more and 7 mol%, 2 mol% or more and 6 mol% or more mol %, greater than or equal to 2 mol % to less than or equal to 5 mol %, greater than or equal to 2 mol % to less than or equal to 4 mol %, greater than or equal to 2 mol % to less than or equal to 3 mol %, greater than or equal to 3 mol % to less than or equal to 12 mol %, greater than or equal to 3 mol % to less than or equal to 10 mol %, greater than or equal to 3 mol % to less than or equal to 7 mol %, greater than or equal to 3 mol % to less than or equal to 6 mol %, greater than or equal to 3 mol % to less than or equal to 5 mol %, greater than or equal to 3 mol % to less than or equal to 4 mol %, greater than or equal to 4 mol % to less than or equal to 12 mol %, greater than or equal to 4 mol % to less than or equal to 10 mol %. %, greater than or equal to 4 mol % to less than or equal to 7 mol %, greater than or equal to 4 mol % to less than or equal to 6 mol %, greater than or equal to 4 mol % to less than or equal to 5 mol %, greater than or equal to 5 mol % to less than or equal to 12 mol %, greater than or equal to 5 mol % to less than or equal to 10 mol %, greater than or equal to 5 mol % to less than or equal to 7 mol %, greater than or equal to 5 mol % to less than or equal to 6 mol %, greater than or equal to 6 mol % to less than or equal to 12 mol %, greater than or equal to 6 mol % to less than or equal to 10 mol %, greater than or equal to 6 mol % to less than or equal to 7 mol %, or any and all subranges formed by any of these endpoints. In embodiments, the concentration of HfO in the precursor glass or glass-ceramic composition may be greater than or equal to 1 mol %, 2 mol %, or 3 mol %.In embodiments, the concentration of HfO2 may be less than or equal to 12 mol%, 10 mol%, 7 mol%, 6 mol%, or 5 mol%. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of HfO2.

[0154] In an embodiment, the precursor glass or glass-ceramic composition may include TiO2. Without wishing to be bound by theory, it is believed that TiO2 acts as a nucleating agent that promotes the formation of a crystalline phase during thermal treatment. Increasing the concentration of TiO2 may also impart color to the precursor glass and the resulting glass-ceramic.In embodiments, the concentration of TiO2 in the precursor glass or glass-ceramic composition can be greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of the impurity (0.05 mol% or greater)) to less than or equal to 7 mol%, greater than or equal to 0 mol% to less than or equal to 6 mol%, greater than or equal to 0 mol% to less than or equal to 5 mol%, greater than or equal to 0 mol% to less than or equal to 4 mol%, greater than or equal to 0 mol% to less than or equal to 3 mol%, greater than or equal to 0 mol% to less than or equal to 2 mol%, greater than or equal to 0 mol% to less than or equal to 1 mol%, greater than or equal to 0.3 mol% to less than or equal to 7 mol%, greater than or equal to 0.3 mol% to less than or equal to 6 mol%. mol %, greater than or equal to 0.3 mol % to less than or equal to 5 mol %, greater than or equal to 0.3 mol % to less than or equal to 4 mol %, greater than or equal to 0.3 mol % to less than or equal to 3 mol %, greater than or equal to 0.3 mol % to less than or equal to 2 mol %, greater than or equal to 0.3 mol % to less than or equal to 1 mol %, greater than or equal to 0.5 mol % to less than or equal to 7 mol %, greater than or equal to 0.5 mol % to less than or equal to 6 mol %, greater than or equal to 0.5 mol % to less than or equal to 5 mol %, greater than or equal to 0.5 mol % to less than or equal to 4 mol %, greater than or equal to 0.5 mol % to less than or equal to 3 mol %, greater than or equal to 0.5 mol % to less than or equal to % to less than or equal to 2 mol%, greater than or equal to 0.5 mol% and less than or equal to 1 mol%, greater than or equal to 1 mol% and less than or equal to 7 mol%, greater than or equal to 1 mol% and less than or equal to 6 mol%, greater than or equal to 1 mol% and less than or equal to 5 mol%, greater than or equal to 1 mol% and less than or equal to 4 mol%, greater than or equal to 1 mol% and less than or equal to 3 mol%, greater than or equal to 1 mol% and less than or equal to 2 mol%, greater than or equal to 2 mol% and less than or equal to 7 mol%, greater than or equal to 2 mol% and less than or equal to 6 mol%, greater than or equal to 2 mol% and less than or equal to 5 mol%, greater than or equal to 2 mol% and less than or equal to 4 mol%, greater than or equal to 1 mol% and less than or equal to 3 mol%. % to less than or equal to 7 mol%, greater than or equal to 3 mol% to less than or equal to 6 mol%, greater than or equal to 3 mol% to less than or equal to 5 mol%, greater than or equal to 3 mol% to less than or equal to 4 mol%, greater than or equal to 4 mol% to less than or equal to 7 mol%, greater than or equal to 4 mol% to less than or equal to 6 mol%, greater than or equal to 4 mol% to less than or equal to 5 mol%, greater than or equal to 5 mol% to less than or equal to 7 mol%, greater than or equal to 5 mol% to less than or equal to 6 mol%, greater than or equal to 6 mol% to less than or equal to 7 mol%, or any and all subranges formed by any of these endpoints. In embodiments, the concentration of TiO in the precursor glass or glass-ceramic composition may be greater than or equal to 0 mol%, 1 mol%, or 2 mol%.In embodiments, the concentration of TiO2 may be less than or equal to 7 mol%, 6 mol%, or 5 mol%. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of TiO2.

[0155] In embodiments, ZrO2 (mol%) + TiO2 (mol%) in the precursor glass or glass-ceramic composition described herein may be greater than or equal to 2.0 mol%, greater than or equal to 3.0 mol%, or even greater than or equal to 4.0 mol%. In embodiments, ZrO2 (mol%) / (ZrO2 (mol%) + TiO2 (mol%)) in the precursor glass or glass-ceramic composition described herein may be greater than or equal to 0.3. Without intending to be bound by theory, when ZrO2 (mol%) / (ZrO2 (mol%) + TiO2 (mol%)) in the precursor glass or glass-ceramic composition is less than 0.3, the main crystalline phase in the glass-ceramic may be a forsterite crystalline phase rather than a crystalline phase having a jeffbenite crystalline structure, which may be undesirable.

[0156] In an embodiment, the precursor glass or glass-ceramic composition may include SnO2. SnO2 is mainly used as a clarifier in the precursor glass composition. However, the addition of SnO2 can also help nucleating agents (such as TiO2 and ZrO2) to nucleate the crystalline phase during heat treatment. In an embodiment, the concentration of SnO2 in the precursor glass or glass-ceramic composition may be greater than or equal to 0 mol% to less than or equal to 0.2 mol%, greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of impurities (0.05 mol% or more)) to less than or equal to 0.18 mol%, greater than or equal to 0 mol% to less than or equal to 0.16 mol%, greater than or equal to 0 mol% to less than or equal to 0.14 mol%, greater than or equal to mol% to less than or equal to 0.12 mol%, greater than or equal to 0 mol% to less than or equal to 0.11 mol% %, greater than or equal to 0 mol% to less than or equal to 0.1 mol%, greater than or equal to 0.08 mol% to less than or equal to 0.2 mol%, greater than or equal to 0.09 mol% to less than or equal to 0.2 mol%, greater than or equal to 0.1 mol% to less than or equal to 0.2 mol%, greater than or equal to 0.12 mol% to less than or equal to 0.2 mol%, greater than or equal to 0.13 mol% to less than or equal to 0.2 mol%, greater than or equal to 0.14 mol% to less than or equal to 0.2 mol%, or any and all subranges formed by any of these endpoints. In an embodiment, the concentration of SnO2 in the precursor glass or glass-ceramic composition may be greater than or equal to 0 mol%, 0.08 mol% or 0.09 mol%. In an embodiment, the concentration of SnO2 may be less than or equal to 0.2 mol%, 0.18 mol% or 0.16 mol%. In an embodiment, the precursor glass or glass-ceramic composition may be substantially free of SnO2.

[0157] In an embodiment, the precursor glass or glass-ceramic composition may include BaO. BaO can increase the refractive index of the residual glass of the glass-ceramic to better match the refractive index of the crystalline phase having the jeffbenite crystal structure in the glass-ceramic. In an embodiment, the concentration of BaO in the precursor glass or glass-ceramic composition may be greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of impurities (0.05 mol% or greater)) to less than or equal to 8 mol%, greater than or equal to 0 mol% to less than or equal to 7 mol%, greater than or equal to 0 mol% to less than or equal to 6 mol%, greater than or equal to 0 mol% to less than or equal to 5 mol%, greater than or equal to 0 mol% to less than or equal to 4 mol%, greater than or equal to 0 mol% to less than or equal to 3 mol%, greater than or equal to 0 mol% to less than or equal to 2 ... 0 mol% to less than or equal to 1 mol%, 1 mol% to less than or equal to 8 mol%, 1 mol% to less than or equal to 7 mol%, 1 mol% to less than or equal to 6 mol%, 1 mol% to less than or equal to 5 mol%, 1 mol% to less than or equal to 4 mol%, 1 mol% to less than or equal to 3 mol%, 1 mol% to less than or equal to 2 mol%, 2 mol% to less than or equal to 8 mol%, 2 mol% to less than or equal to 7 mol%, greater than or equal to 1 mol% % to less than or equal to 6 mol%, greater than or equal to 2 mol% to less than or equal to 5 mol%, greater than or equal to 2 mol% to less than or equal to 4 mol%, greater than or equal to 2 mol% to less than or equal to 3 mol%, greater than or equal to 3 mol% to less than or equal to 8 mol%, greater than or equal to 3 mol% to less than or equal to 7 mol%, greater than or equal to 3 mol% to less than or equal to 6 mol%, greater than or equal to 3 mol% to less than or equal to 5 mol%, greater than or equal to 3 mol% to less than or equal to 4 mol%, greater than or equal to 4 mol% to less than or equal to 8 mol%, % to less than or equal to 8 mol%, greater than or equal to 5 mol% to less than or equal to 7 mol%, greater than or equal to 5 mol% to less than or equal to 8 mol%, greater than or equal to 5 mol% to less than or equal to 7 mol%, greater than or equal to 5 mol% to less than or equal to 6 mol%, greater than or equal to 6 mol% to less than or equal to 8 mol%, greater than or equal to 6 mol% to less than or equal to 7 mol%, greater than or equal to 7 mol% to less than or equal to 8 mol%, or any and all subranges formed by any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition can be substantially free of BaO.

[0158] In embodiments, the precursor glass or glass-ceramic composition may include ZnO. The interpolation of ZnO may increase the refractive index of residual glass in the glass-ceramic to better match the refractive index of the crystalline phases with jeffbenite crystallographic structure in the glass-ceramic. Although not wishing to be bound by theory, it is believed that the interpolation of ZnO may result in replacing at least a portion of Mg in the jeffbenite crystallographic structure with Zn. ZnO may also help stabilize the precursor glass, prevent devitrification and reduce liquidus viscosity. However, too much ZnO may disturb the formation of the crystalline phases with jeffbenite crystallographic structure in the ceramicization process. In embodiments, the concentration of ZnO in the precursor glass or glass-ceramic composition can be greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of the impurity (0.05 mol% or greater)) to less than or equal to 15 mol%, greater than or equal to 0 mol% to less than or equal to 14 mol%, greater than or equal to 0 mol% to less than or equal to 13 mol%, greater than or equal to 0 mol% to less than or equal to 12 mol%, greater than or equal to 0 mol% to less than or equal to 11 mol%, greater than or equal to 0 mol% to less than or equal to 10 ...5 mol%, greater than or equal to 0 mol% to less than or equal to 14 mol%, greater than or equal to 0 mol% to less than or equal to 13 mol%, greater than or equal to 0 mol% to less than or equal to 12 mol%, greater than or equal to 0 mol% to less than or equal to 11 mol%, greater than or equal to 0 mol% to less than or equal to 10 mol%, greater than or equal to 0 mol% to less than or equal to 15 mol%. % to less than or equal to 8 mol %, greater than or equal to 0 mol % to less than or equal to 7 mol %, greater than or equal to 0 mol % to less than or equal to 6 mol %, greater than or equal to 0 mol % to less than or equal to 5 mol %, greater than or equal to 0 mol % to less than or equal to 4 mol %, greater than or equal to 0 mol % to less than or equal to 3 mol %, greater than or equal to 0 mol % to less than or equal to 2 mol %, greater than or equal to 0 mol % to less than or equal to 1 mol %, greater than or equal to 1 mol % to less than or equal to 15 ... 1 mol% to less than or equal to 14 mol%, 1 mol% to less than or equal to 13 mol%, 1 mol% to less than or equal to 12 mol%, 1 mol% to less than or equal to 11 mol%, 1 mol% to less than or equal to 10 mol%, 1 mol% to less than or equal to 9 mol%, 1 mol% to less than or equal to 8 mol%, 1 mol% to less than or equal to 7 mol%, 1 mol% to less than or equal to 6 mol%, 1 mol% to less than or equal to 10 mol%, 1 mol% to less than or equal to 9 mol%, 1 mol% to less than or equal to 8 mol%, 1 mol% to less than or equal to 7 mol%, 1 mol% to less than or equal to 6 mol%, 1 mol% to less than or equal to 10 mol%, % to less than or equal to 15 mol %, greater than or equal to 2 mol % to less than or equal to 14 mol %, greater than or equal to 2 mol % to less than or equal to 13 mol %, greater than or equal to 2 mol % to less than or equal to 12 mol %, greater than or equal to 2 mol % to less than or equal to 11 mol %, greater than or equal to 2 mol % to less than or equal to 10 mol %,% to less than or equal to 15 mol %, 3 mol % to less than or equal to 14 mol %, 3 mol % to less than or equal to 13 mol %, 3 mol % to less than or equal to 12 mol %, 3 mol % to less than or equal to 11 mol %, 3 mol % to less than or equal to 16 mol %, 3 mol % to less than or equal to 17 mol %, 3 mol % to less than or equal to 18 mol %, 3 mol % to less than or equal to 19 mol %, 3 mol % to less than or equal to 11 mol %, 3 mol % to less than or equal to 12 mol %, 3 mol % to less than or equal to 13 mol %, 3 mol % to less than or equal to 16 mol %, 3 mol % to less than or equal to 18 mol %, 3 mol % to less than or equal to 19 mol %, 3 mol % to less than or equal to 1 ...9 mol %, 3 mol % to less than or equal to 11 % to less than or equal to 10 mol%, 3 mol% to less than or equal to 9 mol%, 3 mol% to less than or equal to 8 mol%, 3 mol% to less than or equal to 7 mol%, 3 mol% to less than or equal to 6 mol%, 3 mol% to less than or equal to 5 mol%, 3 mol% to less than or equal to 4 mol%, 4 mol% to less than or equal to 15 mol%, 4 mol% to less than or equal to 14 mol%, 4 mol% to less than or equal to 13 mol%, 4 mol% to less than or equal to 12 mol%, 4 mol% to less than or equal to 11 mol%, 4 mol% to less than or equal to 16 mol%, 4 mol% to less than or equal to 17 mol%, 4 mol% to less than or equal to 18 mol%, 4 mol% to less than or equal to 19 mol%, 4 mol% to less than or equal to 20 mol%, 4 mol% to less than or equal to 21 mol%, 4 mol% to less than or equal to 23 mol%, 4 mol% to less than or equal to 24 mol%, 4 mol% to less than or equal to 25 mol%, 4 mol% to less than or equal to 26 mol%, 4 mol% to less than or equal to 27 mol%, 4 mol% to less than or equal to 28 mol%, 4 mol% to less than or equal to 29 mol%, 4 mol% to less than or equal to 30 ... % to less than or equal to 10 mol %, greater than or equal to 4 mol % to less than or equal to 9 mol %, greater than or equal to 4 mol % to less than or equal to 8 mol %, greater than or equal to 4 mol % to less than or equal to 7 mol %, greater than or equal to 4 mol % to less than or equal to 6 mol %, greater than or equal to 4 mol % to less than or equal to 5 mol %, greater than or equal to 5 mol % to less than or equal to 15 mol %, greater than or equal to 5 mol % to less than or equal to 14 mol %, greater than or equal to 5 mol % to less than or equal to 13 mol %, greater than or equal to 5 mol % to less than or equal to 12 mol %, greater than or equal to 5 mol % to less than or equal to 11 mol %, greater than or equal to 5 mol % to less than or equal to 10 mol %, % to less than or equal to 9 mol%, 5 mol% to less than or equal to 8 mol%, 5 mol% to less than or equal to 7 mol%, 5 mol% to less than or equal to 6 mol%, 6 mol% to less than or equal to 15 mol%, 6 mol% to less than or equal to 14 mol%, 6 mol% to less than or equal to 13 mol%, 6 mol% to less than or equal to 12 mol%, 6 mol% to less than or equal to 11 mol%, 6 mol% to less than or equal to 10 mol%, 6 mol% to less than or equal to 9 mol%, 6 mol% to less than or equal to 8 mol%,% to less than or equal to 7 mol%, greater than or equal to 7 mol% to less than or equal to 15 mol%, greater than or equal to 7 mol% to less than or equal to 14 mol%, greater than or equal to 7 mol% to less than or equal to 13 mol%, greater than or equal to 7 mol% to less than or equal to 8 mol%, or any and all subranges formed by any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition can be substantially free of ZnO.

[0159] In an embodiment, the precursor glass or glass-ceramic composition may include FeO. Although not wishing to be bound by theory, it is believed that the addition of FeO may result in the replacement of at least a portion of Mg in the jeffbenite crystalline structure with Fe. FeO may also impart color to the precursor glass and glass-ceramic. In an embodiment, the concentration of FeO in the precursor glass or glass-ceramic composition may be greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of impurities (0.05 mol% or greater)) to less than or equal to 9 mol%, greater than or equal to 0 mol% to less than or equal to 8 mol%, greater than or equal to 0 mol% to less than or equal to 7 mol%, greater than or equal to 0 mol% to less than or equal to 6 mol%, greater than or equal to 0 mol% to less than or equal to 5 mol%, greater than or equal to 0 mol% to less than or equal to 4 mol%, greater than or equal to 0 mol% to less than or equal to 3 mol%, greater than or equal to 0 mol% to less than 1 ... In some embodiments, the precursor glass or glass-ceramic composition may be substantially free of FeO, or 2 mol %, 0 mol % to less than 1 mol %, 1 mol % to less than 9 mol %, 2 mol % to less than 9 mol %, 3 mol % to less than 9 mol %, 4 mol % to less than 9 mol %, 5 mol % to less than 9 mol %, 6 mol % to less than 9 mol %, 7 mol % to less than 9 mol %, 8 mol % to less than 9 mol %, or any and all subranges formed by any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of FeO.

[0160] In an embodiment, the precursor glass or glass-ceramic composition may include CaO, SrO, or a combination thereof. The addition of CaO, SrO, and a combination thereof may increase the amount of residual glass in the glass-ceramic. Without wishing to be bound by theory, the inclusion of SrO in the glass-ceramic may increase the refractive index of the residual glass to better match the refractive index of the crystalline phase. In embodiments, the concentration of CaO, SrO, or a combination thereof may be from greater than or equal to 0 mol% (e.g., a positive amount, such as greater than the amount of the impurity (0.05 mol% or greater)) to less than or equal to 2.0 mol%, from greater than or equal to 0.2 mol% to less than or equal to 2.0 mol%, from greater than or equal to 0.4 mol% to less than or equal to 2.0 mol%, from greater than or equal to 0.6 mol% to less than or equal to 2.0 mol%, from greater than or equal to 0.8 mol% to less than or equal to 2.0 mol%, from greater than or equal to 1.0 mol% to less than or equal to 2.0 mol%, from greater than or equal to 1.2 mol% to less than or equal to 2.0 mol%, from greater than or equal to 1.4 mol% to less than or equal to 2.0 mol%, from greater than or equal to 0 mol% to less than or equal to 1.7 mol%, from greater than or equal to 0.2 mol% to less than or equal to 1.7 mol%, from greater than or equal to 0.4 mol% to less than or equal to 2.0 mol%. % to less than or equal to 1.7 mol%, greater than or equal to 0.6 mol% to less than or equal to 1.7 mol%, greater than or equal to 0.8 mol% to less than or equal to 1.7 mol%, greater than or equal to 1.0 mol% to less than or equal to 1.7 mol%, greater than or equal to 1.2 mol% to less than or equal to 1.7 mol%, greater than or equal to 1.4 mol% to less than or equal to 1.7 mol%, greater than or equal to 0 mol% to less than or equal to 1.4 mol%, greater than or equal to 0 mol% to less than or equal to 1.2 mol%, greater than or equal to 0 mol% to less than or equal to 1.0 mol%, greater than or equal to 0 mol% to less than or equal to 0.8 mol%, greater than or equal to 0 mol% to less than or equal to 0.6 mol%, greater than or equal to 0 mol% to less than or equal to 0.4 mol%, greater than or equal to 0 mol% to less than or equal to 0.2 mol%, or any and all subranges formed by any of these endpoints.In embodiments, the concentration of CaO may be from greater than or equal to 0 mol% to less than or equal to 10 mol%, from greater than or equal to 1 mol% to less than or equal to 10 mol%, from greater than or equal to 2 mol% to less than or equal to 10 mol%, from greater than or equal to 3 mol% to less than or equal to 10 mol%, from greater than or equal to 4 mol% to less than or equal to 10 mol%, from greater than or equal to 5 mol% to less than or equal to 10 mol%, from greater than or equal to 6 mol% to less than or equal to 10 mol%, from greater than or equal to 7 mol% to less than or equal to 10 mol%, from greater than or equal to 8 mol% to less than or equal to 10 mol%, from greater than or equal to 9 mol% to less than or equal to 10 mol%. In some embodiments, the precursor glass or glass-ceramic composition may be substantially free of CaO. In some embodiments, the precursor glass or glass-ceramic composition may be substantially free of SrO. In some embodiments, the precursor glass or glass-ceramic composition may be substantially free of CaO. In some embodiments, the precursor glass or glass-ceramic composition may be substantially free of SrO. In some embodiments, the precursor glass or glass-ceramic composition may be substantially free of both CaO and SrO.

[0161] In an embodiment, precursor glass or glass-ceramic composition can include Cs o.Do not wish to be bound by theory, it is believed that Cs the additive of o will be retained in residual glass after ceramization and play the refractive index improving residual glass and do not cause the effect of crystallization.In an embodiment, Cs in precursor glass or glass-ceramic composition the concentration of o can be greater than or equal to 0 % by mole (as positive amount, as greater than the amount (0.05 % by mole or greater) of impurity) to be less than or equal to 5 % by mole, greater than or equal to 0 % by mole to be less than or equal to 4 % by mole, greater than or equal to 0 % by mole to be less than or equal to 3 % by mole, greater than or equal to 0 % by mole to be less than or equal to 2 % by mole, greater than or equal to 0 % by mole to be less than or equal to 1 % by mole, greater than or equal to 1 % by mole to be less than or equal to 5 % by mole, greater than or equal to 2 % by mole to be less than or equal to 5 % by mole, greater than or equal to 3 % by mole to be less than or equal to 5 % by mole, greater than or equal to 4 % by mole to be less than or equal to 5 % by mole, or any and all sub-ranges formed by any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of Cs2O.

[0162] In an embodiment, the precursor glass or glass-ceramic composition may include Li2O. For example, but not limited to, the precursor glass or glass-ceramic composition may include less than or equal to 3 mol%, less than or equal to 2.5 mol%, less than or equal to 2 mol%, less than or equal to 1.5 mol%, less than or equal to 1 mol%, less than or equal to 0.7 mol%, less than or equal to 0.5 mol%, less than or equal to 0.3 mol%, or less than or equal to 0.1 mol% Li2O, but in a positive amount, such as greater than the amount of impurities (0.05 mol% or greater), or at most only the amount of impurities (i.e., less than 0.05 mol%). In an embodiment, the precursor glass or glass-ceramic composition may be substantially free of Li2O. Without intending to be bound by theory, when the precursor glass includes less than or equal to 3 mol% Li2O, the formation of beta quartz during heat treatment can be reduced.

[0163] In an embodiment, the precursor glass or glass-ceramic composition may include Y2O3. Without wishing to be bound by theory, Y2O3 may stabilize ZrO2 included in the precursor glass or glass-ceramic composition. In an embodiment, the concentration of Y2O3 may be greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of the impurity (0.05 mol% or greater)) to less than or equal to 2.0 mol%, greater than or equal to 0.2 mol% to less than or equal to 2.0 mol%, greater than or equal to 0.4 mol% to less than or equal to 2.0 mol%, greater than or equal to 0.6 mol% to less than or equal to 2.0 mol%, greater than or equal to 0.8 mol% to less than or equal to 2.0 mol%, greater than or equal to 1.0 mol% to less than or equal to 2.0 mol%, greater than or equal to 1.2 mol% to less than or equal to 2.0 mol%, greater than or equal to 1.4 mol% to less than or equal to 2.0 mol%, greater than or equal to 1.6 mol% to less than or equal to %, greater than or equal to 0 mol% to less than or equal to 0.6 mol%, greater than or equal to 0 mol% to less than or equal to 0.4 mol%, greater than or equal to 0 mol% to less than or equal to 0.2 mol%, or any and all subranges formed by any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition can be substantially free of Y2O3.

[0164] In embodiments, the precursor glass or glass-ceramic composition may be substantially free of P2O5. In some embodiments, the precursor glass or glass-ceramic composition may be free of P2O5. Without wishing to be bound by theory, the inclusion of P2O5 in the precursor glass or glass-ceramic composition may result in the formation of magnesium phosphate and reduce the formation of a crystalline phase having a jeffbenite crystal structure.

[0165] In an embodiment, the precursor glass or glass-ceramic composition may include P2O5. Although not wishing to be bound by theory, it is believed that the addition of P2O5 can improve the diffusion rate of the glass-ceramic composition during the ion exchange process. In an embodiment, the concentration of P2O5 in the precursor glass or glass-ceramic composition can be greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of impurities (0.05 mol% or greater)) to less than or equal to 4 mol%, greater than or equal to 0 mol% to less than or equal to 3.5 mol%, greater than or equal to 0 mol% to less than or equal to 3 mol%, greater than or equal to 0 mol% to less than or equal to 2.5 mol%, greater than or equal to 0 mol% to less than or equal to 2 mol%, greater than or equal to 0 mol% to less than or equal to 1.5 mol%, greater than or equal to 0 mol% to less than or equal to the same. %, PO 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5 5

[0166] In embodiments, the precursor glass or glass-ceramic composition may include MnO2. While not wishing to be bound by theory, it is believed that the addition of MnO2 may result in the replacement of at least a portion of the Mg in the jeffbenite crystalline structure with Mn. MnO2 may also impart color to the precursor glass and glass-ceramic. For example, but not limited to, the addition of MnO2 may impart a black color to the glass-ceramic. In embodiments, the concentration of MnO2 may be from 0 mol% or more (e.g., a positive amount, such as greater than the amount of the impurity (0.05 mol% or more)) to 10 mol% or less, from 0 mol% or more to 9 mol% or less, from 0 mol% or more to 8 mol% or less, from 0 mol% or more to 7 mol% or more, from 0 mol% or more to 6 mol% or less, from 0 mol% or more to 5 mol% or less, from 0 mol% or more to 4 mol% or more, from 0 mol% or more to 3 mol% or less, from 0 mol% or more to 2 mol% or more, from 0 mol% or more to 1.0 mol% or less, from 0.1 mol% or more to 1 mol% or less, from 0.2 mol% or more to 1.0 mol% or less, from 0.4 mol% or more to 1.0 mol% or more, from 0.6 mol% or more to less or less, %, greater than or equal to 1.0 mol %, greater than or equal to 0.8 mol % to less than or equal to 1.0 mol %, greater than or equal to 0.8 mol %, greater than or equal to 0.6 mol %, greater than or equal to 0.4 mol %, greater than or equal to 0.2 mol %, greater than or equal to 1 mol % to less than or equal to 10 mol %, greater than or equal to 2 mol % to less than or equal to 10 mol %, greater than or equal to 3 mol % to less than or equal to 10 mol %, greater than or equal to 4 mol % to less than or equal to 10 mol %, greater than or equal to 5 mol % to less than or equal to 10 mol %, greater than or equal to 6 mol % to less than or equal to 10 mol %, greater than or equal to 7 mol % to less than or equal to 10 mol %, greater than or equal to 8 mol % to less than or equal to 10 mol %, greater than or equal to 9 mol % to less than or equal to 10 mol %, or any and all subranges formed by any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of MnO2.

[0167] In an embodiment, the precursor glass or glass-ceramic composition may include La 2 O 3. While not wishing to be bound by theory, it is believed that the addition of La 2 O 3 may increase the refractive index of the residual glass of the glass-ceramic composition, which may improve the transparency of the glass-ceramic composition. In embodiments, the concentration of La2O3 in the precursor glass or glass-ceramic composition can be greater than or equal to 0 mol% to less than or equal to 7 mol%, greater than or equal to 0 mol% (such as a positive amount, such as greater than the amount of impurities (0.05 mol% or greater)) to less than or equal to 6 mol%, greater than or equal to 0 mol% to less than or equal to 5 mol%, greater than or equal to 0 mol% to less than or equal to 4 mol%, greater than or equal to 0 mol% to less than or equal to 3 mol%, greater than or equal to 0 mol% to less than or equal to 2 mol%, greater than or equal to 0 mol% to less than or equal to 1 mol%, greater than or equal to 1 mol% to less than or equal to 7 mol%, greater than or equal to 1 mol% to less than or equal to 6 mol%, greater than or equal to 1 mol% to less than or equal to 5 mol%, greater than or equal to 1 mol% to less than or equal to 4 mol%, greater than or equal to 1 mol% to less than or equal to 3 mol%, greater than or equal to 1 ...1 mol% In some embodiments, the precursor glass or glass-ceramic composition may be substantially free of La2O3.

[0168] The articles formed from the precursor glass or glass-ceramic described herein can have any suitable thickness, depending on the specific application of the glass-ceramic. The glass-ceramic sheet embodiment can have a thickness T of greater than or equal to 0.2 mm to less than or equal to 10 mm. In an embodiment, the glass-ceramic sheet embodiment can have a thickness T of 6 mm or less, 5 mm or less, 4 mm or less, 3 mm or less, 2 mm or less, 1.0 mm or less, 750 μm or less, 500 μm or less, or 250 μm or less. In an embodiment, the glass-ceramic sheet embodiment can have a thickness T of greater than or equal to 200 μm to less than or equal to 5 mm, greater than or equal to 500 μm to less than or equal to 5 mm, greater than or equal to 200 μm to less than or equal to 4 mm, greater than or equal to 200 μm to less than or equal to 2 mm, greater than or equal to 400 μm to less than or equal to 5 mm, or greater than or equal to 400 μm to less than or equal to 2 mm. It will be appreciated that the thickness of the precursor glass or glass-ceramic article can be within the sub-ranges formed by any and all of the aforementioned endpoints. Alternatively, the glass sheet can be thicker than 10 mm, such as for use in certain armored windows or other applications. Alternatively, for example, containers and tubes comprising the glass or glass-ceramics disclosed herein can have such thicknesses as wall thicknesses, and rods and balls and other articles comprising the glass or glass-ceramics disclosed herein can have similar thicknesses.

[0169] In embodiments, the precursor glass or glass-ceramic composition described herein is ion exchangeable to facilitate strengthening the precursor glass or glass-ceramic. In a typical ion exchange process, smaller metal ions in the glass-ceramic are replaced or "exchanged" by larger metal ions of the same valence in a layer near the outer surface of the glass-ceramic. Replacing smaller ions with larger ions will produce compressive stresses in the layer of the glass-ceramic. In embodiments, the metal ions are monovalent metal ions (e.g., Li + 、Na + , K + The ion exchange is accomplished by immersing the glass-ceramic in a bath containing at least one molten salt of a larger metal ion to replace the smaller metal ion in the glass-ceramic. One or more ion exchange processes for strengthening the glass-ceramic may include, but are not limited to, immersion in a single bath or multiple baths of similar or different compositions with washing and / or annealing steps between immersions. In an embodiment, the glass-ceramic may be ion exchanged by exposure to a molten KNO3 salt, a molten NaNO3 salt, or a molten salt mixture containing KNO3 and NaNO3. If Na2O is present in the precursor glass or glass-ceramic, Na2O is ion exchanged with the precursor glass or glass-ceramic. + Exchange for K +The ion exchange can take place in a KNO3 salt bath or a salt bath containing a combination of KNO3 and NaNO3. If Li2O is present in the precursor glass or glass-ceramic, Li + Exchange for Na + The ion exchange may occur in a NaNO3 salt bath or a salt bath comprising a combination of NaNO3 and KNO3. In an embodiment, the glass-ceramic may be ion exchanged in a molten salt bath at a bath temperature of greater than or equal to 350°C to less than or equal to 500°C. For example, but not limited to, the glass-ceramic may be ion exchanged at a bath temperature of greater than or equal to 350°C to less than or equal to 530°C, greater than or equal to 375°C to less than or equal to 530°C, greater than or equal to 400°C to less than or equal to 530°C, greater than or equal to 425°C to less than or equal to 530°C, greater than or equal to 450°C to less than or equal to 530°C, greater than or equal to 475°C to less than or equal to 530°C, greater than or equal to 500°C to less than or equal to 530°C, greater than or equal to 350°C to less than or equal to 500°C, greater than or equal to 375°C to less than or equal to 500°C, greater than or equal to 4 In some embodiments, the ion exchange process may be performed at a bath temperature of 100°C to less than or equal to 500°C, 425°C to less than or equal to 500°C, 450°C to less than or equal to 500°C, 475°C to less than or equal to 500°C, 350°C to less than or equal to 475°C, 350°C to less than or equal to 450°C, 350°C to less than or equal to 425°C, 350°C to less than or equal to 400°C, 350°C to less than or equal to 375°C, or any and all subranges formed by any of these endpoints. The ion exchange time may be greater than or equal to 1 hour to less than or equal to 48 hours. In an embodiment, the ion exchange process may produce a surface compression layer in the glass precursor or glass-ceramic composition. The generation of such a surface compression layer is conducive to achieving better crack resistance and higher flexural strength compared to non-ion exchanged materials. The surface compression layer has a higher concentration of ions exchanged into the glass-ceramic article than the concentration of ions exchanged into the glass-ceramic article in the bulk of the glass-ceramic article (ie, the area excluding the surface compression).

[0170] In an embodiment, the precursor glass and / or glass-ceramic can be ion exchanged to achieve a compression depth of about 30 μm or greater, about 40 μm or greater, about 50 μm or greater, about 60 μm or greater, about 70 μm or greater, about 80 μm or greater, about 90 μm or greater, or about 100 μm or greater. In an embodiment, the compression depth can be greater than or equal to 3% of the thickness of the article formed by the precursor glass and / or glass-ceramic, greater than or equal to 5% of the thickness, greater than or equal to 10% of the thickness, greater than or equal to 15% of the thickness, greater than or equal to 20% of the thickness, or even greater than or equal to 22% of the thickness. Compared with non-ion exchanged materials, the generation of such a surface compression layer is conducive to achieving better crack resistance and higher flexural strength. The surface compression layer has a higher concentration of ions exchanged into the precursor glass and / or glass-ceramic article than the concentration of ions exchanged into the article in the body of the article (i.e., the area excluding the surface compression).

[0171] In an embodiment, the precursor glass and / or glass-ceramic is ion exchanged to achieve a central tension of greater than or equal to 10 MPa. In an embodiment, the central tension may be greater than or equal to 10 MPa and less than or equal to 200 MPa, greater than or equal to 20 MPa and less than or equal to 200 MPa, greater than or equal to 30 MPa and less than or equal to 200 MPa, greater than or equal to 40 MPa and less than or equal to 200 MPa, greater than or equal to 50 MPa and less than or equal to 200 MPa, greater than or equal to 60 MPa and less than or equal to 200 MPa, greater than or equal to 70 MPa and less than or equal to 200 MPa, greater than or equal to 80 MPa and less than or equal to 200 MPa, greater than or equal to 90 MPa and less than or equal to 200 MPa, greater than or equal to 100 MPa and less than or equal to 200 MPa, or greater than or equal to 200 MPa. MPa, greater than or equal to 110 MPa and less than or equal to 200 MPa, greater than or equal to 120 MPa and less than or equal to 200 MPa, greater than or equal to 130 MPa and less than or equal to 200 MPa, greater than or equal to 140 MPa and less than or equal to 200 MPa, greater than or equal to 150 MPa and less than or equal to 200 MPa, greater than or equal to 160 MPa and less than or equal to 200 MPa, greater than or equal to 170 MPa and less than or equal to 200 MPa, greater than or equal to 180 MPa and less than or equal to 200 MPa, greater than or equal to 190 MPa and less than or equal to 200 MPa, or any and all subranges formed by any of these endpoints.

[0172] In embodiments, the precursor glass or glass-ceramic may have a pressure of greater than or equal to 100 MPa to less than or equal to 1 GPa, greater than or equal to 100 MPa to less than or equal to 950 MPa, greater than or equal to 100 MPa to less than or equal to 900 MPa, greater than or equal to 100 MPa to less than or equal to 850 MPa, greater than or equal to 100 MPa to less than or equal to 800 MPa, greater than or equal to 100 MPa to less than or equal to 750 MPa, greater than or equal to 100 MPa to less than or equal to 700 MPa, greater than or equal to 100 MPa to less than or equal to 650 MPa, greater than or equal to 100 MPa to less than or equal to 600 MPa, greater than or equal to 100 MPa MPa to less than or equal to 550 MPa, greater than or equal to 100 MPa to less than or equal to 500 MPa, greater than or equal to 100 MPa to less than or equal to 450 MPa, greater than or equal to 100 MPa to less than or equal to 400 MPa, greater than or equal to 100 MPa to less than or equal to 350 MPa, greater than or equal to 100 MPa to less than or equal to 300 MPa, greater than or equal to 100 MPa to less than or equal to 250 MPa, greater than or equal to 100 MPa to less than or equal to 200 MPa, greater than or equal to 100 MPa to less than or equal to 150 MPa, 150 MPa to less than or equal to 500 MPa, greater than or equal to 150 MPa to less than or equal to 4 50 MPa, greater than or equal to 150 MPa and less than or equal to 400 MPa, greater than or equal to 150 MPa and less than or equal to 350 MPa, greater than or equal to 150 MPa and less than or equal to 300 MPa, greater than or equal to 150 MPa and less than or equal to 250 MPa, greater than or equal to 150 MPa and less than or equal to 200 MPa, 200 MPa and less than or equal to 500 MPa, greater than or equal to 200 MPa and less than or equal to 450 MPa, greater than or equal to 200 MPa and less than or equal to 400 MPa, greater than or equal to 200 MPa and less than or equal to 350 MPa, greater than or equal to 200 MPa and less than or equal to 300 MPa, greater than or equal to 200 MPa and less than or equal to 300 MPa, greater than or equal to 250 MPa 200 MPa to less than or equal to 250 MPa, 250 MPa to less than or equal to 500 MPa, greater than or equal to 250 MPa to less than or equal to 450 MPa, greater than or equal to 250 MPa to less than or equal to 400 MPa, greater than or equal to 250 MPa to less than or equal to 350 MPa, greater than or equal to 250 MPa to less than or equal to 300 MPa, 300 MPa to less than or equal to 500 MPa, greater than or equal to 300 MPa to less than or equal to 450 MPa, greater than or equal to 300 MPa to less than or equal to 400 MPa, greater than or equal to 300 MPa to less than or equal to 350 MPa, 350 MPa to less than or equal to 500 MPa,In some embodiments, the precursor glass or glass-ceramic may have a surface compressive stress in a range of greater than or equal to 350 MPa to less than or equal to 450 MPa, greater than or equal to 350 MPa to less than or equal to 400 MPa, 400 MPa to less than or equal to 500 MPa, greater than or equal to 400 MPa to less than or equal to 450 MPa, greater than or equal to 450 MPa to less than or equal to 500 MPa, or any and all subranges formed by any of these endpoints. In an embodiment, the precursor glass or glass-ceramic may have a surface compressive stress of about 100 MPa or greater, about 150 MPa or greater, about 200 MPa or greater, about 250 MPa or greater, about 300 MPa or greater, about 350 MPa or greater, about 400 MPa or greater, about 450 MPa or greater, or about 500 MPa or greater.

[0173] In an embodiment, the process of making glass-ceramics includes melting a batch of constituent components to form a precursor glass. The molten precursor glass can be poured into a mold. In an embodiment, the mold can include steel. The precursor glass can be annealed. A disk of the precursor glass can be sliced ​​and then heat treated to form a glass-ceramic.

[0174] Alternatively, the precursor glasses described herein can be made from molten precursor glasses and formed into sheets by processes including, but not limited to, slot drawing, float, rolling, and other sheet forming processes known in the art.

[0175] In an embodiment, the process of manufacturing glass-ceramic includes heat treating the precursor glass (also referred to herein as "ceramicization") at one or more preselected temperatures for one or more preselected times to induce glass homogenization and crystallization (i.e., nucleation and growth) of one or more crystalline phases (e.g., with one or more compositions, amounts, forms, sizes or size distributions, etc.). In the whole heat treatment process, the one or more preselected temperatures may be less than 1500K. It should be noted that temperature may refer to a temperature within a certain range, not necessarily a static single (singular) temperature. Similarly, it should be noted that crystal nucleation and / or growth may occur in continuous or multiple discrete heat treatments, which are added together to achieve desired crystal growth. Without wishing to be bound by theory, nucleating agents may serve as or form nucleation sites for the nucleation and growth of the grains of crystalline phases, including nucleation and growth of the grains of the crystalline phases with jeffbenite crystallographic structure. The nucleation sites are positioned and oriented within the precursor glass so that the grains of the resulting crystalline phase (including the grains of the crystalline phase having the jeffbenite crystal structure) are uniformly distributed throughout the resulting glass-ceramic and grow in a random orientation, thereby producing a glass-ceramic having isotropic material properties. In an embodiment, the heat treatment may include heating the precursor glass at a rate of 1-10°C / minute in a heat treatment furnace until the furnace reaches a first temperature. The first temperature of the furnace may be greater than or equal to 700°C to less than or equal to 950°C.In an embodiment, the first temperature of the furnace can be greater than or equal to 700°C and less than or equal to 950°C, greater than or equal to 710°C and less than or equal to 950°C, greater than or equal to 730°C and less than or equal to 950°C, greater than or equal to 750°C and less than or equal to 950°C, greater than or equal to 770°C and less than or equal to 950°C, greater than or equal to 790°C and less than or equal to 950°C, greater than or equal to 810°C and less than or equal to 950°C, greater than or equal to 830°C and less than or equal to 950°C, greater than or equal to 850°C and less than or equal to 950°C, greater than or equal to 870°C and less than or equal to 950°C, greater than or equal to 890°C and less than or equal to 950°C, greater than or equal to 910°C and less than or equal to 950°C, greater than or equal to 930°C and less than or equal to 950°C or equal to 950°C, 700°C or greater to 930°C or less, 700°C or greater to 910°C or less, 700°C or greater to 890°C or less, 700°C or greater to 870°C or less, 700°C or greater to 850°C or less, 700°C or greater to 830°C or less, 700°C or greater to 810°C or less, 700°C or greater to 790°C or less, 700°C or greater to 770°C or greater, 700°C or greater to 750°C or less, 700°C or greater to 730°C or less, 700°C or greater to 710°C or less, or any and all subranges formed by any of these endpoints. Unless otherwise specified, the temperature of the heat treatment or ion exchange treatment refers to the temperature of the environment to which the article is exposed (such as a furnace for heat treatment or a molten salt bath for ion exchange treatment). In an embodiment, the process of making a glass-ceramic includes maintaining the precursor glass at a first temperature for a first time in the range of 0.25 hours to 6 hours.For example, but not limited to, the precursor glass can be maintained at the first temperature for 0.25 hours to 6 hours or less, 0.5 hours to 6 hours or less, 0.75 hours to 6 hours or less, 1 hour to 6 hours or less, 1.25 hours to 6 hours or less, 1.5 hours to 6 hours or less, 1.75 hours to 6 hours or less, 2 hours to 6 hours or less, 2.25 hours to 6 hours or less, 2.5 hours to 6 hours or less, or 2.5 hours to 6 hours or less. 75 hours to less than or equal to 6 hours, 3 hours to less than or equal to 6 hours, 3.25 hours to less than or equal to 6 hours, 3.5 hours to less than or equal to 6 hours, 3.75 hours to less than or equal to 6 hours, 4 hours to less than or equal to 6 hours, 4.25 hours to less than or equal to 6 hours, 4.5 hours to less than or equal to 6 hours, 4.75 hours to less than or equal to 6 hours, 5 hours to less than or equal to 6 hours, 5.25 hours to less than or equal to 6 hours, 5.5 hours to less than or equal to 6 hours, 5.75 hours to less than or equal to 6 hours, 0.25 hours to less than or equal to 5.75 hours, 0.25 hours to less than or equal to 5.5 hours, 0.25 hours to less than or equal to 5.25 hours, 0.25 hours to less than or equal to 5 hours, 0.25 hours to less than or equal to 4.75 hours, 0.25 hours to less than or equal to 4.5 hours, 0.25 hours to less than or equal to 4.25 hours, 0.25 hours to less than or equal to 4 hours, 0.25 hours to less than or equal to 3.7 ... In an embodiment, the first time in the range of 0.25 hours to less than or equal to 3.5 hours, 0.25 hours to less than or equal to 3.25 hours, 0.25 hours to less than or equal to 3 hours, 0.25 hours to less than or equal to 2.75 hours, 0.25 hours to less than or equal to 2.5 hours, 0.25 hours to less than or equal to 2.25 hours, 0.25 hours to less than or equal to 1 hour, 0.25 hours to less than or equal to 0.75 hours, 0.25 hours to less than or equal to 0.5 hours, or any and all sub-ranges formed by any of these endpoints. In an embodiment, heat treating the precursor glass at a first temperature in a heat treating furnace for a first time can promote nucleation and growth of a desired crystalline phase in the precursor glass to form a glass-ceramic.In other embodiments, heat treating the precursor glass at a first temperature for a first time in a heat treatment furnace can promote nucleation of a desired crystalline phase in the precursor glass, and performing a second heat treatment step to grow the nucleated crystalline phase in the precursor glass to form a glass-ceramic.

[0176] For example, in an embodiment, the heat treatment may include a second step of heating the precursor glass in a heat treatment furnace at a rate of 1-10°C / minute until the furnace reaches a second temperature. The second temperature may be different from the first temperature. The second temperature of the furnace may be greater than or equal to 750°C to less than or equal to 950°C. In an embodiment, the second temperature may be greater than or equal to 750°C to less than or equal to 950°C, greater than or equal to 770°C to less than or equal to 950°C, greater than or equal to 790°C to less than or equal to 950°C, greater than or equal to 810°C to less than or equal to 950°C, greater than or equal to 830°C to less than or equal to 950°C, greater than or equal to 850°C to less than or equal to 950°C, greater than or equal to 870°C to less than or equal to 950°C, greater than or equal to 890°C to less than or equal to 950°C, greater than or equal to 910°C to less than or equal to 950°C, greater than or equal to 930°C to less than or equal to 950°C In an embodiment, the process for making the glass-ceramic comprises maintaining the precursor glass at a second temperature for a second time in a range of greater than or equal to 0.25 hours to less than or equal to 6 hours.For example, but not limited to, the precursor glass can be maintained at the second temperature for 0.25 hours to 6 hours or less, 0.5 hours to 6 hours or less, 0.75 hours to 6 hours or less, 1 hour to 6 hours or less, 1.25 hours to 6 hours or less, 1.5 hours to 6 hours or less, 1.75 hours to 6 hours or less, 2 hours to 6 hours or less, 2.25 hours to 6 hours or less, 2.5 hours to 6 hours or less, or 2.5 hours to 6 hours or less. 75 hours to less than or equal to 6 hours, 3 hours to less than or equal to 6 hours, 3.25 hours to less than or equal to 6 hours, 3.5 hours to less than or equal to 6 hours, 3.75 hours to less than or equal to 6 hours, 4 hours to less than or equal to 6 hours, 4.25 hours to less than or equal to 6 hours, 4.5 hours to less than or equal to 6 hours, 4.75 hours to less than or equal to 6 hours, 5 hours to less than or equal to 6 hours, 5.25 hours to less than or equal to 6 hours, 5.5 hours to less than or equal to 6 hours, 5.75 hours to less than or equal to 6 hours, 0.25 hours to less than or equal to 5.75 hours, 0.25 hours to less than or equal to 5.5 hours, 0.25 hours to less than or equal to 5.25 hours, 0.25 hours to less than or equal to 5 hours, 0.25 hours to less than or equal to 4.75 hours, 0.25 hours to less than or equal to 4.5 hours, 0.25 hours to less than or equal to 4.25 hours, 0.25 hours to less than or equal to 4 hours, 0.25 hours to less than or equal to 3.7 ... A second time in the range of 0.25 hours to less than or equal to 3.5 hours, 0.25 hours to less than or equal to 3.25 hours, 0.25 hours to less than or equal to 3 hours, 0.25 hours to less than or equal to 2.75 hours, 0.25 hours to less than or equal to 2.5 hours, 0.25 hours to less than or equal to 2.25 hours, 0.25 hours to less than or equal to 1 hour, 0.25 hours to less than or equal to 0.75 hours, 0.25 hours to less than or equal to 0.5 hours, or any and all subranges formed by any of these endpoints. Heat treating the precursor glass having a nucleated crystalline phase in a heat treating furnace at a second temperature for a second time will promote growth of the desired crystalline phase in the precursor glass to form a glass-ceramic.

[0177] In an embodiment, heat treating the precursor glass may further include heating the precursor glass to one or more subsequent furnace temperatures, such as greater than or equal to 750°C to less than or equal to 950°C, in a heat treatment furnace, and maintaining the precursor glass at each subsequent furnace temperature for a time in a range of greater than or equal to 0.25 hours to less than or equal to 6 hours.

[0178] In an embodiment, heat treating the precursor glass can be performed at ambient pressure. In an embodiment, heat treating the precursor glass can be performed at ambient atmospheric pressure (e.g., 101.325 kPa). In an embodiment, heat treating the precursor glass can be performed at about 100 kPa. In one or more embodiments, heat treating the precursor glass can be performed at a pressure less than or equal to 15 GPa. For example, but not limited to, heat treating the precursor glass can be performed at a pressure less than or equal to 15 GPa, less than or equal to 10 GPa, less than or equal to 5 GPa, or less than or equal to 1 GPa. According to the methods described herein, jeffbenite can be formed in a glass-ceramic article without the need for such pressurization.

[0179] After heat treatment (i.e., after nucleation and growth of the crystalline phase in the precursor glass), at least some grains of the crystalline phase having the jeffbenite crystalline structure will overlap and interlock with each other within the residual glass phase. The grains of the crystalline phase having the jeffbenite crystalline structure can overlap and interlock with each other within the bulk glass-ceramic, such as until the glass-ceramic has a fracture toughness as disclosed herein, such as about 0.75 MPa·m 1 / 2 Or other such values ​​as disclosed herein. In other aspects of the present disclosure, overlapping and interlocking of the jeffbenite crystalline structure occurs within the bulk glass-ceramic, but to an extent that does not provide such fracture toughness. In still other aspects, crystals of the jeffbenite crystalline structure may be present, but are so sparse that they do not overlap or interlock with each other to any extent within the bulk glass-ceramic.

[0180] In embodiments, the resulting glass-ceramic may be transparent, translucent, or opaque. In embodiments, the glass-ceramic has an average transmittance of ≥85% for light in a wavelength range of about 400 nm to about 1,000 nm at an article thickness of 0.85 mm. In embodiments, the average transmittance of the glass-ceramic for light in a wavelength range of about 400 nm to about 1000 nm at an article thickness of 0.85 mm is about 85% or greater, about 86% or greater, about 87% or greater, about 88% or greater, about 89% or greater, about 90% or greater, about 91% or greater, about 92% or greater, about 93% or greater.

[0181] In embodiments, the resulting glass-ceramic may be colored. The colored glass-ceramic article may include at least one colorant in a colorant package, the function of which is to impart a desired color to the glass-ceramic. The colorant package may include at least one of Au, Ag, Cr2O3, transition metal oxides (e.g., CuO, NiO, Co3O4, TiO2, Cr2O3), rare earth metal oxides (e.g., CeO2) and / or combinations thereof as colorants in the colorant package and the precursor glass or glass-ceramic may include greater than or equal to 1x10 -6 mol%, such as greater than 0.0005 mol%, such as greater than 0.001 mol%, such as greater than or equal to 0.01 mol%, such as greater than or equal to 0.1 mol%, such as greater than or equal to 0.2 mol%, such as greater than or equal to 0.01 mol%, and / or less than or equal to 10 mol% of colorant (i.e., the sum of all colorants in the colorant package), in some cases such as less than 5 mol%, such as less than 2 mol%, such as less than 1 mol%, such as less than 0.5 mol%, such as less than 0.25 mol. For example, yellow glass or glass-ceramic can contain rare earth metal oxides, such as greater than about 0.2 mol% and less than 1 mol%; black or gray glass can contain NiO and Co3O4 in such amounts; green glass or glass-ceramic can also contain Cr2O3; and pink, red or orange glass or glass-ceramic can contain small amounts of gold, such as greater than 1x10 -6 mol % and less than 0.5 mol %, consistent with the disclosure of U.S. Application No. 17 / 691,813. Other colorants may also be used in such amounts, such as iron oxides for, for example, green or brown glass or glass-ceramics, manganese oxides for amber or purple, selenium for red, antimony for white, uranium for luminescent colors, copper for red, tin for white, lead for yellow, and other colorants. However, some such colorants such as lead, antimony, and selenium may not be as ideal as, for example, other colorants. Further redox of the colorant, UV light treatment, and particulate matter may all contribute to the color of the glass, and the applicant hereby incorporates by reference in their entirety U.S. Application Nos. 63 / 433,060 filed on December 16, 2022, 63 / 433,065 filed on December 16, 2022, and 63 / 433,119 filed on December 16, 2022.

[0182] In embodiments, the colored glass-ceramic may form a glass-ceramic sheet. The colored glass-ceramic may have a thickness disclosed herein at some, most, and / or all frequencies in the visible spectrum (e.g., 4×10 14 Up to 8×10 14Hz; 380 to 750 nm wavelength) can be semi-translucent (e.g., >1% total transmittance, >5%, >10% and / or <95%, <92%, <90%, <85%, <80%, <70%). In addition, the total transmittance of the glass of the sheet through the main thickness (e.g., about 1 mm, about 0.6 mm, about 0.8 mm, about 1.2 mm, about 1.6 mm, about 2 mm, wherein about in this context means within 0.2 mm) is less than 90%, such as less than 85%, less than 80%, less than 70%, less than 60%, and / or less than 50% in at least one 10 nm broadband in the wavelength range of 380 nm to 750 nm (e.g., 380 to 390 nm; 390 to 400 nm; 385 to 395 nm; and / or 740 to 750 nm).

[0183] In embodiments, the colored glass-ceramic can be opaque, such as a solid color (e.g., white, black, forest green) that substantially does not transmit visible light (e.g., less than 1% total transmittance between wavelengths of 380 to 750 nanometers). The colored glass-ceramic can transmit light at some, most, and / or all frequencies in the visible spectrum (e.g., 4×10 14 Up to 8×10 14 Hz; 380 to 750 nm wavelength) can also be translucent, such as having a transmittance of >95%, >96% and / or <100%).

[0184] In an embodiment, the color of glass-ceramic can be described using CIELAB color space coordinates L*, a* and b*. In an embodiment, the value of L* can be 0 to 100, 10 to 100, 20 to 100, 30 to 100, 40 to 100, 50 to 100, 60 to 100, 70 to 100, 80 to 100, 90 to 100, 0 to 90, 0 to 80, 0 to 70, 0 to 60, 0 to 50, 0 to 40, 0 to 30, 0 to 20, 0 to 10, or any and all subranges formed by these endpoints. In an embodiment, the L* coordinate can be greater than or equal to 50, greater than or equal to 60, greater than or equal to 70, greater than or equal to 80 and less than or equal to 100. In an embodiment, the value of a* can be from -128 to 128, -120 to 128, -110 to 128, -100 to 128, -90 to 128, -80 to 128, -70 to 128, -60 to 128, -50 to 128, -40 to 128, -30 to 128, -20 to 128, -10 to 128, 0 to 128, 10 to 128, 20 to 128, 30 to 128, 40 to 128, 50 to 128, 60 to 128, 70 to 128, 80 to 128, 90 to 128, 100 to 128, 110 to 128, 120 to 128, or any and all subranges formed by these endpoints. In an embodiment, the a* coordinate may be greater than or equal to -100, greater than or equal to -90, greater than or equal to -80, greater than or equal to -70, greater than or equal to -60, greater than or equal to -50, greater than or equal to -40, greater than or equal to -30, or greater than or equal to -20. In an embodiment, the a* coordinate may be less than or equal to 100, less than or equal to 90, less than or equal to 80, less than or equal to 70, less than or equal to 60, less than or equal to 50, less than or equal to 40, less than or equal to 30, or less than or equal to 20. In an embodiment, the value of b* can be from -128 to 128, -120 to 128, -110 to 128, -100 to 128, -90 to 128, -80 to 128, -70 to 128, -60 to 128, -50 to 128, -40 to 128, -30 to 128, -20 to 128, -10 to 128, 0 to 128, 10 to 128, 20 to 128, 30 to 128, 40 to 128, 50 to 128, 60 to 128, 70 to 128, 80 to 128, 90 to 128, 100 to 128, 110 to 128, 120 to 128, or any and all subranges formed by these endpoints. In an embodiment, the b* coordinate can be greater than or equal to -100, greater than or equal to -90, greater than or equal to -80, greater than or equal to -70, greater than or equal to -60, greater than or equal to -50, greater than or equal to -40, greater than or equal to -30, or greater than or equal to -20.In an embodiment, the b* coordinate may be less than or equal to 100, less than or equal to 90, less than or equal to 80, less than or equal to 70, less than or equal to 60, less than or equal to 50, less than or equal to 40, less than or equal to 30, or less than or equal to 20.

[0185] In embodiments, the resulting glass-ceramic may have a thickness greater than or equal to 2.65 g / cm 3 To less than or equal to 2.95g / cm 3 In embodiments, the resulting glass-ceramic may have a density greater than or equal to 2.50 g / cm 3 To less than or equal to 3.70g / cm 3 For example, but not limited to, the glass-ceramic may have a density greater than or equal to 2.50 g / cm 3 To less than or equal to 3.70g / cm 3 , greater than or equal to 2.55g / cm 3 To less than or equal to 3.70g / cm 3 , greater than or equal to 2.60g / cm 3 To less than or equal to 3.70g / cm 3 , greater than or equal to 2.65g / cm 3 To less than or equal to 3.70g / cm 3 , greater than or equal to 2.70g / cm 3 To less than or equal to 3.70g / cm 3 , greater than or equal to 2.75g / cm 3 To less than or equal to 3.70g / cm 3 , greater than or equal to 2.80g / cm 3 To less than or equal to 3.70, greater than or equal to 2.85g / cm 3 To less than or equal to 3.70, greater than or equal to 2.90g / cm 3 To less than or equal to 3.70g / cm 3 , greater than or equal to 3.00g / cm 3 To less than or equal to 3.70g / cm 3 , greater than or equal to 3.10g / cm 3 To less than or equal to 3.70g / cm 3 , greater than or equal to 3.20g / cm 3 To less than or equal to 3.70g / cm 3 , greater than or equal to 3.30g / cm 3 To less than or equal to 3.70g / cm 3 , greater than or equal to 3.40g / cm 3 To less than or equal to 3.70g / cm 3, greater than or equal to 2.50g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 2.55g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 2.60g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 2.65g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 2.70g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 2.75g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 2.80g / cm 3 To less than or equal to 3.60, greater than or equal to 2.85g / cm 3 To less than or equal to 3.60, greater than or equal to 2.90g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 3.00g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 3.10g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 3.20g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 3.30g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 3.40g / cm 3 To less than or equal to 3.60g / cm 3 , greater than or equal to 2.65g / cm 3 To less than or equal to 2.95g / cm 3 , greater than or equal to 2.70g / cm 3 To less than or equal to 2.95g / cm 3 , greater than or equal to 2.75g / cm 3 To less than or equal to 2.95g / cm 3 , greater than or equal to 2.80g / cm 3 To less than or equal to 2.95g / cm 3 , greater than or equal to 2.85g / cm 3 To less than or equal to 2.95g / cm 3, greater than or equal to 2.90g / cm 3 To less than or equal to 2.95g / cm 3 , greater than or equal to 2.75g / cm 3 To less than or equal to 2.90g / cm 3 , greater than or equal to 2.75g / cm 3 To less than or equal to 2.85g / cm 3 , greater than or equal to 2.75g / cm 3 To less than or equal to 2.80g / cm 3 Without intending to be bound by theory, the presence of a crystalline phase having a jeffbenite crystal structure in a glass-ceramic article may result in a glass-ceramic having a relatively high density when considering the relatively light components of the glass-ceramic precursor.

[0186] In embodiments, the resulting glass-ceramic may include a crystalline phase having a jeffbenite crystalline structure. In embodiments, at least some of the grains, or even a majority of the grains, of the crystalline phase having a jeffbenite crystalline structure in the glass-ceramic may have a size that is smaller than the wavelength of visible light (e.g., measured from a slice / polished cut of the glass-ceramic, where "size" is a linear cross-sectional dimension, measured from the oppositely facing outermost surfaces of the grain along the surface of the slice / polished cut of the glass-ceramic through the geometric centroid of the grain, such as the longest cross-sectional dimension, the shortest cross-sectional dimension, the average cross-sectional dimension; unless otherwise indicated, "size" in this context refers to the longest such cross-sectional dimension of a given grain; see Figure 3-4 , 6A-6F and generally Fig. 9). For example, but not limited to, at least some of the grains, or even most of the grains, of the crystalline phase having the jeffbenite crystal structure may have a size less than or equal to 500 nm, 400 nm, 350 nm, 300 nm, 250 nm, 200 nm, 150 nm, or even less than or equal to 100 nm. In an embodiment, at least some of the grains, or even most of the grains, of the crystalline phase having the jeffbenite crystal structure in the glass-ceramic may have a size greater than or equal to 20 nm, or even greater than or equal to 30 nm. For example, but not limited to, at least some, or even a majority, of the crystallites of the crystalline phase having the jeffbenite crystal structure in the glass-ceramic may have a diameter of greater than or equal to 20 nm to less than or equal to 100 nm, greater than or equal to 30 nm to less than or equal to 100 nm, greater than or equal to 40 nm to less than or equal to 100 nm, greater than or equal to 50 nm to less than or equal to 100 nm, greater than or equal to 60 nm to less than or equal to 100 nm, greater than or equal to 70 nm to less than or equal to 100 nm, greater than or equal to 80 nm to less than or equal to 100 nm, greater than or equal to 90 nm to less than or equal to 100 nm, greater than or equal to 20 nm to less than or equal to 90 nm, or greater than or equal to 100 nm. In an embodiment, at least some of the grains of the crystalline phase having the jeffbenite crystalline structure may be in an elongated form. In an embodiment, at least some of the grains of the crystalline phase having the jeffbenite crystalline structure may include a needle-like or plate-like shape. In an embodiment, the grains of the crystalline phase having the jeffbenite crystalline structure may include a bulk modulus of about 170 GPa. In an embodiment, grains of a crystalline phase having a jeffbenite crystal structure may include a hardness of about 1350 VHn.

[0187] In embodiments, the resulting glass-ceramic may include a phase combination, wherein at least some grains of the crystalline phase of the phase combination, or even most of the grains, have a size less than the wavelength of visible light. For example, but not limited to, at least some grains of the crystalline phase in the phase combination, or even most of the grains, may have a size less than or equal to 500nm, 400nm, 350nm, 300nm, 250nm, 200nm, 150nm, or even less than or equal to 100nm. In embodiments, at least some grains of the crystalline phase in the phase combination, or even most of the grains, may have a size greater than or equal to 20nm or even greater than or equal to 30nm. For example, but not limited to, at least some of the grains of the crystalline phase in the glass-ceramic, or even a majority, may have a diameter of greater than or equal to 20 nm to less than or equal to 100 nm, greater than or equal to 30 nm to less than or equal to 100 nm, greater than or equal to 40 nm to less than or equal to 100 nm, greater than or equal to 50 nm to less than or equal to 100 nm, greater than or equal to 60 nm to less than or equal to 100 nm, greater than or equal to 70 nm to less than or equal to 100 nm, greater than or equal to 80 nm to less than or equal to 100 nm, greater than or equal to 90 nm to less than or equal to 100 nm, greater than or equal to 20 nm to less than or equal to 90 nm, greater than or equal to 30 nm to less than or equal to 100 nm, A grain size of less than or equal to 90 nm, greater than or equal to 20 nm to less than or equal to 80 nm, greater than or equal to 30 nm to less than or equal to 80 nm, greater than or equal to 20 nm to less than or equal to 70 nm, greater than or equal to 30 nm to less than or equal to 70 nm, greater than or equal to 20 nm to less than or equal to 60 nm, greater than or equal to 30 nm to less than or equal to 60 nm, greater than or equal to 20 nm to less than or equal to 50 nm, greater than or equal to 30 nm to less than or equal to 50 nm, greater than or equal to 20 nm to less than or equal to 40 nm, greater than or equal to 30 nm to less than or equal to 40 nm, or any and all sub-ranges formed by any of these endpoints.

[0188] In an embodiment, the glass-ceramic may have an elastic modulus greater than or equal to 50 GPa and less than or equal to 200 GPa. In an embodiment, the glass-ceramic may have an elastic modulus greater than or equal to 50 GPa, greater than or equal to 80 GPa, greater than or equal to 90 GPa, or even greater than or equal to 100 GPa. In an embodiment, the glass-ceramic may have an elastic modulus less than or equal to 200 GPa, or even less than or equal to 150 GPa. In an embodiment, the glass-ceramic can have an elastic modulus greater than or equal to 50 GPa and less than or equal to 200 GPa, greater than or equal to 50 GPa and less than or equal to 175 GPa, greater than or equal to 60 GPa and less than or equal to 175 GPa, greater than or equal to 60 GPa and less than or equal to 150 GPa, greater than or equal to 70 GPa and less than or equal to 175 GPa, greater than or equal to 70 GPa and less than or equal to 150 GPa, greater than or equal to 80 GPa and less than or equal to 175 GPa, or even greater than or equal to 80 GPa and less than or equal to 150 GPa, or any and all subranges formed by any of these endpoints.

[0189] In embodiments, the glass-ceramic exhibits a relative humidity of about 0.75 MPa·m 1 / 2 or greater, about 0.85MPa·m 1 / 2 or larger, about 1.0MPa·m 1 / 2 or larger, about 1.1MPa·m 1 / 2 or greater, 1.2MPa·m 1 / 2 or greater, 1.3MPa·m 1 / 2 or greater, 1.4MPa·m 1 / 2 or greater, 1.5MPa·m 1 / 2 or greater, 1.6MPa·m 1 / 2 or greater, 1.7MPa·m 1 / 2 or greater, 1.8MPa·m 1 / 2 or greater, 1.9MPa·m 1 / 2 or greater, or about 2.0 MPa·m 1 / 2 In the embodiment, the fracture toughness is greater than or equal to 0.75 MPa·m 1 / 2 To less than or equal to 2MPa·m 1 / 2 or any and all sub-ranges formed by any of these endpoints.

[0190] In one or more embodiments, the glass-ceramic has a Vickers hardness. In some embodiments, the non-ion exchanged glass-ceramic exhibits a Vickers hardness of greater than or equal to 600 kgf / mm 2 To less than or equal to 1400kgf / mm 2 , greater than or equal to 600kgf / mm2 To less than or equal to 1300kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 1200kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 1100kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 1000kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 900kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 875kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 850kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 825kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 800kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 775kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 750kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 725kgf / mm 2 , greater than or equal to 600kgf / mm 2 To less than or equal to 700kgf / mm 2 , greater than or equal to 700kgf / mm 2 To less than or equal to 900kgf / mm 2 , greater than or equal to 700kgf / mm 2 To less than or equal to 875kgf / mm 2 , greater than or equal to 700kgf / mm 2 To less than or equal to 850kgf / mm 2 , greater than or equal to 700kgf / mm 2 To less than or equal to 825kgf / mm 2 , or greater than or equal to 700kgf / mm 2 To less than or equal to 800kgf / mm 2In some embodiments, the Vickers hardness is 600 kgf / mm 2 or higher, 625kgf / mm 2 or higher, 650kgf / mm 2 or higher, 675kgf / mm 2 or higher, 700kgf / mm 2 or higher, 725kgf / mm 2 or higher, 750kgf / mm 2 or higher, 775kgf / mm 2 or higher, 800kgf / mm 2 or higher, 825kgf / mm 2 or higher, 850kgf / mm 2 or higher, 875kgf / mm 2 or higher, or 900kgf / mm 2 or higher, or any and all subranges formed by any of these endpoints.

[0191] The resulting glass-ceramic can be provided in sheet form, which can then be reshaped or re-formed into a curved or bent piece of uniform thickness by pressing, blowing, bending, concave, vacuum forming or other means. The reshaping can be performed before the heat treatment, or the shaping step can also serve as the heat treatment step, wherein the shaping and heat treatment are performed substantially simultaneously.

[0192] The glass-ceramics and glass-ceramic articles described herein can be used in a variety of applications, including, for example, cover glass or glass back applications in consumer electronic devices or commercial electronic devices (including, for example, LCD and LED displays, computer monitors, and automated teller machines (ATMs)); for touch screen or touch sensor applications, for portable electronic devices, including, for example, mobile phones, personal media players, and tablet computers; for integrated circuit applications, including, for example, semiconductor wafers; for photovoltaic applications; for architectural glass applications; for automotive or vehicle glass applications; or for commercial or household appliance applications. In an embodiment, consumer electronic devices (e.g., smartphones, tablet computers, personal computers, ultrabooks, televisions, and cameras), architectural glass, and / or automotive glass may include a glass article as described herein.

[0193] Figure 1 and 2 An exemplary electronic device incorporating any of the glass-ceramic articles disclosed herein is shown in FIG. Figure 1 and 2A consumer electronic device 100 is shown, comprising a housing 102 having a front surface 104, a rear surface 106, and side surfaces 108; electrical components (not shown) at least partially or completely within the housing and including at least a controller, a memory, and a display 110 located at or adjacent to the front surface of the housing; and a cover substrate 112 located at or above the front surface of the housing such that it is above the display. In an embodiment, at least a portion of at least one of the cover substrate 112 and the housing 102 may include any of the glass-ceramic articles disclosed herein.

[0194] Reference now Fig. 8A and 8B , which depicts one embodiment of a glass-ceramic article 200 formed from the glass-ceramic described herein. In this embodiment, the glass-ceramic article is in the form of a glass sheet and may include a body 201 disposed between opposing first and second surfaces 202, 204. The body 201 comprises or consists essentially of a glass-ceramic as described herein. The first surface 202 and the second surface 204 may be major surfaces of the glass sheet that are opposite to each other. In an embodiment, the first surface 202 and the second surface 204 may be generally planar and spaced apart from each other by a thickness T defined between the first surface 202 and the second surface 204. The first surface 202 and the second surface 204 are bounded by at least one edge surface 206 that forms a perimeter that generally defines the shape of the glass-ceramic article 200. In Fig. 8A and 8B In the embodiment illustrated in , the shape of the glass-ceramic article is rectangular and includes a length L and a width W. In this embodiment, the width W of the glass sheet is defined as the distance between the opposite edges along the first surface 202 orthogonal to the thickness T. The length L is defined as the distance between the opposite edges along the first surface 202 orthogonal to the thickness T and the width W. In an embodiment, the width W can be greater than or equal to the thickness T and the length L can be greater than or equal to the width W. However, it should be understood that other shapes of the glass-ceramic article are also expected and possible, including but not limited to squares, circles and other regular or irregular geometric shapes. For example, the glass-ceramic article may also include rods, fibers, spherical or nearly spherical, curved sheets, tubes, bowls, lenses, vials, bottles or other containers.

[0195] In an embodiment, the thickness T of the glass-ceramic article 200 can be as described herein. The length L and width W of the glass-ceramic article can be selected according to the specific application in which the glass-ceramic article 200 is used. In an embodiment, the length L and width W of the glass-ceramic article can be greater than or equal to 5mm, such as greater than or equal to 10mm, greater than or equal to 15mm, greater than or equal to 20mm, greater than or equal to 25mm and greater than or equal to 30mm. For example, but not limited to, the length L of the glass-ceramic article can be greater than or equal to 30mm to less than or equal to 1m, greater than or equal to 30mm to less than or equal to 75cm, greater than or equal to 30mm to less than or equal to 50cm, greater than or equal to 30mm to less than or equal to 25cm, greater than or equal to 30mm to less than or equal to 20cm, greater than or equal to 30mm to less than or equal to 15cm, greater than or equal to 30mm to less than or equal to 10cm, greater than or equal to 30mm to less than or equal to 5cm, or any and all sub-ranges formed by any of these endpoints. The width W of the glass-ceramic article can be greater than or equal to 30 mm to less than or equal to 1 m, greater than or equal to 30 mm to less than or equal to 75 cm, greater than or equal to 30 mm to less than or equal to 50 cm, greater than or equal to 30 mm to less than or equal to 25 cm, greater than or equal to 30 mm to less than or equal to 20 cm, greater than or equal to 30 mm to less than or equal to 15 cm, greater than or equal to 30 mm to less than or equal to 10 cm, greater than or equal to 30 mm to less than or equal to 5 cm, or any and all subranges formed by any of these endpoints. In embodiments where the glass-ceramic article is a glass sheet, such as Fig. 8A and 8B As shown in FIG. 1 , the surface of the glass sheet may have a thickness greater than or equal to 25 mm. 2 In embodiments where the glass-ceramic article is a glass sheet, the glass-ceramic in the body 201 of the glass sheet may have an area greater than or equal to 25 mm. 3 volume.

[0196] In an embodiment, the body 201 of the glass-ceramic article 200 has an average transmittance of at least 75% for light in the wavelength range of 400nm to 800nm ​​(including the endpoints) at a thickness of 0.85mm of the article, so that the glass-ceramic article is transparent. In an embodiment, the body 201 of the glass-ceramic article 200 has an average transmittance of greater than or equal to 20% to less than 75% for light in the wavelength range of 400nm to 800nm ​​(including the endpoints) at a thickness of 0.85mm of the article, so that the glass-ceramic article is translucent. In an embodiment, the body of the glass-ceramic article has an average transmittance of less than 20% for light in the wavelength range of 400nm to 800nm ​​(including the endpoints) at a thickness of 0.85mm of the article when measured at normal incidence, so that the glass-ceramic article is opaque. In an embodiment, the body 201 of the glass-ceramic article 200 is at least partially translucent such that at least 20% of light having a wavelength of 400 nm to 800 nm directed into the thickness of the article is transmitted through the body.

[0197] Jeffbenite Characterization Method

[0198] In embodiments, the glass-ceramic article can be tested by X-ray diffraction to determine whether the glass-ceramic article contains a jeffbenite crystalline phase, as described in detail herein. The following equipment and software were used for the test: X-ray diffractometer - Bruker-AXSD8 Endeavor equipped with Cu radiation and Lynx Eye detector, Rocklabs Whisper series ring mill, backfill sample holder (Malvern Panalytical PW1770 / 10 powder sample preparation kit and PW18XX sample holder), 6" x 6" weighing paper, slide, spatula, and data analysis software (MDI Jade, Bruker Topas and Powder Diffraction File Database PDF-4).

[0199] The sample of glass-ceramic product is received with small pieces of glass-ceramic. The glass-ceramic block is broken in a ring mill so that about 3 grams of glass-ceramic can be obtained. The 3 grams of glass-ceramic sample is ground into a fine powder using a Rocklabs ring mill, and ground for about 30 seconds.

[0200] The PW18XX sample holder is filled with fine powder as described herein. Clamp the sample holding ring onto the preparation table. Spread the fine powder into the sample holding ring so that the fine powder is packed into a cone shape inside the holding ring. Use a glass slide to press the fine powder firmly down into the holding ring. Use a glass slide to scrape any excess powder back into the holding ring. Additional fine powder can be added as needed to fill the sample holder. Repeat this process until a densely packed powder sample is obtained. Use the edge of the glass slide to remove excess fine powder above the edge of the holding ring. Place the base plate onto the holding ring and clamp it in place. Remove the complete sample holder from the preparation table and load it into the X-ray diffractometer.

[0201] Create a job file for the sample in XRD Commander. The job file includes the location of the sample in the X-ray diffractometer and the sample's identification information. After the job file is created, the X-ray diffractometer scans the sample.

[0202] After scanning the sample through the X-ray diffractometer, the data obtained from the X-ray diffractometer was analyzed using MDI Jade software. The file containing the data from the X-ray diffractometer was opened in MDI Jade. The "Phases" window was used to identify the index peaks in the data. Table 1 includes the index peaks of at least some phases that may be present in the glass-ceramic containing jeffbenite. The PDF number of each phase is entered in the "PDF Recall" field. Fig.14 Plots the location of the PDF Recall field in the Phases window of MDI Jade.

[0203] Table 1

[0204] Peak(Angstrom) Mutually card number 6.2、3.2、2.7 Jeffbenite 69-138 2.95、2.54、1.81 <![CDATA[tetragonal ZrO2]]> 50-1089 3.87、2.45 Forsterite 34-189

[0205] For some phases, a large number of solid solutions are possible. The lattice parameters can be scaled to make the card data match the sample data. To scale the lattice parameters, select the name of the phase in the Phase tab and then select the ascending size arrows on the right side of the main display. The position of the arrows is plotted on the Fig.15 The lattice constraints can be increased and decreased using the left and right mouse buttons, respectively.

[0206] The phases listed in Table 1 can be found in glass-ceramic samples containing jeffbenite. If there are unidentified peaks in the data, the PDF-4 database can be searched using the composition and peak positions of the glass-ceramic. After all phases have been identified and the lattice adjusted to match the sample data, use the "Assign Phases" function on the "Peaks" tab. The software lists the peaks and finds the assigned phase for each peak. Some peaks may not have an assigned phase. This is determined by Fig.161 in the peak list shown in Figure 1. If a peak does not include the assigned phase, the peak is evaluated by the instrument or peak search algorithm to determine whether it is a real peak or an artifact. If the peak is a real peak, the PDF-4 database is manually searched to match the missing peak to the chemical composition of the sample. Although the automatic search matching program is powerful, the highly solid solutions in some glass-ceramic products may cause problems for the automatic matching program. Therefore, the operator may have to perform the above steps.

[0207] Perform a Rietveld analysis using Topas to determine the lattice constants and unit cell volume. Open the file "Jeffbenite with hkl phase and ZrO2.pro" in Topas. Run an initial refinement by clicking the red run arrow, as shown in Fig.17 . When the refinement converges, save the parameters. The scan data from the X-ray diffractometer is then loaded into Topas by clicking on the file name at the top of the file tree in the left hand window, selecting "Replace Scan Data", navigating to the folder where the data is located and double clicking on the file containing the data to load the data. Fig.18 Shown is the location of "Replace Scan Data" in Topas. The file tree under Scan can be expanded so that all phases are visible. Set the model to represent the phases present in the current sample. This is done by clicking on the phase in the file tree and then checking or unchecking the "Use Phase" box in the structure window. If the phase exists, the box is checked, and if it does not, the box is unchecked. Fig.19 The location of the "Use Phase" box is depicted in Figure 1. If there is no matching structure for experimental jeffbenite in the database, the Jeffbenite HKL phase is used in this step. The lattice parameters and unit cell volume in the Jeffbenite HKL phase are the best match and can be used to characterize the jeffbenite in the sample.

[0208] Once all structures and phases of the sample have been correctly identified, click the red run arrow and Topas will refine until it converges to a solution. After the solution converges, analyze the RwP values, difference maps, and modeled phase data. Fig. 20RwP values, difference graphs, and modeled phase data are plotted in . The RwP value in the upper right window should be less than 5. In the difference graph, a curve between the experimental data and the modeled data (inside the ellipse) and a stick pattern of each phase are shown. If there is a peak in the difference curve, there may be a phase missing. If there is a phase missing, repeat the phase identification step of the analysis. Check the modeled phase data to determine whether each phase looks reasonable. The phase that looks reasonable remains below the background, has no negative data points, and has a peak width that matches the experimental data. If the modeled phase data does not look reasonable, the model may fall into a local minimum. If the model falls into a local minimum, restart the Rietveld analysis in Topas. If the RwP value, difference graph, and modeled phase data are acceptable, the lattice constraints and unit cell volume of jeffbenite are correct, and the lattice constraints and unit cell volume of the sample are recorded.

[0209] In embodiments, the glass-ceramic article may have a lattice parameter corresponding to jeffbenite and indicating the presence of a jeffbenite crystalline phase in the glass-ceramic article. For example, in embodiments, the glass-ceramic article may have a lattice parameter greater than or equal to and less than or equal to or even greater than or equal to and less than or equal to In embodiments, the glass-ceramic article may have a lattice parameter greater than or equal to and less than or equal to Greater than or equal to and less than or equal to Greater than or equal to and less than or equal to Greater than or equal to and less than or equal to Greater than or equal to and less than or equal to or even greater than or equal to 18.2 and less than or equal to In embodiments, the glass-ceramic article may have a lattice parameter of greater than or equal to 775A. 3 and less than or equal to 825A 3 , greater than or equal to 775A 3 and less than or equal to 810A 3 , greater than or equal to 790A 3 and less than or equal to 825A 3 Or even greater than or equal to 790A 3 and less than or equal to 810A 3 In embodiments, the glass-ceramic article may have a lattice volume greater than or equal to and less than or equal to Greater than or equal to and less than or equal to Greater than or equal to and less than or equal to Greater than or equal to and less than or equal to Greater than or equal to and less than or equal to or even greater than or equal to and less than or equal to The peak position.

[0210] In an embodiment, the glass-ceramic article may have an X-ray diffraction (XRD) spectrum corresponding to jeffbenite and indicating the presence of a jeffbenite crystalline phase in the glass-ceramic article. For example, in an embodiment, the glass-ceramic article may have an XRD spectrum including a first peak at a 2θ angle between 30° and 32°, a second peak at a 2θ angle between 33° and 35°, a third peak at a 2θ angle between 40° and 42°, and a fourth peak and a fifth peak at a 2θ angle between 55° and 58°, wherein the first, second, third, fourth, and fifth peaks correspond to jeffbenite.

[0211] ***

[0212] Without wishing to be bound by theory, it is believed that the ability to produce a high pressure crystalline phase (e.g., nucleated and / or grown at 2.5 GPa) that may be considered to have a jeffbenite crystal structure at the temperatures and pressures disclosed herein (e.g., standard atmospheric pressure, about 101.325 kPa) may be related to the alumina content of the precursor glass. More specifically, this ability may correspond to the amount of alumina in the batch being less than the stoichiometric ideal for natural jeffbenite crystals, i.e., Mg 2 O 3 2 O 4 2 O 5 6 7 8 9 10 12 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 x Al y SiO 12, where x=3 and y=2 ("nominal jeffbenite"), e.g., a formulation where y is greater than 0 but only close to y=2, e.g., y is preferably in the range of at least 0.5 to no greater than 1.5, which can achieve a more ideal modulus for handling and forming (e.g., an elastic modulus greater than or equal to 85 MPa), where x varies proportionally, and, for example, zirconium oxide or titanium dioxide can be exchanged with additional magnesium oxide. In a mixture (e.g., an amorphous glass, a glass precursor to a glass-ceramic), in at least some of the crystals where the locally available y of the aluminum oxide is less than 2, it is expected that at least some of the corresponding crystals (after nucleation and growth therein) contain half of the aluminum stoichiometry ideal of a natural jeffbenite crystal, where the other half (i.e., not present) will therefore not need to be squeezed into the smallest octahedral position M2 at high pressure, and the aluminum that is present can simply enter the larger M3 position, e.g., Mg 3.5 (Zr,Ti) 0.5 AlSi3O 12 , where the components in brackets are substitutes for the corresponding example crystals. This arrangement of components with less alumina in the batch may improve the stability of jeffbenite at lower pressures and temperatures, such as possibly even at room temperature (e.g., 27° C.). Based on the above, the applicant has found that when the composition of the natural jeffbenite crystal (i.e., Mg3Al2Si3O 12 ) stoichiometrically ideal amount batching components and when ceramicizing at normal pressure, the amount of the crystalline phase of the jeffbenite crystalline structure is very small. But, batching is less than y=1.5 and / or greater than y=0.5, for example, about half of the aluminum content of nominal jeffbenite, and heat-treated under pressure (for example atmospheric pressure) disclosed herein, the glass-ceramic produced has the crystalline phase that is mainly the jeffbenite structure, as shown in the embodiments disclosed herein.

[0213] In an embodiment, the phase combination of the glass-ceramic described herein may include one or more crystalline phases, such as a crystalline phase comprising a jeffbenite crystal structure, in an amount of greater than or equal to 10 wt % to less than or equal to 85 wt % by weight of the glass-ceramic article. In an embodiment, the amount of one or more crystalline phases may be greater than or equal to 10 wt %, greater than or equal to 20 wt %, greater than or equal to 30 wt %, greater than or equal to 40 wt %, greater than or equal to 50 wt %, greater than or equal to 60 wt %, greater than or equal to 70 wt %, or even greater than or equal to 80 wt %, by weight of the glass-ceramic article. In an embodiment, the amount of one or more crystalline phases may be less than or equal to 85 wt %, less than or equal to 75 wt %, less than or equal to 65 wt %, or even less than or equal to 55 wt %, by weight of the glass-ceramic article. In embodiments, the amount of crystalline phase, based on the weight of the glass-ceramic article, can be from greater than or equal to 10 wt % to less than or equal to 85 wt %, from greater than or equal to 10 wt % to less than or equal to 75 wt %, from greater than or equal to 10 wt % to less than or equal to 65 wt %, from greater than or equal to 10 wt % to less than or equal to 55 wt %, from greater than or equal to 20 wt % to less than or equal to 85 wt %, from greater than or equal to 20 wt % to less than or equal to 75 wt %, from greater than or equal to 20 wt % to less than or equal to 65 wt %, from greater than or equal to 20 wt % to less than or equal to 55 wt %, from greater than or equal to 30 wt % to less than or equal to 85 wt %, from greater than or equal to 30 wt % to less than or equal to 75 wt %, from greater than or equal to 30 wt % to less than or equal to 65 wt %, from greater than or equal to 30 wt % to less than or equal to 55 wt %, from greater than or equal to 40 wt % to less than or equal to 85 wt %. %, greater than or equal to 40 weight % to less than or equal to 75 weight %, greater than or equal to 40 weight % to less than or equal to 65 weight %, greater than or equal to 40 weight % to less than or equal to 55 weight %, greater than or equal to 50 weight % to less than or equal to 85 weight %, greater than or equal to 50 weight % to less than or equal to 75 weight %, greater than or equal to 50 weight % to less than or equal to 65 weight %, greater than or equal to 50 weight % to less than or equal to 55 weight %, greater than or equal to 60 weight % to less than or equal to 85 weight %, greater than or equal to 60 weight % to less than or equal to 75 weight %, greater than or equal to 60 weight % to less than or equal to 65 weight %, greater than or equal to 70 weight % to less than or equal to 85 weight %, greater than or equal to 70 weight % to less than or equal to 75 weight %, or even greater than or equal to 80 weight % to less than or equal to 85 weight %, or any and all subranges formed by any of these endpoints.

[0214] In an embodiment, the phase combination of glass-ceramic described herein can include a glass phase greater than or equal to 15 wt % to less than or equal to 90 wt %, such as residual glass, by the weight of the glass-ceramic article. In an embodiment, the amount of the glass phase can be greater than or equal to 15 wt %, greater than or equal to 25 wt %, greater than or equal to 35 wt %, or even greater than or equal to 45 wt %, by the weight of the glass-ceramic article. In an embodiment, the amount of the glass phase can be less than or equal to 90 wt %, less than or equal to 80 wt %, less than or equal to 70 wt %, less than or equal to 60 wt %, less than or equal to 50 wt %, less than or equal to 40 wt %, less than or equal to 30 wt %, or even less than or equal to 20 wt %, by the weight of the glass-ceramic article. In embodiments, the amount of glass phase can be from greater than or equal to 15 wt % to less than or equal to 90 wt %, from greater than or equal to 15 wt % to less than or equal to 80 wt %, from greater than or equal to 15 wt % to less than or equal to 70 wt %, from greater than or equal to 15 wt % to less than or equal to 60 wt %, from greater than or equal to 15 wt % to less than or equal to 50 wt %, from greater than or equal to 15 wt % to less than or equal to 40 wt %, from greater than or equal to 15 wt % to less than or equal to 30 wt %, from greater than or equal to 15 wt % to less than or equal to 20 wt %, from greater than or equal to 25 wt % to less than or equal to 90 wt %, from greater than or equal to 25 wt % to less than or equal to 80 wt %, from greater than or equal to 25 wt % to less than or equal to 70 wt %, from greater than or equal to 25 wt % to less than or equal to 60 wt %, from greater than or equal to 25 wt % to less than or equal to 50 wt %. %, greater than or equal to 25 weight % to less than or equal to 40 weight %, greater than or equal to 25 weight % to less than or equal to 30 weight %, greater than or equal to 35 weight % to less than or equal to 90 weight %, greater than or equal to 35 weight % to less than or equal to 80 weight %, greater than or equal to 35 weight % to less than or equal to 70 weight %, greater than or equal to 35 weight % to less than or equal to 60 weight %, greater than or equal to 35 weight % to less than or equal to 50 weight %, greater than or equal to 35 weight % and less than or equal to 40 weight %, greater than or equal to 45 weight % to less than or equal to 90 weight %, greater than or equal to 45 weight % to less than or equal to 80 weight %, greater than or equal to 45 weight % to less than or equal to 70 weight %, greater than or equal to 45 weight % to less than or equal to 60 weight %, or even greater than or equal to 45 weight % to less than or equal to 50 weight %, or any and all subranges formed by any of these endpoints.

[0215] As described herein, in embodiments, the jeffbenite crystalline structure can be the main crystalline phase. In embodiments, the amount of the jeffbenite crystalline structure in the one or more crystalline phases can be greater than or equal to 90 wt % to less than or equal to 100 wt %, based on the total weight of the one or more crystalline phases. In embodiments, the amount of the jeffbenite crystalline structure in the one or more crystalline phases can be greater than or equal to 90 wt %, greater than or equal to 92 wt %, greater than or equal to 94 wt %, greater than or equal to 96 wt %, or even greater than or equal to 98 wt %. In embodiments, the amount of the jeffbenite crystalline structure in the one or more crystalline phases can be less than or equal to 100 wt %, less than or equal to 97 wt %, or even less than or equal to 95 wt %, based on the total weight of the one or more crystalline phases. In embodiments, the amount of jeffbenite crystalline structure in the one or more crystalline phases can be from greater than or equal to 90 wt% to less than or equal to 100 wt%, greater than or equal to 90 wt% to less than or equal to 97 wt%, greater than or equal to 90 wt% to less than or equal to 95 wt%, greater than or equal to 92 wt% to less than or equal to 100 wt%, greater than or equal to 92 wt% to less than or equal to 97 wt%, greater than or equal to 92 wt% to less than or equal to 95 wt%, greater than or equal to 94 wt% to less than or equal to 100 wt%, greater than or equal to 94 wt% to less than or equal to 97 wt%, greater than or equal to 94 wt% to less than or equal to 95 wt%, greater than or equal to 96 wt% to less than or equal to 100 wt%, greater than or equal to 96 wt% to less than or equal to 97 wt%, or even greater than or equal to 98 wt% to less than or equal to 100 wt%, based on the total weight of the one or more crystalline phases, or any and all subranges formed by any of these endpoints. In embodiments, the jeffbenite crystalline structure comprises 100 weight percent of the crystalline phase, based on the total weight of the crystalline phase.

[0216] As described herein, in embodiments, one or more crystalline phases of the phase combination may include one or more secondary crystalline phases. The amount of one or more secondary crystalline phases in the glass-ceramic may be less than the main crystalline phase. In embodiments, one or more secondary crystalline phases may include tetragonal zirconium oxide (ZrO2), ZrTiO4, or a combination thereof. In embodiments, by the total weight of one or more crystalline phases, the amount of one or more secondary crystalline phases in one or more crystalline phases may be greater than or equal to 0 wt% to less than or equal to 10 wt%. In embodiments, by the total weight of one or more crystalline phases, the amount of one or more secondary crystalline phases in one or more crystalline phases may be greater than or equal to 0 wt%, greater than or equal to 3 wt%, or even greater than or equal to 5 wt%. In embodiments, by the total weight of one or more crystalline phases, the amount of one or more secondary crystalline phases in one or more crystalline phases may be less than or equal to 10 wt%, less than or equal to 8 wt%, less than or equal to 6 wt%, less than or equal to 4 wt%, or even less than or equal to 2 wt%. In an embodiment, the amount of one or more sub crystalline phases in one or more crystalline phases, based on the total weight of the one or more crystalline phases, can be greater than or equal to 0 wt% to less than or equal to 10 wt%, greater than or equal to 0 wt% to less than or equal to 8 wt%, greater than or equal to 0 wt% to less than or equal to 6 wt%, greater than or equal to 0 wt% to less than or equal to 4 wt%, greater than or equal to 0 wt% to less than or equal to 2 wt%, greater than or equal to 3 wt% to less than or equal to 10 wt%, greater than or equal to 3 wt% to less than or equal to 8 wt%, greater than or equal to 3 wt% to less than or equal to 6 wt%, greater than or equal to 3 wt% to less than or equal to 4 wt%, greater than or equal to 0 wt% to less than or equal to 10 wt%, greater than or equal to 5 wt% to less than or equal to 8 wt%, or even greater than or equal to 5 wt% to less than or equal to 6 wt%, or any and all subranges formed by any of these endpoints.

[0217] Although not wishing to be bound by theory, it is believed that the grain size can be increased by reducing the concentration of the nucleating agent. In an embodiment, at least some of the grains comprising at least one crystalline phase of the jeffbenite crystalline structure may have a maximum size of greater than or equal to 20 nm to less than or equal to 500 nm. In an embodiment, at least some of the grains comprising at least one crystalline phase of the jeffbenite crystalline structure may have a maximum size of greater than or equal to 20 nm, greater than or equal to 40 nm, or even greater than or equal to 60 nm. In an embodiment, at least some of the grains comprising at least one crystalline phase of the jeffbenite crystalline structure may have a maximum size of less than or equal to 500 nm, less than or equal to 450 nm, less than or equal to 400 nm, less than or equal to 350 nm, less than or equal to 300 nm, less than or equal to 250 nm, or even less than or equal to 200 nm. In embodiments, at least some of the grains of at least one crystalline phase comprising the jeffbenite crystalline structure may have a diameter of 20 nm or more to 500 nm or less, 20 nm or more to 450 nm or less, 20 nm or more to 400 nm or less, 20 nm or more to 350 nm or less, 20 nm or more to 300 nm or less, 20 nm or more to 250 nm or less, 20 nm or more to 200 nm or less, 40 nm or more to 500 nm or less, 40 nm or more to 450 nm or less, 40 nm or more to 400 nm or less, or 40 nm or more to 400 nm or less. In some embodiments, the present invention relates to a maximum dimension of at least 40 nm to less than or equal to 350 nm, at least 40 nm to less than or equal to 300 nm, at least 40 nm to less than or equal to 250 nm, at least 40 nm to less than or equal to 200 nm, at least 60 nm to less than or equal to 500 nm, at least 60 nm to less than or equal to 450 nm, at least 60 nm to less than or equal to 400 nm, at least 60 nm to less than or equal to 350 nm, at least 60 nm to less than or equal to 300 nm, at least 60 nm to less than or equal to 250 nm, or even at least 60 nm to less than or equal to 200 nm, or any and all sub-ranges formed by any of these endpoints.

[0218] In an embodiment, the precursor glass or glass-ceramic composition may include greater than or equal to 2.5 mol% to less than or equal to 20 mol% Al2O3. In an embodiment, the concentration of Al2O3 in the precursor glass or glass-ceramic composition may be a positive amount, such as greater than an impurity (0.05 mol% or greater), such as greater than or equal to 2.5 mol% to less than or equal to 20 mol%, greater than or equal to 2.5 mol% to less than or equal to 18 mol%, greater than or equal to 2.5 mol% to less than or equal to 16 mol%, greater than or equal to 2.5 mol% to less than or equal to 14 mol%, greater than or equal to 2.5 mol% to less than or equal to 12 mol%, greater than or equal to 4 mol% to less than or equal to 20 mol%, greater than or equal to 4 mol% to less than or equal to 18 mol%, greater than or equal to 4 mol% to less than or equal to 16 mol%, greater than or equal to 4 mol% to less than or equal to 14 mol%, greater than or equal to 1 % to less than or equal to 12 mol %, greater than or equal to 6 mol % to less than or equal to 20 mol %, greater than or equal to 6 mol % to less than or equal to 18 mol %, greater than or equal to 6 mol % to less than or equal to 16 mol %, greater than or equal to 6 mol % to less than or equal to 14 mol %, greater than or equal to 6 mol % to less than or equal to 12 mol %, greater than or equal to 8 mol % to less than or equal to 20 mol %, greater than or equal to 8 mol % to less than or equal to 18 mol %, greater than or equal to 8 mol % to less than or equal to 16 mol %, greater than or equal to 8 mol % to less than or equal to 14 mol %, or even greater than or equal to 8 mol % to less than or equal to 12 mol %, or any and all subranges formed by any of these endpoints. In embodiments, the concentration of Al2O3 in the precursor glass or glass-ceramic composition may be greater than or equal to 2.5 mol %, 4 mol %, 6 mol %, or 8 mol %. In embodiments, the concentration of Al2O3 may be less than or equal to 20 mol%, 18 mol%, 16 mol%, 14 mol%, or 12 mol%.

[0219] In an embodiment, the precursor glass or glass-ceramic composition may include B2O3. The addition of B2O3 may increase the elastic modulus of the precursor glass and the resulting glass-ceramic. B2O3 may also generally reduce the diffusivity during ion exchange. However, while not wishing to be bound by theory, it is believed that B2O3 is present in a crystalline phase on the glass-ceramic described herein, thereby resulting in a relatively high diffusivity during ion exchange compared to a glass-ceramic having B2O3 present in the glass phase. In embodiments, the concentration of B2O3 in the precursor glass or glass-ceramic composition can be greater than or equal to 0 mol%, such as a positive amount, such as greater than the amount of the impurity (0.05 mol% or more), to less than or equal to 10 mol%, greater than or equal to 0 mol% to less than or equal to 8 mol%, greater than or equal to 0 mol% to less than or equal to 6 mol%, greater than or equal to 0 mol% to less than or equal to 4 mol%, greater than or equal to 0 mol% to less than or equal to 2 mol%, greater than or equal to 0 mol% to less than or equal to 1 mol%, greater than or equal to 1 mol% to less than or equal to 10 mol%, greater than or equal to 1 mol% to less than or equal to 8 mol%, greater than or equal to 1 mol% to less than or equal to 6 mol%, greater than or equal to 1 mol% to less than or equal to 1 mol%. % to less than or equal to 10 mol %, greater than or equal to 2 mol % to less than or equal to 8 mol %, greater than or equal to 2 mol % to less than or equal to 6 mol %, greater than or equal to 2 mol % to less than or equal to 4 mol %, greater than or equal to 4 mol % to less than or equal to 10 mol %, greater than or equal to 4 mol % to less than or equal to 8 mol %, greater than or equal to 4 mol % to less than or equal to 6 mol %, greater than or equal to 6 mol % to less than or equal to 10 mol %, greater than or equal to 6 mol % to less than or equal to 8 mol %, or even greater than or equal to 8 mol % to less than or equal to 10 mol %, or any and all subranges formed by any of these endpoints. In embodiments, the precursor glass or glass-ceramic composition can be substantially free of B2O3.

[0220] Reference again Fig.10 , 30 and 31. According to one aspect of the present disclosure, at a thickness disclosed herein, such as 0.6 mm, the glass-ceramic disclosed herein transmits light at a total transmittance greater than 30%, such as greater than 40%, such as greater than 50% over the visible spectrum between wavelengths of 380 and 700 nm. Some glass-ceramics are translucent, as marked herein, and, for example, at Fig.31GC23 is shown in FIG. 1 , for example, having a total transmittance of greater than 80% over most of the visible spectrum. According to one aspect, the glass-ceramic disclosed herein transmits light so that a band of light between 380 and 700 nm wavelengths (e.g., 10 nm wide, 50 nm wide, 100 nm wide) has a total transmittance of greater than 70%, such as greater than 80%, greater than 85%, about 90% at the above thickness, such as Fig.31 As shown. Similarly, the glass-ceramic includes a band between 700nm and 1400nm (e.g., 10nm wide, 50nm wide, 100nm wide) with a total transmittance greater than 70%, such as greater than 80%, greater than 85%, about 90%. According to one aspect, at a wavelength of 400nm, at a thickness disclosed herein (e.g., 0.6mm), the glass-ceramic exhibits a diffuse transmission of less than 30%, such as less than 25%, such as less than 20%, such as less than 10%, about 5%. According to one aspect, at a wavelength of 700nm, at a thickness disclosed herein (e.g., 0.6mm), the glass-ceramic exhibits a scattering ratio of less than 30%, such as less than 25%, such as less than 20%, such as less than 10%, about 5%.

[0221] In embodiments, the resulting glass-ceramic may be colored. The colored glass-ceramic article may include at least one colorant in a colorant package, which is used to impart the desired color to the glass-ceramic. The colorant package may include at least one of Au, Ag, Cr2O3, transition metal oxides (e.g., CuO, NiO, CoO, Co3O4, TiO2, Cr2O3, V2O5, and MnO), rare earth metal oxides (e.g., CeO2), and / or combinations thereof as the colorant in the colorant package. In embodiments, the concentration of the colorant (e.g., any of the above oxides, but more than one colorant having such a concentration may be included in the mixture) in the precursor glass or glass-ceramic composition may be greater than or equal to 1x10 -6 mol % (where x in this usage means x or "times"), greater than or equal to 1x10 -5 mol%, greater than or equal to 1x10 -4 mol %, greater than or equal to 0.001 mol %, greater than or equal to 0.01 mol %, or even greater than or equal to 0.1 mol %; and / or can be less than or equal to 10 mol %, less than or equal to 5 mol %, less than or equal to 3 mol %, less than or equal to 2 mol %, less than or equal to 1 mol %, less than or equal to 0.5 mol %, less than or equal to 0.1 mol %, or even less than or equal to 0.01 mol %, or any and all subranges formed by any of these endpoints, for example, the concentration of the colorant in the precursor glass or glass-ceramic composition can be greater than or equal to 1×10 -6 mol % to less than or equal to 2 mol %.

[0222] In embodiments, the CIELAB color space coordinates L*, a*, and b* can be used to describe the color of the glass-ceramic, for example, which can be controlled at least in part by the amount of colorant in the batch. In embodiments, the value of L* can be greater than or equal to 0, greater than or equal to 20, greater than or equal to 40, greater than or equal to 60, or even greater than or equal to 80, 85, 90, 95, 96, 97, 98, or even greater than or equal to 99, and / or the value of L* can be less than or equal to 100, less than or equal to 80, less than or equal to 60, less than or equal to 40, or even less than or equal to 20, 99, 98, 97, 96, 95, 90, or even less than or equal to 85, or any and all subranges formed by any of these endpoints. In embodiments, the CIELAB coordinates may have values ​​of a* and / or b* that are each or both greater than or equal to -128, greater than or equal to -120, greater than or equal to -100, greater than or equal to -80, greater than or equal to -60, greater than or equal to -40, greater than or equal to -20, greater than or equal to 0, greater than or equal to 20, greater than or equal to 40, greater than or equal to 60, greater than or equal to 80, greater than or equal to 100, or even greater than or equal to 120, and / or the values ​​of a* and / or b* may be less than or equal to 127, less than or equal to 120, less than or equal to 100, less than or equal to 80, less than or equal to 60, less than or equal to 40, less than or equal to 20, less than or equal to 0, less than or equal to -20, less than or equal to -40, less than or equal to -60, less than or equal to -80, less than or equal to -100, or even less than or equal to -120, or any combination thereof; for example, a* is greater than or equal to -128 to less than or equal to 127, and b* is greater than or equal to -128 to less than or equal to 100, and L* is greater than 20 and less than 99, or any and all subranges formed by any of these endpoints.

[0223] In embodiments, the precursor glass or glass-ceramic composition may include other components, such as chemical fining agents. Such fining agents include, but are not limited to, SnO2, As2O3, Sb2O3, F, Cl, and Br. In some embodiments, the concentration of the chemical fining agent is maintained at a level of 3, 2, 1, or 0.5, >0 mol%. In embodiments, the precursor glass or glass-ceramic composition may be substantially free of chemical fining agents.

[0224] In embodiments, the precursor glasses or glass-ceramic compositions described herein allow for relatively rapid ion exchange. Without being bound by any particular theory, applicants believe that the exceptionally high ion exchange rates can be attributed at least in part to local tensions within the residual glass generated as crystals form and shrink, which pull the molecular network apart for faster exchange. For example, in embodiments, the glass-ceramic composition is heated to 400°C in a Na 2 O 4 salt bath.+ K + The diffusion rate during ion exchange can be greater than or equal to 200 μm 2 / hour, greater than or equal to 250μm 2 / hour, greater than or equal to 300μm 2 / hour, greater than or equal to 350μm 2 / hour, greater than or equal to 400μm 2 / hour, greater than or equal to 450μm 2 / hour, or even greater than or equal to 500 μm 2 In an embodiment, the glass-ceramic composition is heated to 550°C in a salt bath containing Na + K + The diffusion rate during ion exchange can be greater than or equal to 1500 μm 2 / hour, greater than or equal to 1550μm 2 / hour, greater than or equal to 1600μm 2 / hour, greater than or equal to 1650μm 2 / hour, greater than or equal to 1700μm 2 / hour, or even greater than or equal to 1750 μm 2 / Hour.

[0225] As used herein, "depth of layer" (DOL) refers to the depth in a glass article at which ions of a metal oxide diffuse into the glass article, where the concentration of the ions reaches a minimum. The DOL values ​​given herein are calculated from diffusivity measurements, but may also be measured by a surface stress meter (FSM). In embodiments, the precursor glass and / or glass-ceramic may be ion exchanged to obtain a depth of layer greater than or equal to 5%, greater than or equal to 10%, greater than or equal to 20%, or even greater than or equal to 30% of the thickness of the article formed from the precursor glass and / or glass-ceramic.

[0226] It should be understood that various shapes of glass-ceramic articles are contemplated and possible. For example, the glass-ceramic article may not include a rod, fiber, boule, curved sheet, tube, bowl, lens, vial, bottle or other container.

[0227] In embodiments, the precursor glass or glass-ceramic composition may be powdered to allow for the formation of a sintered body.

[0228] In embodiments, the glass-ceramic article may include or be incorporated into a laminate or layered product.Glass-ceramics in porous or powder form may be incorporated into composite materials, such as polymer composites.

[0229] According to one aspect of the present disclosure, applicants contemplate that the glasses and glass-ceramics disclosed herein can be formed into sheets having major surfaces and edges extending therebetween and defining a perimeter of the sheet (see generally Fig. 8A In the subject 201, Figure 8B According to one aspect, the thickness between the major surfaces of the sheet (see generally Figure 8B The thickness T) in the sheet varies very little, so that the difference between the maximum and minimum values ​​of the thickness of the entire sheet is close to zero, or as close to zero as possible, while still being measurable according to ASTM F657. This high level of geometric consistency is achievable for sheets with small surface areas, for example, by careful polishing. However, according to one aspect, for sheets having the same surface area as described above, Fig. 8A and 8B Discussion of geometrically consistent sheets, at least some of the major surfaces of the sheets formed from the glasses and glass-ceramics disclosed herein have at least some total thickness variation therebetween, e.g., greater than 0.1 μm, greater than 0.2 μm, greater than 0.5 μm, greater than 1 μm, and / or less than 1 mm, e.g., less than 500 μm, e.g., less than 200 μm. For example, such sheets can have a total thickness variation of greater than 0.1 μm and / or less than 1 mm (or other such values ​​as just disclosed and controllable by polishing), and also have one or more of the following three types of geometric properties in the same sheet, depending on how the glass or glass-ceramic is formed or cut: (1) having a total area greater than 25 mm 2 And not more than 10,000m 2 (1) having a volume greater than 25 mm 3 And no more than 100m 3 and (3) a surface-to-surface dimension greater than 5 mm and less than 5 km extending through the geometric centroid of the article.

[0230] According to one aspect, the sheet may be circular with a single continuous edge forming a perimeter between its major surfaces. However, according to one aspect, the sheet may have corners (or vertices) separating the perimeter to form different sides of the sheet, e.g. Fig. 8AFour-sided sheet shown. The corner of a glass or glass-ceramic sheet can be a sharp geometric intersection of two lines corresponding to the edge of the periphery, forming a clear point or vertex, which can be achieved by very fine polishing close to the atomic level. Or according to one aspect, at least one or more corners of a sheet or other glass or glass-ceramic product as disclosed herein can be blunted, such as rounded or rounded. "Passivation" as used herein refers to a geometric shape that is not ideally sharp (or in terms of geometry, the curvature does not include discontinuities at, for example, corners or vertices). This blunted corner can be rounded to have a constant radius of curvature, or can be rounded to have a variable radius. In other aspects, the blunted corners of a sheet or other glass or glass-ceramic product can be passivated by chamfering (e.g., chamfering). For example, making the corner of a sheet blunt can make the processing of the sheet easier. Similarly, according to one aspect, all edges between the main surfaces of a sheet or other glass or glass-ceramic product form sharp / ideal right angles relative to the corresponding main surface, and the side edges are almost completely straight and completely at right angles to the main surface. However, according to one aspect, the edges may also be blunted, for example rounded, beveled or radiused.

[0231] Similarly, according to one aspect, glass or glass-ceramic articles other than sheets (e.g., tubes, containers, spheres, glass-filled industrial glass melting furnace tanks, rolled sheets or strips) can be cut, polished or formed to have such geometric properties, such as a combination of the total thickness variation disclosed above and one or more of the following properties: (1) having a total area greater than 5 cm 2 Not more than 1,000m 2 (1) having a volume greater than 50 mm 3 Not more than 1m 3 and (3) a surface-to-surface dimension extending through the geometric centroid of the article that is greater than 5 cm and less than 5 m. As described above, one aspect of the present disclosure also includes articles of the presently disclosed glass or glass-ceramic, such as powders, microspheres, having a diameter less than 25 mm. 2 surface area and / or less than 25mm 3 Similarly, other glass or glass-ceramic articles, such as lenses or kitchen utensils having complex geometries, may intentionally include thickness variations greater than 1 mm, but may have any combination of the other geometric attributes described above.

[0232] In an embodiment, the glass or glass-ceramic can be coated with conductive carbon. According to one aspect, the glass or glass-ceramic disclosed herein can be coated with an organic substance (e.g., except 100% pure conductive carbon), such as a carbon-based polymer chain, and / or another coating, such as an oxide, nitride, sulfide, metal, etc. The coating may include, for example, a polymer, such as an epoxy resin, an acrylic resin, a urethane, a silicone, a phenolic resin, a polycarbonate, etc. In many uses, the coating may include a thickness greater than 20nm (e.g., measured by a cross section), such as greater than 50nm, such as greater than 100nm, and / or not greater than 50μm. Other coatings thinner than 20nm, such as coatings deposited by atomic layer deposition, are also conceivable. According to one aspect, a method for manufacturing an article may include coating the glass or glass-ceramic disclosed herein, such as by sputtering, atomic layer deposition, spraying, vapor deposition, dip coating, etc. The coating may provide functional benefits to articles comprising glass or glass-ceramic, regardless of whether the article is in sheet form. For example, coatings can be used to improve scratch resistance, provide anti-reflective properties, modify the coefficient of friction, etc.

[0233] According to one aspect of the present disclosure, referring again to Figure 1 and 2, the device 100 includes glass, or more preferably includes a glass-ceramic disclosed herein. From the perspective of its volume, the glass or glass-ceramic can form a large part of the cover substrate 112 and / or the housing 102. For example, the cover substrate 112 may include a transparent glass-ceramic disclosed herein, and the housing 102 may include an opaque and / or colored glass-ceramic disclosed herein. The cover substrate 112 or other articles may be coated with, for example, an anti-reflective coating (i.e., reducing the reflection of visible light), an anti-scratch coating (i.e., improving scratch resistance) or other coatings. The cover substrate 112 or other articles may include decorations, such as paint or dyes. Similarly, the housing 102, which may include glass or glass-ceramic disclosed herein, may be coated or decorated. The cover substrate 112 or the housing 102 may be adhered or otherwise bonded to another part of the device 100, such as an electronic device, such as a display 110. According to one aspect, the glass, or more preferably, the glass-ceramic disclosed herein, is relatively close to at least some electrical components, such as within 10 cm, such as within 1 cm, within 0.5 cm, within 10 mm, and / or adjacent to or in direct contact with a controller, memory, and / or display. According to one aspect, the device 100 includes materials other than glass or glass-ceramic, such as metal (e.g., circuits, encasement, fasteners) and / or plastic, and the glass or glass-ceramic disclosed herein is coupled thereto directly (e.g., with an adhesive or fastener) or indirectly (e.g., through other elements, such as intermediate layers, guides, frames, or other features). According to one aspect, applicants contemplate that the glass or glass-ceramic disclosed herein can be bent or loaded in such a device 100 or assembly, wherein external forces are applied to the glass or glass-ceramic from different elements of the device, and the glass or glass-ceramic is thereby at least partially deformed in strain or bending. According to one aspect, the device 100 includes an antenna (generally see Figure 2 108), a conductive coil, a magnet, a wire, a circuit, an electronic speaker and / or a receiver (generally referred to as Figure 2 ), a port coupled to the housing 102 (generally seen as the elongated body on the front surface 104), an on / off switch (generally seen as the circle surrounding the square rectangle on the bottom side surface 108), a battery, a light source and / or other elements to which the glass or glass-ceramic disclosed herein can be close and provide support, such as protecting it from the external environment, wherein the glass or glass-ceramic serves as a cover substrate 112, the housing 102 and / or another element of the device 100, such as a printed circuit board, or an internal partition, or other uses.

[0234] According to one aspect of the present disclosure, before ceramicization, the glass disclosed herein can be clarified in the melting process and / or in the manufacturing process, for example, with a clarifier such as arsenic, antimony oxide, sodium sulfate, redox oxide and sodium chloride or other materials disclosed herein, from which many bubbles are removed so that the resulting solidified glass is relatively free of bubbles (i.e., the trapped bubbles have a diameter greater than about 1 / 16 inch, or> 1.5mm) and seeds (less than about 1 / 16 inch, or< 1.5mm diameter). According to one aspect, the articles disclosed herein (e.g., cover sheet, container, window, display glass sheet) can have less than 100 bubbles, for example, less than 10 bubbles, for example, less than 2 bubbles, for example, no bubbles. The articles disclosed herein can have less than 100 seeds with a diameter less than 1.5mm and greater than 20μm, for example, less than 10 such seeds, for example, less than 2 such seeds, for example, no, and / or at least one. However, other aspects of the present disclosure include foam products or porous products, which can have more seeds or bubbles. Although the glass and / or glass-ceramic disclosed herein can be relatively free of bubbles and seeds, the applicant expects that the glass and / or glass-ceramic may include at least one detectable seed, such as a seed having a diameter of less than 50 μm, such as less than 20 μm but greater than 20 nm, and / or a seed that can be detected using a microscope, for example. Similarly, the glass and glass-ceramic disclosed herein can be melted in a furnace, such as where the batch ingredients disclosed above are thoroughly melted and mixed to form the glass disclosed herein. Therefore, the glass and / or glass-ceramic disclosed herein may not contain unmelted batch particles having a maximum cross-sectional dimension (e.g., length, width, height, diameter) greater than 50 μm. However, the applicant expects that in some cases, the glass and glass-ceramic disclosed herein may include at least one unmelted batch particle, such as a batch particle having a maximum cross-sectional dimension less than 50 μm, such as less than 20 μm and / or greater than 20 nm.

[0235] According to one aspect of the present disclosure, the stacked object (for example, its sheet material) of glass disclosed herein or more preferably glass-ceramic can include interlayer material (for example, paper, polymer) to help separate the layers of glass or glass-ceramic from each other during transportation and handling. The stacked object can be placed in a crate consisting of a wooden pallet or other frameworks at least partially surrounding the stacked object. The sheets in the stacked object can be packaged close to each other, for example, within 1 cm of another sheet material. The stacked object can include at least 2 sheets, for example, at least 10 sheets.

[0236] ***

[0237] Example

[0238] In order to more readily understand the various embodiments, reference is made to the following examples, which are intended to illustrate the various embodiments of the glass-ceramics described herein.

[0239] Table 2 shows example precursor glass compositions AA-DH (in mol %).

[0240] Table 2

[0241]

[0242] Table 2 continued

[0243]

[0244]

[0245] Table 2 continued

[0246]

[0247]

[0248] Table 2 continued

[0249]

[0250] Table 2 continued

[0251]

[0252]

[0253] Table 2 continued

[0254]

[0255]

[0256] Table 2 continued

[0257]

[0258] Table 2 continued

[0259]

[0260]

[0261] Table 2 continued

[0262]

[0263]

[0264] Table 2 continued

[0265]

[0266] Table 2 continued

[0267]

[0268]

[0269] Table 2 continued

[0270]

[0271]

[0272] Table 2 continued

[0273]

[0274] Each sample is formed by melting a batch of constituent components to form a precursor glass having a specified composition. The molten precursor glass is then poured into a steel mold and cooled to form a disk. The disk of precursor glass is sliced ​​and then heat treated to form a glass-ceramic. The sample of glass-ceramic is approximately 1 cm thick (unless otherwise specified).

[0275] Measure the character of glass-ceramic, comprise crystallization phase, sample appearance, volume reduction % (i.e. shrinkage), precursor glass density, glass-ceramic (GC) density, density increase %, elastic modulus, shear modulus, Poisson's ratio, fracture toughness and Vickers hardness when crystallization phase, sample appearance, sample crystallization.Measure the crystallization phase of glass-ceramic by " Jeffbenite characterization method " described above.The ceramization scheme realizing glass-ceramic GC1-GC97 and the property separately of these glass-ceramics are shown in table 3-6.

[0276] When describing the appearance of the samples, the term "white" refers to a glass-ceramic that is white and opaque. The term "opal" refers to a glass-ceramic that is white and slightly translucent. The term "transparent opal" refers to a glass-ceramic that is white but more translucent. In addition, some of the samples listed in Tables 3-6 are transparent, such as glass-ceramics GC22 and GC23 formed from batch composition CX and batch composition CY, such as Fig.30 as shown in .

[0277] Tables 3-6 include several samples of glass-ceramics containing jeffbenite. Tables 3-6 also include comparative examples in which the crystalline phase does not contain jeffbenite. For example, some compositions in Tables 3-6 (i.e., batch compositions AE, BI, BN, etc.) contain ZrO2 as the crystalline phase and no jeffbenite is present.

[0278] Table 3

[0279]

[0280] Table 3 continued

[0281]

[0282]

[0283] Table 3 continued

[0284]

[0285] Table 3 continued

[0286]

[0287] Table 3 continued

[0288]

[0289]

[0290] Table 4

[0291]

[0292] Table 4 continued

[0293]

[0294]

[0295] Table 5

[0296]

[0297] Table 5 continued

[0298]

[0299] Table 5 continued

[0300]

[0301] Table 6

[0302]

[0303]

[0304] Table 6 continued

[0305]

[0306]

[0307] Table 6 continued

[0308]

[0309]

[0310] Table 6 continued

[0311]

[0312] Table 6 continued

[0313]

[0314] Table 6 continued

[0315]

[0316]

[0317] Table 6 continued

[0318]

[0319]

[0320] Table 6 continued

[0321]

[0322]

[0323] The lattice parameters of the glass-ceramics formed from the precursor glass compositions were determined according to the "Jeffbenite Characterization Method" described above. Table 7 gives the batch compositions, ceramization schemes, corresponding glass-ceramics and lattice parameters.

[0324] Table 7

[0325]

[0326] The XRD spectra of the glass-ceramic were obtained according to the "Jeffbenite Characterization Method" described above. The figure contains the XRD spectra of several glass-ceramic products. Fig.21 The XRD spectrum of the glass-ceramic GC19 in Table 7 is shown in FIG. Fig. 22 The XRD spectrum of the glass-ceramic GC2 in Table 7 is shown in FIG. Fig.23 FIG. 7 shows the XRD spectra of the glass-ceramic formed by heat treating the batch compositions AB shown in Table 7. Fig.24 The XRD spectrum of the glass-ceramic GC71 in Table 7 is shown in FIG. Fig.25 The XRD spectrum of the glass-ceramic GC20 in Table 7 is shown in FIG. Fig.26 The XRD spectrum of the glass-ceramic GC21 in Table 7 is shown in FIG. Fig. 27 The XRD spectrum of the glass-ceramic GC24 in Table 7 is shown in FIG.

[0327] Fig.28 The XRD spectrum of the glass-ceramic GC25 in Table 3 is shown in FIG. Fig.29 The XRD spectra of the glass-ceramic GC26 of Table 3 are shown in FIG. The glass-ceramics GC25 and GC26 of Table 3 both contain P2O5, which can improve the diffusion rate during the ion exchange process. The XRD spectra of the glass-ceramics GC25 and GC26 of Table 3 illustrate that jeffbenite can be formed in glass-ceramic articles containing P2O5.

[0328] Figure 3 The microstructure of glass-ceramic GC53 is depicted. Figure 4 The microstructure of glass-ceramic GC4 is depicted. Figure 3 Also depicted are ZrO2 crystals (lighter colored areas) in the microstructure of the glass-ceramic.

[0329] Samples of the glass-ceramic composition of batch composition AB were analyzed by high temperature X-ray diffraction (XRD). The samples were kept for one hour at each of the following temperatures: 800° C., 825° C., 850° C., 875° C., 900° C., 925° C., 950° C., 975° C., and 1000° C. The XRD spectra of the samples were obtained in the last fifteen minutes during which the samples were kept at the specific temperatures. Figure 5 The XRD spectrum is shown in Figure 2. High temperature XRD analysis indicates the stability range of various crystalline phases in the sample. Figure 5 As shown in FIG. 1 , the sample includes a crystalline phase having a jeffbenite crystalline structure and a tetragonal ZrO 2 crystalline phase.

[0330] The surface of glass-ceramic GC53 was observed by scanning electron microscopy (SEM). The sample appears translucent. In order to be able to image by SEM, the surface of the sample was etched in 0.5% HF for 10 seconds. Then, the conductive carbon coating on the sample was evaporated to reduce charging. SEM images of the sample surface were taken using a Hitachi SU70, 5kv scanning electron microscope. SEM images were obtained at magnifications of 5K to 150K. Figures 6A-6F The surface of the sample is shown. The magnification of the SEM micrographs is from 6A to 6F The grain size of the crystals in the sample was measured to be about 30 nm.

[0331] Reference now Figure 7 A sample of the precursor glass composition having the batch composition AP was heat treated at 780°C for 4 hours and at 850°C for 4 hours to form a glass-ceramic. The obtained glass-ceramic was then analyzed by X-ray diffraction to obtain Figure 7 Diffraction pattern shown in . Figure 7 The X-ray diffraction pattern shown in shows that a composition in which a portion of MgO is replaced by ZnO (in this case, 21.5% of MgO is replaced by ZnO) can still lead to the formation of a crystalline phase having a jeffbenite crystal structure without generating other crystalline phases when heat treated.

[0332] The sample formed by the composition of the batch composition AA was heat treated at 725°C for 4 hours and at 850°C for 4 hours to form glass-ceramic. The sample formed by the composition of the batch composition AA was heat treated at 775°C for 4 hours and at 850°C for 4 hours to form glass-ceramic. Polished parts with a size of 25mm x 25mm x0.6mm were made from the obtained glass-ceramic. Then these samples of glass-ceramic were ion exchanged in a bath of 100 wt % KNO3 at 450°C for 1 hour, 2 hours, 4 hours, 8 hours, 16 hours and 32 hours. The sample was then analyzed to determine the variation of the maximum surface compressive stress and the maximum center tension with the ion exchange time. The depth of layer DOL is also calculated based on the diffusivity measurement results, which is the percentage of the thickness of the glass-ceramic. The results are reported in Table 8.

[0333] Table 8

[0334]

[0335]

[0336] As shown in Table 8, maximum central tensions up to 187.08 MPa and maximum surface compressive stresses up to 690.57 MPa were achieved with different ion exchange times, indicating that the stress distribution in the glass-ceramic can be tailored to meet different performance criteria.

[0337] The transmittance of a polished sample of about 0.6 mm thick of a glass-ceramic composition of composition AA ceramicized at 725°C for 4 hours and at 850°C for 4 hours was measured using the following procedure. The transmittance measurements were performed on a Lambda 950 UV-Vis-NIR spectrophotometer manufactured by PerkinElmer Inc. (Waltham, Massachusetts, USA). In this example, the spectrophotometer used the following instrument settings: 150 mm integrating sphere; data interval 2 nm; detector switching at 860 nm (InGaAs to PMT); lamp switching at 340 nm; tungsten-halogen source; servoed InGaAs spectral bandwidth; InGaAs gain 15; InGaAs averaging time 0.4 seconds; PMT spectral bandwidth 3.5 nm; PMT averaging time 0.2 seconds; dual beam mode. For total transmittance (Total Tx), the sample was fixed at the integrating sphere entrance point. For diffuse transmittance (Diffuse Tx), the A reference reflective disk is used to allow on-axis light to leave the sphere and enter the light trap. A zero-offset measurement of the diffuse portion is performed without a sample to determine the efficiency of the light trap. To correct the diffuse transmittance measurement, the zero-offset contribution is subtracted from the sample measurement using the following formula: Diffuse Tx = Diffuse Reflectance 测量值 - (Zero offset * (Total Tx / 100)). For all wavelengths, the scatter ratio is measured as follows: (% Diffuse Tx / % Total Tx). Axial transmittance is also measured. Axial transmittance measurements are made using coaxial light exiting the integrating sphere through the exit port. Fig.10 The total transmittance of the glass-ceramic of Example A is plotted in FIG. Fig.11 The diffuse transmittance of the glass-ceramic is plotted in FIG. Fig.12 The axial transmittance of the glass-ceramic is plotted in Fig.13 The scattering ratio of the glass-ceramic is plotted in FIG.

[0338] The transmittance of five glass-ceramic articles was measured using the procedure described above. Table 9 lists the batch compositions, ceramization schemes, corresponding glass-ceramics and thicknesses.

[0339] Table 9.

[0340]

[0341] Fig.31 The total transmittance of each glass-ceramic in Table 9 is plotted in . Fig.32The diffuse transmittance of each glass-ceramic in Table 9 is plotted in FIG. Fig.33 The scattering ratio of each glass-ceramic in Table 9 is plotted in FIG. The following formula is used to calculate Fig.33 The scattering ratio given in: % scattering ratio = (% diffuse Tx / % total Tx) * 100.

[0342] The color coordinates of each glass-ceramic listed in Table 9 were determined using the following procedure. Color measurements were performed on a Lambda 950UV-Vis-NIR spectrophotometer manufactured by PerkinElmer Inc. (Waltham, Massachusetts, USA) as described above. Color coordinates are typically calculated using the weighted sum of object spectral transmittance, human eye "standard observer" spectral function, and illuminant power spectral distribution. The color coordinates of each sample are calculated based on the transmittance data obtained using three illuminants (illuminant CIE D65, illuminant CIE A, and illuminant CIE F2). Measurements were made using 2 ° and 10 ° observer angles, and a wavelength range of 770nm to 380nm (2nm intervals) was used. The first set of color coordinates was calculated using total transmittance data, and the second set of color coordinates was calculated using diffuse transmittance data from each glass-ceramic article listed in Table 9. Color measurements performed using total transmittance are included in Table 10 below. Color measurements performed using diffuse transmittance are included in Table 11 below. Tables 10 and 11 include CIE L*A*B* color space data as well as CIE Yxy color space data. It is noteworthy that the glass-ceramics in Tables 10 and 11 appear to be transparent.

[0343] Table 10. Colors calculated from total transmittance data

[0344]

[0345]

[0346]

[0347] Table 11. Colors calculated from diffuse transmittance data

[0348]

[0349]

[0350]

[0351] In addition to the foregoing examples and disclosures relating to glass-ceramics containing jeffbenite, as part of the art of exploring the currently disclosed precursor glass compositions and glass-ceramics formed therefrom, the following table provides additional compositions melted by the applicant as described herein, which correspond to the information disclosed herein and other samples disclosed and further described herein. These additional compositions are presented in mole % based on oxides and are listed in Table 12.

[0352] Table 12:

[0353]

[0354]

[0355] Table 12 continued

[0356]

[0357]

[0358] Table 12 continued

[0359]

[0360] Table 12 continued

[0361]

[0362]

[0363] Table 12 continued

[0364]

[0365]

[0366] Table 12 continued

[0367]

[0368] Table 12 continued

[0369]

[0370]

[0371] Table 12 continued

[0372]

[0373]

[0374] Table 12 continued

[0375]

[0376] Table 12 continued

[0377]

[0378]

[0379] Table 12 continued

[0380]

[0381] Table 12 continued

[0382]

[0383]

[0384] Table 12 continued

[0385]

[0386] Table 12 continued

[0387]

[0388] Table 12 continued

[0389]

[0390]

[0391] Table 12 continued

[0392]

[0393] Table 12 continued

[0394]

[0395]

[0396] Table 12 continued

[0397]

[0398] Table 12 continued

[0399]

[0400]

[0401] Table 12 continued

[0402]

[0403] Table 12 continued

[0404]

[0405] Table 12 continued

[0406]

[0407]

[0408] Table 12 continued

[0409]

[0410] Table 12 continued

[0411]

[0412]

[0413] Table 12 continued

[0414]

[0415] Table 12 continued

[0416]

[0417] Table 12 continued

[0418]

[0419]

[0420] Table 12 continued

[0421]

[0422] Table 12 continued

[0423]

[0424]

[0425] Table 12 continued

[0426]

[0427]

[0428] Table 12 continued

[0429]

[0430] Table 12 continued

[0431]

[0432]

[0433] Table 12 continued

[0434]

[0435]

[0436] Table 12 continued

[0437]

[0438] Table 12 continued

[0439]

[0440]

[0441] Table 12 continued

[0442]

[0443] Table 12 continued

[0444]

[0445] Table 12 continued

[0446]

[0447]

[0448] Table 12 continued

[0449]

[0450] Table 12 continued

[0451]

[0452]

[0453] Table 12 continued

[0454]

[0455] Table 12 continued

[0456]

[0457]

[0458] Table 12 continued

[0459]

[0460]

[0461] Table 12 continued

[0462]

[0463] Table 13 shows exemplary precursor glass compositions DI and DJ (in mol %) and glass-ceramics GC 102 and GC 103 obtained from exemplary precursor glass compositions DI and DJ by subjecting them to ceramic treatment procedures at 780°C for 4 hours and 850°C for 4 hours, respectively.

[0464] Table 13

[0465]

[0466] Table 14 shows the example precursor glass composition DK-DP (in mol %), the observable color of the precursor glass, and the observable color and appearance of the glass-ceramics GC104 to GC108, which were obtained by subjecting the example precursor glass composition DK-DP to ceramic treatment procedures at 780°C for 4 hours and 850°C for 4 hours, respectively.

[0467] Table 14

[0468]

[0469]

[0470] Fig.34 and 35The variation of the molar percentage of oxide with depth for glass-ceramics GC 22 and GC 23 having a thickness of 0.6 mm after ion exchange in a 95 wt % KNO 3 and 5 wt % NaNO 3 bath at 550° C. for 0.5 hour is shown.

[0471] The entirety of U.S. application No. 63 / 309,667 filed on February 14, 2022, U.S. application No. 17 / 887,012 filed on August 12, 2022, U.S. application No. 63 / 444,715 filed on February 10, 2023, U.S. application No. 63 / 449,498 filed on March 2, 2023, U.S. application No. 63 / 449,394 filed on March 2, 2023, U.S. application No. 63 / 326,308 filed on April 1, 2022, U.S. application No. 63 / 420,952 filed on October 31, 2022, U.S. application No. 63 / 428,773 filed on November 30, 2022, and U.S. application No. 63 / 530,542 filed on August 3, 2023 are hereby incorporated by reference.

[0472] It is obvious to those skilled in the art that various modifications and changes may be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Therefore, this specification is intended to cover modifications and changes of the various embodiments described herein, as long as such modifications and changes fall within the scope of the appended claims and their equivalents.

[0473] This application also includes the following implementation schemes:

[0474] Embodiment 1. A glass-ceramic comprising glass and crystals therein, wherein the crystals include a jeffbenite crystalline structure.

[0475] Embodiment 2. A product, comprising:

[0476] Surface; and

[0477] a body inside said surface,

[0478] wherein the body comprises the glass-ceramic according to Embodiment 1.

[0479] Embodiment 3. The article of embodiment 2, wherein the surface is a first surface, the article further comprising a second surface facing away from the first surface, wherein the body is located between the first and second surfaces, such that the article is a sheet.

[0480] Embodiment 4. A method of making a material, the method comprising growing crystals comprising a jeffbenite crystalline structure in an ambient environment at a pressure below 10 GPa.

[0481] Embodiment 5. A method according to Embodiment 4, wherein the growth is performed at a temperature of the crystal and / or the surrounding environment below 1400K.

[0482] Embodiment 6. The method of Embodiment 4, wherein the crystals grow within the glass to form a glass-ceramic.

[0483] Embodiment 7. A glass-ceramic article, comprising:

[0484] Surface; and

[0485] A phase combination within the surface, the phase combination comprising one or more crystalline phases and a glass phase, the one or more crystalline phases including a crystalline phase comprising a jeffbenite crystal structure.

[0486] Embodiment 8. The glass-ceramic article of Embodiment 7, wherein the crystalline phase comprising the jeffbenite crystal structure is the main crystalline phase.

[0487] Embodiment 9. The glass-ceramic article of any one of Embodiments 7 to 8, wherein the phase combination comprises greater than or equal to 25 weight percent of the one or more crystalline phases and less than or equal to 75 weight percent of the glass phase.

[0488] Embodiment 10. The glass-ceramic article of any one of Embodiments 7 to 9, wherein at least some of the grains of the crystalline phase comprising the jeffbenite crystal structure have a maximum dimension of greater than or equal to 20 nm to less than or equal to 100 nm.

[0489] Embodiment 11. The glass-ceramic article of any one of Embodiments 7 to 10, wherein the glass-ceramic article is substantially free of lithium.

[0490] Embodiment 12. The glass-ceramic article of any one of Embodiments 7 to 11, wherein the crystalline phase comprising the jeffbenite crystal structure has a composition according to the formula:

[0491] (Mg,R 2+ ) 3+x (Zr,R 4+ ) x Al 2-2x SiO 12 ,

[0492] Where R 2+ represents one or more divalent metal cations, R 4+ represents one or more tetravalent metal cations, and x is greater than or equal to 0 and less than or equal to 1.

[0493] Embodiment 13. The glass-ceramic article of embodiment 12, wherein R 2+ is selected from Ca 2+ , Mn 2+ , Fe 2 + 、Zn 2+ one or more divalent metal cations, and wherein R 4+ Selected from Ti 4+ Sn 4+ , Hf 4+ One or more tetravalent metal cations.

[0494] Embodiment 14. The glass-ceramic article of any one of Embodiments 7 to 13, wherein the glass-ceramic article has an average transmittance of at least 75% for light in the wavelength range of 400 nm to 800 nm at an article thickness of 0.6 mm.

[0495] Embodiment 15. A glass-ceramic article, in mole percent (mol %) based on oxides, comprising:

[0496] 35 mol% or more and 65 mol% or less of SiO2;

[0497] 5 mol% or more and 20 mol% or less of Al2O3;

[0498] 7 mol% or more and 65 mol% or less of MgO;

[0499] 0 mol % or more and 7 mol % or less of ZrO2;

[0500] 0 mol % or more and 15 mol % or less of Na2O;

[0501] 0 mol % or more and 15 mol % or less of K2O;

[0502] 0 mol % or more and 9 mol % or less of FeO;

[0503] 0 mol % or more and 10 mol % or less of MnO2; and

[0504] 0 mol % or more and 15 mol % or less of ZnO;

[0505] The glass-ceramic comprises a phase combination comprising one or more crystalline phases and a glass phase, wherein the one or more crystalline phases include a crystalline phase comprising a jeffbenite crystal structure.

[0506] Embodiment 16. The glass-ceramic article of Embodiment 15, further comprising less than or equal to 3 mol % Li2O.

[0507] Embodiment 17. The glass-ceramic article of Embodiment 15, wherein the glass-ceramic article is substantially free of Li2O.

[0508] Embodiment 18. The glass-ceramic article of any one of Embodiments 15 to 17, wherein the glass-ceramic article comprises greater than or equal to 1.5 mol % and less than or equal to 3 mol % ZrO2.

[0509] Embodiment 19. The glass-ceramic article of any one of Embodiments 15 to 18, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 12 mol % HfO2, wherein the sum of ZrO2 and HfO2 is greater than 1 mol %.

[0510] Embodiment 20. The glass-ceramic article of any one of Embodiments 15 to 19, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 15 mol % CaO.

[0511] Embodiment 21. The glass-ceramic article of any one of Embodiments 15 to 20, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 4 mol % P2O5.

[0512] Embodiment 22. The glass-ceramic article of any one of Embodiments 15 to 21, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 7 mol % La2O3.

[0513] Embodiment 23. The glass-ceramic article of any one of Embodiments 15 to 22, wherein Na2O (mol%) + K2O (mol%) is greater than, or equal to, 2 mol% and less than, or equal to, 15 mol%.

[0514] Embodiment 24. The glass-ceramic article of any one of Embodiments 15 to 23, wherein Na2O (mol%) / (Na2O (mol%) + K2O (mol%)) is greater than or equal to 0.2.

[0515] Embodiment 25. The glass-ceramic article of any one of Embodiments 15 to 24, further comprising greater than or equal to 0.3 mol % to less than or equal to 7 mol % TiO2.

[0516] Embodiment 26. The glass-ceramic article of any one of Embodiments 15 to 25, wherein ZrO2 (mol %) + TiO2 (mol %) is greater than or equal to 2 mol %.

[0517] Embodiment 27. The glass-ceramic article of any one of Embodiments 15 to 26, wherein ZrO2 (mol%) / (ZrO2 (mol%) + TiO2 (mol%)) is greater than or equal to 0.3.

[0518] Embodiment 28. The glass-ceramic article of any one of Embodiments 15 to 27, comprising greater than or equal to 1 mol % to less than or equal to 12 mol % ZnO.

[0519] Embodiment 29. The glass-ceramic article of any one of Embodiments 15 to 28, further comprising greater than or equal to 1 mol % to less than or equal to 8 mol % BaO.

[0520] Embodiment 30. The glass-ceramic article of any one of Embodiments 15 to 29, further comprising 0.2 mol % or more and 1.7 mol % or less of at least one of CaO and SrO.

[0521] Embodiment 31. A method of making a glass-ceramic article, the method comprising:

[0522] thermally treating a precursor glass comprising SiO2, Al2O3, and MgO to nucleate one or more crystalline phases in the precursor glass, wherein the one or more crystalline phases include a crystalline phase comprising a jeffbenite crystalline structure; and

[0523] The one or more crystalline phases are grown in the glassy phase.

[0524] Embodiment 32. A method for making a glass-ceramic article according to Embodiment 31, wherein the heat treatment comprises:

[0525] heating the precursor glass in an environment of 700° C. or more and 950° C. or less; and

[0526] The precursor glass is maintained in the environment for a first time greater than or equal to 0.25 hours and less than or equal to 6 hours.

[0527] Embodiment 33. The method for making a glass-ceramic article according to Embodiment 32, wherein the heat treatment further comprises:

[0528] Heating the precursor glass in an environment of 750° C. or more and 950° C. or less; and

[0529] The precursor glass is maintained in the environment for a second time of greater than or equal to 0.25 hours and less than or equal to 6 hours.

[0530] Embodiment 34. A glass-ceramic sheet, comprising:

[0531] a first major surface and a second major surface opposite the first major surface, an edge forming a perimeter of the first and second major surfaces and extending between the first and second major surfaces; wherein the thickness of the article is defined as the distance between the first and second major surfaces, the width of the article is defined as the distance orthogonal to the thickness and along the first major surface between the edges, and the length of the article is defined as the distance orthogonal to both the width and thickness and along the first major surface between the edges;

[0532] wherein the width is greater than or equal to the thickness;

[0533] wherein said length is greater than or equal to said width; and

[0534] A body between the first major surface, the second major surface, and the edge, wherein the body comprises a glass-ceramic, wherein the glass-ceramic comprises a crystalline phase having a jeffbenite crystal structure.

[0535] Embodiment 35. The glass-ceramic sheet of Embodiment 34, wherein the grains of the crystalline phase having the jeffbenite crystal structure are uniformly distributed throughout the glass-ceramic of the body.

[0536] Embodiment 36. The glass-ceramic sheet of Embodiment 34 or Embodiment 35, wherein the grains of the crystalline phase having the jeffbenite crystal structure are randomly oriented within the glass-ceramic of the host.

[0537] Embodiment 37. A glass-ceramic sheet according to any one of Embodiments 34 to 36, wherein the grains of the crystalline phase having the jeffbenite crystal structure overlap and interlock with each other within the glass-ceramic of the body to achieve a fracture toughness of 0.75 MPa·m 1 / 2 or a higher degree.

[0538] Embodiment 38. The glass-ceramic sheet of any one of Embodiments 34 to 37, wherein the glass-ceramic has isotropic material properties.

[0539] Embodiment 39. The glass-ceramic sheet of any one of Embodiments 34 to 38, wherein the thickness is greater than, or equal to, 200 μm and less than, or equal to, 5 mm, wherein both the length and the width are greater than 5 mm.

[0540] Embodiment 40. A method of making a glass-ceramic, the method comprising:

[0541] heat treating a precursor glass containing nucleation sites to grow grains of a crystalline phase having a jeffbenite crystalline structure from the nucleation sites within the precursor glass, thereby forming a glass-ceramic containing the crystalline phase having a jeffbenite crystalline structure and residual glass; and

[0542] The grains of the crystalline phase having the jeffbenite crystalline structure are grown during the heat treatment so that at least some of the grains of the crystalline phase having the jeffbenite crystalline structure have a size greater than or equal to 20 nm.

[0543] Embodiment 41. A method according to Embodiment 40, wherein the growing is carried out at atmospheric pressure.

[0544] Embodiment 42. A method according to Embodiment 40 or Embodiment 41, wherein after the growing, at least some grains of the crystalline phase having the jeffbenite crystal structure have a size less than or equal to 5 μm.

[0545] Embodiment 43. A glass-ceramic article comprising:

[0546] Crystals of pyrope-almandine garnet stoichiometry having a tetragonal structure; and

[0547] Amorphous glass surrounds and encapsulates the crystals such that the crystals and glass together form the glass-ceramic of the glass-ceramic article.

[0548] Embodiment 44. The glass-ceramic article of Embodiment 43, wherein the tetragonal structure falls within the 1-42d space group.

[0549] Embodiment 45. A glass-ceramic article comprising:

[0550] Greater than or equal to and less than or equal to The "a" lattice parameter of

[0551] Greater than or equal to and less than or equal to The "c" lattice parameter; and

[0552] Contains the following X-ray diffraction spectra:

[0553] The first peak with a 2θ angle between 30° and 32°;

[0554] a second peak with a 2θ angle between 33° and 35°;

[0555] A third peak with a 2θ angle between 40° and 42°; and

[0556] The fourth and fifth peaks with 2θ angles between 55° and 58°,

[0557] Wherein the first, second, third, fourth and fifth peaks correspond to jeffbenite.

[0558] Embodiment 46. A glass-ceramic comprising a glass phase and one or more crystalline phases, wherein at least one of the one or more crystalline phases comprises jeffbenite.

[0559] Embodiment 47. An article comprising:

[0560] Surface; and

[0561] a body inside said surface,

[0562] wherein the body comprises the glass-ceramic according to Embodiment 46.

[0563] Embodiment 48. An article according to embodiment 47, wherein the surface is a first surface, and the article further includes a second surface opposite to the first surface, wherein the body is located between the first and second surfaces, so that the article is a sheet.

[0564] Embodiment 49. A glass-ceramic article comprising:

[0565] a first surface;

[0566] a second surface opposite to the first surface;

[0567] a perimeter defining the shape of the glass-ceramic article; and

[0568] A phase combination comprising one or more crystalline phases and a glassy phase, the one or more crystalline phases including a crystalline phase comprising a jeffbenite crystal structure.

[0569] Embodiment 50. A glass-ceramic article according to Embodiment 49, wherein the crystalline phase comprising the jeffbenite crystal structure is the main crystalline phase.

[0570] Embodiment 51. A glass-ceramic article according to Embodiment 49 or Embodiment 50, wherein the phase combination comprises greater than or equal to 10 weight percent to less than or equal to 85 weight percent of the one or more crystalline phases and greater than or equal to 15 weight percent to less than or equal to 90 weight percent of the glass phase, based on the weight of the glass-ceramic article.

[0571] Embodiment 52. A glass-ceramic article according to any one of Embodiments 49 to 51, wherein the amount of jeffbenite crystalline structure in the one or more crystalline phases is greater than or equal to 90 weight percent and less than or equal to 100 weight percent, based on the total weight of the one or more crystalline phases.

[0572] Embodiment 53. The glass-ceramic article of any one of Embodiments 49 to 52, wherein at least some of the grains of the at least one crystalline phase comprising the jeffbenite crystalline structure have a maximum dimension of greater than or equal to 20 nm to less than or equal to 500 nm.

[0573] Embodiment 54. The glass-ceramic article of any one of Embodiments 49 to 53, wherein the glass-ceramic article is substantially free of lithium.

[0574] Embodiment 55. The glass-ceramic article of any one of Embodiments 49 to 54, wherein the crystalline phase comprising the jeffbenite crystal structure has a composition according to the formula:

[0575] (Mg,R 2+ ) 3+x (Zr,R 4+ ) x Al 2-2x SiO 12 ,

[0576] Where R 2+ represents one or more divalent metal cations, R 4+ represents one or more tetravalent metal cations, and x is greater than or equal to 0 and less than or equal to 1.

[0577] Embodiment 56. The glass-ceramic article of embodiment 55, wherein R 2+ is selected from Ca 2+ , Mn 2+ , Fe 2 + 、Zn 2+ one or more divalent metal cations, and wherein R 4+ Selected from Ti 4+ Sn 4+ , Hf 4+One or more tetravalent metal cations.

[0578] Embodiment 57. The glass-ceramic article of any one of Embodiments 49 to 56, wherein the glass-ceramic article has an average transmittance of at least 75% for light in the wavelength range of 400 nm to 800 nm at an article thickness of 0.6 mm.

[0579] Embodiment 58. The glass-ceramic article of any one of Embodiments 49 to 56, wherein the glass-ceramic article has an average transmittance in a range of 20% to less than 75% for light in the wavelength range of 400 nm to 800 nm at an article thickness of 0.6 mm.

[0580] Embodiment 59. The glass-ceramic article of any one of Embodiments 49 to 56, wherein the glass-ceramic article has an average transmittance in the range of less than 20% for light in the wavelength range of 400 nm to 800 nm at an article thickness of 0.6 mm.

[0581] Embodiment 60. A glass-ceramic article, in mole percent (mol %) based on oxides, comprising:

[0582] 35 mol% or more and 65 mol% or less of SiO2;

[0583] 2.5 mol% or more and 20 mol% or less of Al2O3;

[0584] 7 mol% or more and 65 mol% or less of MgO;

[0585] 0 mol % or more and 10 mol % or less of CaO;

[0586] 0 mol % or more and 5 mol % or less of B2O3;

[0587] 0 mol % or more and 7 mol % or less of ZrO2;

[0588] 0 mol % or more and 15 mol % or less of Na2O;

[0589] 0 mol % or more and 15 mol % or less of K2O;

[0590] 0 mol % or more and 9 mol % or less of FeO;

[0591] 0 mol % or more and 10 mol % or less of MnO2; and

[0592] 0 mol % or more and 15 mol % or less of ZnO;

[0593] The glass-ceramic comprises a phase combination comprising one or more crystalline phases and a glass phase, wherein the one or more crystalline phases include a crystalline phase comprising a jeffbenite crystal structure.

[0594] Embodiment 61. The glass-ceramic article of Embodiment 60, further comprising less than or equal to 3 mol % Li2O.

[0595] Embodiment 62. The glass-ceramic article of Embodiment 60, wherein the glass-ceramic article is substantially free of Li2O.

[0596] Embodiment 63. The glass-ceramic article of any one of Embodiments 60 to 62, wherein the glass-ceramic article comprises greater than or equal to 1.5 mol % and less than or equal to 3 mol % ZrO2.

[0597] Embodiment 64. A glass-ceramic article according to any one of Embodiments 60 to 63, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 12 mol % HfO2, wherein the sum of ZrO2 and HfO2 is greater than 1 mol %.

[0598] Embodiment 65. The glass-ceramic article of any one of Embodiments 60 to 64, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 4 mol % P2O5.

[0599] Embodiment 66. The glass-ceramic article of any one of Embodiments 60 to 65, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 7 mol % La2O3.

[0600] Embodiment 67. The glass-ceramic article of any one of Embodiments 60 to 66, wherein Na2O (mol %) + K2O (mol %) is greater than, or equal to, 2 mol % and less than, or equal to, 15 mol %.

[0601] Embodiment 68. The glass-ceramic article of any one of Embodiments 60 to 67, wherein Na2O (mol %) / (Na2O (mol %) + K2O (mol %)) is greater than or equal to 0.2.

[0602] Embodiment 69. The glass-ceramic article of any one of Embodiments 60 to 68, further comprising greater than or equal to 0.3 mol % to less than or equal to 7 mol % TiO2.

[0603] Embodiment 70. The glass-ceramic article of any one of Embodiments 60 to 69, wherein ZrO2 (mol %) + TiO2 (mol %) is greater than or equal to 2 mol %.

[0604] Embodiment 71. The glass-ceramic article of any one of Embodiments 60 to 70, wherein ZrO2 (mol%) / (ZrO2 (mol%) + TiO2 (mol%)) is greater than or equal to 0.3.

[0605] Embodiment 72. The glass-ceramic article of any one of Embodiments 60 to 71, comprising greater than or equal to 1 mol % and less than or equal to 12 mol % ZnO.

[0606] Embodiment 73. The glass-ceramic article of any one of Embodiments 60 to 72, further comprising greater than or equal to 1 mol % and less than or equal to 8 mol % BaO.

[0607] Embodiment 74. The glass-ceramic article of any one of Embodiments 60 to 73, further comprising 0.2 mol% or more and 1.7 mol% or less of at least one of CaO and SrO.

[0608] Embodiment 75. The glass-ceramic article of any one of Embodiments 60 to 74, further comprising greater than or equal to 0 mol % and less than or equal to 0.2 mol % SnO2.

[0609] Embodiment 76. The glass-ceramic article according to any one of Embodiments 60 to 75, further comprising greater than or equal to 1×10 -6 mol % to less than or equal to 10 mol % of a colorant, the colorant comprising at least one of Au, Ag, Cr2O3, CuO, NiO, CoO, Co3O4, TiO2, Cr2O3, V2O5, MnO and CeO2.

[0610] Embodiment 77. The glass-ceramic article of Embodiment 76, wherein the glass-ceramic article comprises:

[0611] L* value greater than 0 and less than 100;

[0612] an a* value greater than -128 and less than 127; and

[0613] b* values ​​greater than -128 and less than 127.

[0614] Embodiment 78. The glass-ceramic article of any one of Embodiments 60 to 77, wherein the glass-ceramic article has an elastic modulus greater than or equal to 50 GPa and less than or equal to 200 GPa.

[0615] Embodiment 79. The glass-ceramic article of any one of Embodiments 60 to 78, wherein the glass-ceramic article has a strength of greater than or equal to 600 kgf / mm 2 To less than or equal to 1400kgf / mm 2 Vickers hardness.

[0616] Embodiment 80. The glass-ceramic article of any one of Embodiments 60 to 79, wherein the glass-ceramic article is an ion exchange glass-ceramic article.

[0617] Embodiment 81. The glass-ceramic article of Embodiment 80, wherein the glass-ceramic article is heated to 450°C in a salt bath containing Na + Ion pair K + Ion exchange process with a particle size greater than or equal to 200 μm 2 Diffusion rate / hour.

[0618] Embodiment 82. The glass-ceramic article of Embodiment 80 or Embodiment 81, wherein the glass-ceramic composition is molten in a 550°C salt bath. + Ion pair K + The ion exchange process can have a particle size greater than or equal to 1500 μm 2 Diffusion rate / hour.

[0619] Embodiment 83. The glass-ceramic article of any one of Embodiments 80 to 82, wherein the ion exchange glass-ceramic article has a compression depth of about 30 μm or greater.

[0620] Embodiment 84. The glass-ceramic article of any one of Embodiments 80 to 83, wherein the ion-exchange glass-ceramic article has a compression depth greater than or equal to 3% of the thickness of the ion-exchange glass-ceramic article.

[0621] Embodiment 85. The glass-ceramic article of any one of Embodiments 80 to 84, wherein the ion exchange glass-ceramic article has a central tension greater than or equal to 10 MPa and less than or equal to 200 MPa.

[0622] Embodiment 86. The glass-ceramic article of any one of Embodiments 80 to 85, wherein the ion exchange glass-ceramic article has a surface compressive stress greater than or equal to 100 MPa and less than or equal to 1 GPa.

[0623] Embodiment 87. A glass-ceramic article according to any of the preceding embodiments, an article comprising a glass-ceramic according to any of the preceding embodiments, and / or an article comprising a glass-ceramic manufactured according to any of the preceding embodiments, further comprising limitations, attributes, or features disclosed herein but not explicitly or inherently disclosed in International Application No. PCT / US2023 / 012905 filed on February 13, 2023.

[0624] Embodiment 88. The glass-ceramic article of any preceding Embodiment, wherein the article is a sheet having a total thickness variation greater than 0.1 μm and less than 1 mm.

[0625] Embodiment 89. The glass-ceramic article of any preceding Embodiment, wherein the article has rounded corners or edges.

[0626] Embodiment 90. The glass-ceramic article of any preceding Embodiment, wherein the article is coated with a coating other than conductive carbon.

[0627] Embodiment 91. The glass-ceramic article of any preceding Embodiment, wherein the article is coated and the coating has a thickness greater than 20 nm and less than 50 μm.

[0628] Embodiment 92. A device comprising the glass-ceramic article of any of the preceding embodiments adhered thereto.

[0629] Embodiment 93. A device comprising a curved glass-ceramic article according to any of the preceding embodiments.

[0630] Embodiment 94. A device comprising the glass-ceramic article of any of the preceding embodiments in a strain.

[0631] Embodiment 95. A device comprising the glass-ceramic article of any preceding embodiment positioned within 10 cm of an electronic component of the device.

[0632] Embodiment 96. A device comprising the glass-ceramic article of any of the preceding embodiments and an antenna.

Claims

1. A product comprising: surface; and a body inside said surface, wherein the body comprises a glass-ceramic comprising a glass phase and one or more crystalline phases, wherein at least one of the one or more crystalline phases comprises jeffbenite, The product is a sheet with a total thickness variation greater than 0.1 μm and less than 1 mm.

2. A product comprising: surface; and a body inside said surface, wherein the body comprises a glass-ceramic comprising a glass phase and one or more crystalline phases, wherein at least one of the one or more crystalline phases comprises jeffbenite, wherein the article is coated with a coating other than conductive carbon.

3. A product comprising: Surface; and a body inside said surface, wherein the body comprises a glass-ceramic comprising a glass phase and one or more crystalline phases, wherein at least one of the one or more crystalline phases comprises jeffbenite, wherein the article is coated and the coating has a thickness greater than 20 nm and less than 50 μm.

4. A glass-ceramic article, measured in mole percent (mol %) based on oxides, comprising: 35 mol% or more and 65 mol% or less of SiO2; 2.5 mol% or more and 20 mol% or less of Al2O3; 7 mol% or more and 65 mol% or less of MgO; 0 mol % or more and 10 mol % or less of CaO; 0 mol % or more and 5 mol % or less of B2O3; 0 mol % or more and 7 mol % or less of ZrO2; 0 mol % or more and 15 mol % or less of Na2O; 0 mol % or more and 15 mol % or less of K2O; 0 mol % or more and 9 mol % or less of FeO; 0 mol % or more and 10 mol % or less of MnO2; and 0 mol % or more and 15 mol % or less of ZnO; The glass-ceramic comprises a phase combination comprising one or more crystalline phases and a glass phase, wherein the one or more crystalline phases include a crystalline phase comprising a jeffbenite crystal structure.

5. The glass-ceramic article of claim 4, further comprising less than or equal to 3 mol% Li2O.

6. The glass-ceramic article of claim 4, wherein the glass-ceramic article is substantially free of Li2O.

7. The glass-ceramic article of claim 4, wherein the glass-ceramic article comprises greater than or equal to 1.5 mol % to less than or equal to 3 mol % ZrO2.

8. The glass-ceramic article of claim 4, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 12 mol % HfO2, wherein the sum of ZrO2 and HfO2 is greater than 1 mol %.

9. The glass-ceramic article of claim 4, wherein the glass-ceramic article comprises greater than 0 mol % to less than or equal to 4 mol % P2O5.

10. The glass-ceramic article of claim 4, wherein the glass-ceramic article comprises greater than 0 mol% to less than or equal to 7 mol% La2O3.

11. The glass-ceramic article of claim 4, wherein Na2O (mol%) + K2O (mol%) is greater than or equal to 2 mol% and less than or equal to 15 mol%.

12. The glass-ceramic article of claim 4, wherein Na2O (mol%) / (Na2O (mol%) + K2O (mol%)) is greater than or equal to 0.

2.

13. The glass-ceramic article of claim 4, further comprising greater than or equal to 0.3 mol% and less than or equal to 7 mol% TiO2.

14. The glass-ceramic article of claim 4, wherein ZrO2 (mol %) + TiO2 (mol %) is greater than or equal to 2 mol %.

15. The glass-ceramic article of claim 4, wherein ZrO2 (mol%) / (ZrO2 (mol%)+TiO2 (mol%)) is greater than or equal to 0.

3.

16. The glass-ceramic article of claim 4, comprising greater than or equal to 1 mol% and less than or equal to 12 mol% ZnO.

17. The glass-ceramic article of claim 4, further comprising greater than or equal to 1 mol% and less than or equal to 8 mol% BaO.

18. The glass-ceramic article of claim 4, further comprising greater than or equal to 0.2 mol% to less than or equal to 1.7 mol% of at least one of CaO and SrO.

19. The glass-ceramic article of claim 4, further comprising greater than or equal to 0 mol% and less than or equal to 0.2 mol% SnO2.

20. The glass-ceramic article according to claim 4, further comprising greater than or equal to 1×10 -6 mol % to less than or equal to 10 mol % of a colorant, the colorant comprising at least one of Au, Ag, Cr2O3, CuO, NiO, CoO, Co3O4, TiO2, Cr2O3, V2O5, MnO and CeO2.

21. The glass-ceramic article of claim 20, wherein the glass-ceramic article comprises: L* value greater than 0 and less than 100; an a* value greater than -128 and less than 127; and b* values ​​greater than -128 and less than 127.

22. The glass-ceramic article of claim 4, wherein the glass-ceramic article has an elastic modulus greater than or equal to 50 GPa and less than or equal to 200 GPa.

23. The glass-ceramic article of claim 4, wherein the glass-ceramic article has a strength of greater than or equal to 600 kgf / mm 2 To less than or equal to 1400kgf / mm 2 Vickers hardness.

24. The glass-ceramic article of claim 4, wherein the glass-ceramic article is an ion exchange glass-ceramic article.

25. The glass-ceramic article of claim 24, wherein the glass-ceramic article is heated to 450°C in a salt bath containing Na + Ion pair K + Ion exchange process with a particle size greater than or equal to 200 μm 2 Diffusion rate / hour.

26. The glass-ceramic article of claim 24 or claim 25, wherein the glass-ceramic composition is molten in a 550°C salt bath. + Ion pair K + The ion exchange process can have a particle size greater than or equal to 1500 μm 2 Diffusion rate / hour.

27. The glass-ceramic article of claim 24 or claim 25, wherein the ion exchange glass-ceramic article has a compression depth of about 30 μm or greater.

28. The glass-ceramic article of claim 24 or claim 25, wherein the ion-exchanged glass-ceramic article has a compression depth greater than or equal to 3% of the thickness of the ion-exchanged glass-ceramic article.

29. The glass-ceramic article of claim 24 or claim 25, wherein the ion exchange glass-ceramic article has a central tension greater than or equal to 10 MPa and less than or equal to 200 MPa.

30. The glass-ceramic article of claim 24 or claim 25, wherein the ion exchanged glass-ceramic article has a surface compressive stress greater than or equal to 100 MPa and less than or equal to 1 GPa.

Citation Information

Patent Citations

  • Colored glass articles having improved mechanical durability

    US11634354B2

  • Precursor glasses and glass-ceramics comprising a crystalline phase having a jeffbenite crystalline structure

    US11753331B1